Absorbent, water-absorbent resin, and absorbent article

By using a high gel expansion force water-absorbing resin in absorbents with a small fiber material content, the problem of insufficient liquid capture function in absorbent items such as thin diapers is solved, and efficient liquid capture and absorption magnification is achieved.

CN114929380BActive Publication Date: 2025-04-08NIPPON SHOKUBAI CO LTD
View PDF 33 Cites 0 Cited by

Patent Information

Application Number
CN202080091807.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-01-06
Filing Date
2020-12-22
Publication Date
2025-04-08
Estimated Expiration
2040-12-22

AI Technical Summary

Technical Problem

In absorbent articles such as thin diapers, the liquid capture function of absorbing urination after the second time is insufficient, especially the problem of insufficient liquid capture amount and absorption ratio under pressure.

Method used

A water-absorbent resin with a gel expansion force of 26N or more under 4.83 kPa pressure was used, and it was used in an absorber with a small fiber material content ratio, thereby improving the liquid capture ability and absorption ratio of the absorber for urination after the second time.

Benefits of technology

The liquid capture and absorption ratio of the absorber under pressure for urination after the second time is significantly improved, and the efficient absorption needs of absorbent items such as thin diapers are met.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114929380B_ABST
    Figure CN114929380B_ABST
Patent Text Reader

Abstract

Provided is an absorbent body, wherein when used in an absorbent article such as a thin diaper having an absorbent body with a low content ratio of fiber material (hydrophilic fiber) such as pulp, the absorbent article such as the diaper has a higher liquid capture function for urination after the second time than before, and in particular, the amount of liquid captured under pressure for urination after the second time is higher than before. Also provided is a water-absorbent resin for use in the absorbent body, which has a higher absorption rate under pressure for urination after the second time than before. The absorbent body contains a water-absorbent resin having a gel expansion force of 26N or more under a pressure of 4.83kPa.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an absorbent body, a water-absorbent resin used in the absorbent body, and an absorbent article including the absorbent body, wherein, when used in an absorbent article such as a thin diaper in which the ratio of a fiber material such as pulp contained in the absorbent body is small, the absorbent body has a higher liquid capture capacity under pressure for absorbing urination after the second time than before, and the water-absorbent resin has a higher absorption rate under pressure for absorbing urination after the second time than before. Background Art

[0002] In recent years, various sanitary products such as diapers for children, adults, and mild incontinence have shown a trend of becoming thinner, and the ratio of water-absorbent resin in the absorbent of these sanitary products has been increasing. Generally speaking, the absorbent is a composite formed by water-absorbent resin and wood crushed pulp. Wood crushed pulp is a hydrophilic fiber with cellulose as the main body. For example, wood crushed pulp helps the absorbent in the diaper to quickly absorb the urine just discharged into the absorbent and spread the urine throughout the absorbent (liquid capture function in a short time). However, with the thinning in recent years, the ratio of fiber materials such as pulp has decreased, and diapers with pulp-free absorbents have appeared. As a result, the liquid capture function in a short time that was previously undertaken by pulp in the absorbent needs to be replaced by water-absorbent resin.

[0003] That is, the next generation absorbents used in sanitary products such as diapers are required to have an excellent short-term liquid capture function even when the content ratio of the fiber material such as pulp is small. Furthermore, in view of the absorbent having an excellent short-term liquid capture function and a small content ratio of the fiber material such as pulp, the absorbent needs to have a water-absorbent resin having a better short-term liquid capture function than the conventional water-absorbent resin.

[0004] Therefore, in order to obtain an absorbent having an excellent liquid capturing function even when the content ratio of fiber materials such as pulp is small, and a water-absorbing resin having an improved liquid capturing function, improvements have been made by focusing on the water absorption rate of the water-absorbing resin. For example, the following patent documents 1 to 5 have proposed water-absorbing resins.

[0005] (Prior art literature)

[0006] (Patent Document)

[0007] Patent document 1: WO2016 / 111223A1

[0008] Patent Document 2: WO2019 / 221235A1

[0009] Patent document 3: EP3241861A1

[0010] Patent Document 4: EP3438162A1

[0011] Patent document 5: EP3260485A1 Summary of the invention

[0012] (Problem to be solved by the invention)

[0013] However, although the water-absorbent resins of Patent Documents 1 to 5 have excellent water absorption speed, when used in absorbent articles such as thin diapers in which the content ratio of fiber materials such as pulp contained in the absorbent body is small, the absorbent articles such as diapers have insufficient liquid capture function for absorbing urination after the second time. In particular, there are problems that the amount of liquid captured under pressure by the absorbent body for urination after the second time is insufficient and the absorption rate under pressure of the water-absorbent resin for urination after the second time is insufficient.

[0014] One aspect of the present invention aims to achieve a higher liquid capture function for absorbing urination after the second time than before even when an absorbent body having a low content ratio of a fiber material such as pulp is used in an absorbent article such as a thin diaper. The main object of the present invention is to provide an absorbent body having a higher liquid capture capacity for absorbing urination after the second time than before, and a water-absorbent resin used in the absorbent body having a higher absorption ratio for absorbing urination after the second time than before.

[0015] (Technical means to solve the problem)

[0016] The present inventors have conducted intensive research to solve the above problems, and as a result, found that when a water-absorbent resin having a gel expansion force of 26N or more under a pressure of 4.83kPa is used, the water-absorbent resin has a higher absorption rate under pressure for urination after the second time than before. When the water-absorbent resin is used in an absorbent body having a small content ratio of fiber materials such as pulp, it is found that the absorbent body has a higher amount of liquid captured under pressure for urination after the second time than before. It is found that when the absorbent body is used in an absorbent article such as a thin diaper, the absorbent article such as a diaper has a higher liquid capture function for urination after the second time than before, and the present inventors have completed the present invention.

[0017] That is, the absorbent core according to one embodiment of the present invention includes a water-absorbent resin having a gel swelling force of 26 N or more under a pressure of 4.83 kPa.

[0018] (Effects of the Invention)

[0019] According to one aspect of the present invention, it is possible to provide an absorbent body, wherein when the absorbent body is used in absorbent articles such as thin diapers having a low content ratio of fiber materials such as pulp, the absorbent articles such as diapers have a higher liquid capture function for absorbing urination after the second time than before, and in particular, the liquid capture amount under pressure for absorbing urination after the second time is higher than before; it is also possible to provide a water-absorbent resin having a higher absorption rate under pressure for absorbing urination after the second time than before. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a schematic front view for explaining cavities (recesses and cavities) formed in a water-absorbent resin according to one embodiment of the present invention.

[0021] Figure 2 This is a structural diagram of a unit group A used for measuring the time to reach a gel thickness of 5 mm, the gel swelling force, and the gel swelling rate of a water-absorbent resin according to one embodiment of the present invention.

[0022] Figure 3 This is an explanatory diagram of a method for measuring the time it takes for a water-absorbent resin to reach a gel thickness of 5 mm according to one embodiment of the present invention.

[0023] Figure 4 This is a schematic diagram of the sticking position of the white tape stuck on the top surface of the weight in unit set A.

[0024] Figure 5 This is a perspective view for explaining a method for measuring the gel swelling force and gel swelling rate of a water-absorbent resin according to one embodiment of the present invention, and shows a state where a load cell, a compression jig, and an AAP measuring instrument are provided on a tracer (Autograph).

[0025] Figure 6 This is a diagram for explaining the steps of a method for measuring the gel swelling power and gel swelling rate of a water-absorbent resin according to one embodiment of the present invention.

[0026] Figure 7 This is a diagram for explaining the structure of the unit group B used when measuring the absorption capacity under pressure of the water-absorbent resin for the second urination according to one embodiment of the present invention.

[0027] Figure 8 This is a schematic diagram of the sticking position of the white tape stuck on the top surface of the weight in unit set B.

[0028] Fig. 9 This is a schematic diagram showing a state in which a water-absorbent resin is placed in a cylinder used for SFC measurement and a nonwoven fabric simulating a liquid-permeable front sheet is placed on the water-absorbent resin.

[0029] Fig.10This is a diagram for explaining the structure of a unit group C used for measuring the amount of liquid captured under pressure of an absorbent body according to one embodiment of the present invention.

[0030] Fig.11 It is an explanatory diagram of a method for measuring the amount of liquid captured under pressure by an absorbent body according to one embodiment of the present invention.

[0031] <Description of Reference Numerals>

[0032] 1 weight

[0033] 2 Piston

[0034] 3 Cylinder

[0035] 4 Water-absorbent resin

[0036] 5. Tape

[0037] 6 Filter paper

[0038] 7 Glass filter

[0039] 8 0.9 mass% sodium chloride aqueous solution

[0040] 9 SUS Pallet

[0041] 10-side heater

[0042] 11 Bracket

[0043] 12 Fitting sleeve

[0044] 13 Clamp

[0045] 14 Sensor head

[0046] 15 Amplifier Unit

[0047] 16 Power supply unit

[0048] 17 Data Logger

[0049] 18 Laser irradiation direction

[0050] 19 Load cell

[0051] 20 Upper pressure plate

[0052] 21 Lower pressure plate

[0053] 22 weights

[0054] 23 Cover

[0055] 24 Cylinder

[0056] 25 Piston

[0057] 26 Non-woven fabric DETAILED DESCRIPTION

[0058] An embodiment of the present invention is described below, but the present invention is not limited thereto. The present invention is not limited to the various schemes described below, and various changes can be made within the scope shown in the specification. The embodiments and embodiments obtained by appropriately combining the technical means disclosed in different embodiments and embodiments are also included in the technical scope of the present invention. In addition, all documents recorded in this specification are cited in this specification as references. In this specification, if "A to B" is recorded about the numerical range, the record means "above A and below B".

[0059] [1] Definition of terms

[0060] [1-1] Water-absorbent resin

[0061] In this specification, "water-absorbent resin" refers to a water-insoluble polymer gelling agent that is swellable in water and is generally in the form of particles. In addition, "water-swellable" means that the absorption capacity under no pressure (CRC) specified in WSP241.3 (10) is 5 g / g or more, and "water-insoluble" means that the soluble content (Ext) specified in WSP270.3 (10) is 50% by mass or less. In addition, "CRC" is an abbreviation for Centrifuge Retention Capacity, which refers to the absorption capacity of a water-absorbent resin under no pressure.

[0062] The "water-absorbing resin" is preferably a hydrophilic cross-linked polymer obtained by cross-linking and polymerizing an unsaturated monomer containing a carboxyl group. However, the entire amount, i.e., 100% by mass, of the cross-linked polymer is not limited, and additives may be contained within the range of satisfying the required performances such as CRC and Ext.

[0063] The “water-absorbent resin” may refer to a “polymer cross-linked only internally, i.e., a polymer having substantially the same cross-linking density internally and on the surface” or a “polymer cross-linked both internally and on the surface, i.e., a polymer having a relatively higher cross-linking density on the surface than on the internal surface”.

[0064] In principle, the present specification does not distinguish between the "polymer crosslinked only internally" and the "polymer crosslinked both internally and on the surface", and they are all referred to as "water-absorbent resin". However, if it is necessary to clearly distinguish whether or not there is surface crosslinking, the "polymer crosslinked only internally" is referred to as "water-absorbent resin before surface crosslinking" because it is a polymer before surface crosslinking, and the "polymer crosslinked both internally and on the surface" is referred to as "water-absorbent resin after surface crosslinking" because it is a polymer after surface crosslinking. In addition, "before surface crosslinking" means "before adding a surface crosslinking agent" or "before the crosslinking reaction under heat treatment has started even though a surface crosslinking agent has been added".

[0065] The "water-absorbing resin" mentioned above may include components other than the resin, such as additives, in addition to the resin component alone.

[0066] [1-2] Acrylic acid (salt) monomers, polyacrylic acid (salt) water-absorbent resins

[0067] In the present specification, "acrylic acid (salt)" means acrylic acid and / or its salt, and "acrylic acid (salt)-based monomer" means that the content of acrylic acid (salt) therein is 50 mol% or more based on all monomers excluding the crosslinking agent.

[0068] In this specification, "polyacrylic acid (salt) water-absorbent resin" refers to a polymer made from acrylic acid (salt). That is, "polyacrylic acid (salt) water-absorbent resin" is a polymer containing a structural unit derived from acrylic acid (salt) and containing a graft component as an optional component.

[0069] Specifically, the polyacrylic acid (salt)-based water-absorbent resin is a polymer that preferably contains 50 mol% or more of acrylic acid (salt), more preferably 70 mol% or more of acrylic acid (salt), and further preferably 90 mol% or more of acrylic acid (salt), and preferably contains 100 mol% or less of acrylic acid (salt), and particularly preferably contains substantially 100 mol% of acrylic acid (salt), relative to the portion of the monomers participating in the polymerization reaction excluding the internal crosslinking agent.

[0070] [1-3] "EDANA" and "WSP"

[0071] "EDANA" is the abbreviation of European Disposables and Nonwovens Associations. "WSP" is the abbreviation of Worldwide Strategic Partners, which is a world standard measurement method for water-absorbent resins proposed by EDANA. In this specification, the physical properties of water-absorbent resins are measured in accordance with the original WSP (revised in 2010).

[0072] Unless otherwise specified in the present specification, the measurement of various physical properties of the water-absorbent resin was carried out according to the measurement methods in the Examples described later.

[0073] [1-4] Others

[0074] In the present specification, "a certain acid (salt)" means "a certain acid and / or its salt", and "(meth)acryl" means "acryl and / or methacryl".

[0075] [2] Method for producing water-absorbent resin

[0076] The water-absorbent resin according to one embodiment of the present invention has a gel expansion force of not less than 26 N under a pressure of 4.83 kPa. An example of a preferred method for producing the water-absorbent resin will be described below.

[0077] [2-1] Preparation process of monomer aqueous solution

[0078] This step is a step of preparing a monomer aqueous solution, which contains a monomer mainly composed of acrylic acid (salt) and at least one polymerizable internal crosslinking agent. Although a monomer slurry may also be used, for convenience, the monomer aqueous solution is used as an example in this specification.

[0079] (monomer)

[0080] As the monomer used in the present invention, for example, acrylic acid, maleic acid (anhydride), itaconic acid, cinnamic acid, vinyl sulfonic acid, allyl toluene sulfonic acid, vinyl toluene sulfonic acid, styrene sulfonic acid, 2-(meth)acrylamide-2-methylpropane sulfonic acid, 2-(meth)acryloyloxyethane sulfonic acid, 2-(meth)acryloyloxypropane sulfonic acid, 2-hydroxyethyl (meth)acryloyl phosphate and other anionic unsaturated monomers and / or their salts; unsaturated monomers containing mercapto groups; phenolic unsaturated monomers containing hydroxyl groups; unsaturated monomers containing amide groups such as (meth)acrylamide, N-ethyl (meth)acrylamide, N, N-dimethyl (meth)acrylamide; unsaturated monomers containing amino groups such as (meth)acrylamide, N, N-dimethylaminoethyl (meth)acrylic acid, N, N-dimethylaminopropyl (meth)acrylamide, etc. The monomer includes water-soluble or hydrophobic unsaturated monomers. Among these, acrylic acid (salt) is preferred. In addition, acrylic acid (salt) may be used in combination with other monomers. In this case, the amount of acrylic acid (salt) used is preferably 50 mol% or more, more preferably 70 mol% or more, further preferably 90 mol% or more, and particularly preferably substantially 100 mol% relative to all monomers except the crosslinking agent.

[0081] (Neutralization using alkaline compounds)

[0082] In the present invention, when acrylic acid (salt) monomers are used, acrylic acid is preferably partially neutralized with a basic compound. That is, in the present invention, a water-absorbing resin in which the acid groups of polyacrylic acid are partially neutralized is preferred.

[0083] As the alkaline compound, for example, carbonates and bicarbonates of alkali metals, hydroxides of alkali metals, ammonia, organic amines, etc. can be cited. Among them, from the viewpoint of the water absorption performance of the water-absorbing resin, a strongly alkaline compound is selected. Therefore, hydroxides of alkali metals such as sodium, potassium, and lithium are preferred, and sodium hydroxide is more preferred. In addition, from the viewpoint of handleability, the aqueous solution form of the alkaline compound is preferred. Commercially available sodium hydroxide contains heavy metals such as zinc, lead, and iron at the ppm level (mass basis), so strictly speaking, it can be said to be a composition. In the present invention, the composition is also included in the category of alkaline compounds.

[0084] The neutralization may be performed before, during or after the polymerization, and may be performed at multiple times or a plurality of times. In terms of the production efficiency of the water-absorbent resin, continuous neutralization is preferred.

[0085] In the present invention, when acrylic acid (salt) is used, the neutralization rate of acrylic acid (salt) is preferably 10 mol% or more, more preferably 40 mol% or more, further preferably 50 mol% or more, particularly preferably 60 mol% or more, and preferably 90 mol% or less, more preferably 85 mol% or less, further preferably 80 mol% or less, particularly preferably 75 mol% or less. When the neutralization rate is within this range, the decrease in the water absorption performance of the water-absorbent resin can be suppressed. The above-mentioned neutralization rate requirement also applies to the above-mentioned before polymerization, during polymerization, and after polymerization. In addition, it is also applicable to the water-absorbent resin.

[0086] (Internal crosslinking agent)

[0087] In the preferred production method of the present invention, an internal crosslinking agent is used. Examples of the internal crosslinking agent include N,N'-methylenebis(meth)acrylamide, (poly)ethylene glycol di(meth)acrylate, (poly)propylene glycol di(meth)acrylate, trimethylolpropane di(meth)acrylate, trimethylolpropane tri(meth)acrylate, glycerol tri(meth)acrylate, glycerol acrylate methacrylate, ethoxy-modified trimethylolpropane tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, triallyl cyanurate, triallyl isocyanurate, triallyl phosphate, triallylamine, poly(meth)allyloxyalkane, (poly)ethylene glycol diglycidyl ether, glycerol diglycidyl ether, ethylene glycol, polyethylene glycol, propylene glycol, glycerol, pentaerythritol, ethylenediamine, polyethyleneimine, glycidyl (meth)acrylate, and the like. At least one internal cross-linking agent is selected from these internal cross-linking agents in consideration of reactivity and the like.

[0088] In the present invention, from the viewpoint of the water absorption performance of the water-absorbent resin, it is preferred to select an internal crosslinking agent having two or more polymerizable unsaturated groups, and it is more preferred to select an internal crosslinking agent having a (poly) alkylene glycol structure and having two or more polymerizable unsaturated groups. As the polymerizable unsaturated group, specifically, an allyl group and a (meth) acrylate group can be mentioned. Among them, a (meth) acrylate group is preferred. In addition, as for the internal crosslinking agent having the (poly) alkylene glycol structure and having two or more polymerizable unsaturated groups, polyethylene glycol di(meth) acrylate can be mentioned. As for the number of alkylene glycol structural units (hereinafter, referred to as "n"), it is preferably 1 or more, more preferably 2 or more, further preferably 4 or more, and particularly preferably 6 or more, and is preferably 100 or less, more preferably 50 or less, further preferably 20 or less, and particularly preferably 10 or less.

[0089] The amount of the internal crosslinking agent used is preferably 0.0001 mol% or more, more preferably 0.001 mol% or more, further preferably 0.01 mol% or more, particularly preferably 0.02 mol% or more, and preferably 10 mol% or less, more preferably 5 mol% or less, further preferably 1 mol% or less, particularly preferably 0.50 mol% or less relative to the monomers other than the internal crosslinking agent. When the amount is within this range, a water-absorbent resin having the desired water-absorbing performance can be obtained. On the other hand, when the amount is outside this range, an increase in water-soluble components and a decrease in absorption rate may occur as the gel strength decreases.

[0090] In the present invention, the internal crosslinking agent may be added at a time that allows the polymer to be uniformly crosslinked, and examples thereof include a method of adding the internal crosslinking agent to the aqueous monomer solution before polymerization, during polymerization, or to the hydrogel after polymerization. Among them, a method of adding a predetermined amount of the internal crosslinking agent to the aqueous monomer solution in advance is preferred.

[0091] (Substances added to the aqueous monomer solution)

[0092] In the present invention, from the viewpoint of improving the physical properties of the water-absorbent resin, the following substances may be added to the monomer aqueous solution during the preparation of the monomer aqueous solution, during the polymerization reaction and the crosslinking reaction, or at least one of the following stages after the polymerization reaction and the crosslinking reaction.

[0093] Specific examples of such substances include hydrophilic polymers such as starch, starch derivatives, cellulose, cellulose derivatives, polyvinyl alcohol (PVA), polyacrylic acid (salts), and cross-linked products of polyacrylic acid (salts); and compounds such as carbonates, azo compounds, various foaming agents that generate bubbles, surfactants, chelating agents, and chain transfer agents.

[0094] The amount of the hydrophilic polymer added is preferably 50% by mass or less, more preferably 20% by mass or less, further preferably 10% by mass or less, particularly preferably 5% by mass or less, and preferably 0% by mass or more, and more preferably more than 0% by mass, relative to the aqueous monomer solution. In addition, the amount of the above-mentioned compound added is preferably 5% by mass or less, more preferably 1% by mass or less, further preferably 0.5% by mass or less, and preferably 0% by mass or more, and more preferably more than 0% by mass, relative to the aqueous monomer solution.

[0095] When a water-soluble resin or a water-absorbent resin is used as the hydrophilic polymer, a grafted polymer or a water-absorbent resin composition can be obtained, for example, starch-acrylic acid (salt) copolymer, PVA-acrylic acid (salt) copolymer, etc. These grafted polymers or water-absorbent resin compositions are also included in the category of polyacrylic acid (salt)-based water-absorbent resins.

[0096] (Concentration of monomer component)

[0097] The above-mentioned substances and components (hereinafter referred to as "monomer components") can be selected according to the purpose, and the amounts of the substances and components can be specified so as to satisfy the above-mentioned ranges, and the monomer aqueous solution can be prepared by mixing them with each other. In the present invention, the monomer can be in the form of an aqueous solution or a mixed solution of water and a hydrophilic solvent.

[0098] In addition, from the viewpoint of the physical properties of the water-absorbent resin, the total concentration of the monomer components is preferably 10% by mass or more, more preferably 20% by mass or more, and further preferably 30% by mass or more, and is preferably 80% by mass or less, more preferably 75% by mass or less, and further preferably 70% by mass or less. The concentration of the monomer components is calculated by the following formula (A).

[0099] Concentration of monomer component (mass %) = [(mass of monomer component) / (mass of monomer aqueous solution)] × 100 ... Formula (A)

[0100] In the above formula (A), "the mass of the monomer aqueous solution" does not include the mass of the graft component, the mass of the water-absorbing resin, and the mass of the hydrophobic organic solvent used in the reverse phase suspension polymerization.

[0101] [2-2] Polymerization process

[0102] This step is a step of polymerizing the monomer aqueous solution to obtain a hydrogel-like crosslinked polymer (hereinafter referred to as "hydrogel" for short). Preferably, it is a step of polymerizing the monomer aqueous solution obtained in the monomer aqueous solution preparation step and containing a monomer having acrylic acid (salt) as a main component and at least one polymerizable internal crosslinking agent to obtain a hydrogel.

[0103] (Polymerization initiator)

[0104] The polymerization initiator used in the present invention can be selected from one or more polymerization initiators commonly used in the production of water-absorbent resins, depending on the type of polymerization monomers and polymerization conditions. Examples of the polymerization initiator include thermal decomposition initiators and photodecomposition initiators.

[0105] Examples of the thermal decomposition initiator include persulfates such as sodium persulfate, potassium persulfate, and ammonium persulfate; peroxides such as hydrogen peroxide, tert-butyl peroxide, and methyl ethyl ketone peroxide; and azo compounds such as azonitrile compounds, azo amidine compounds, cyclic azo amidine compounds, azoamide compounds, alkylazo compounds, 2,2'-azobis(2-amidinopropane) dihydrochloride, and 2,2'-azobis[2-(2-imidazolin-2-yl)propane] dihydrochloride.

[0106] Examples of the photodegradable initiator include benzoin derivatives, benzyl derivatives, acetophenone derivatives, benzophenone derivatives, and azo compounds.

[0107] Among these, persulfate is preferred in view of the cost and the ability to suppress the occurrence of residual monomers. In addition, a reducing agent that promotes the decomposition of the oxidative polymerization initiator such as the persulfate or peroxide can also be used in combination, so as to obtain a redox system initiator by combining the oxidative polymerization initiator and the reducing agent. Examples of the reducing agent include: (heavy) sulfurous acid (salts) such as sodium sulfite and sodium bisulfite; reducing metals (salts) such as L-ascorbic acid (salts) and ferrous salts; amines, etc.

[0108] The amount of the polymerization initiator used is preferably 0.001 mol% or more, more preferably 0.01 mol% or more, and preferably 1 mol% or less, more preferably 0.5 mol% or less, and further preferably 0.1 mol% or less, relative to the monomers other than the internal crosslinking agent. In addition, the amount of the reducing agent used is preferably 0.0001 mol% or more, more preferably 0.0005 mol% or more, and preferably 0.02 mol% or less, more preferably 0.015 mol% or less, relative to the monomers other than the internal crosslinking agent. When the amount used is within this range, a water-absorbent resin having the desired water-absorbing performance can be obtained.

[0109] In the present invention, the polymerization reaction may be initiated by irradiation with active energy rays such as radiation, electron beams, and ultraviolet rays. In addition, irradiation with active energy rays and the polymerization initiator may be used in combination.

[0110] (Aggregate form)

[0111] As polymerization forms suitable for the present invention, aqueous solution polymerization, reversed phase suspension polymerization, spray polymerization, droplet polymerization, bulk polymerization, precipitation polymerization, etc. can be cited. Among them, from the viewpoint of easy controllability of polymerization and water absorption performance of water-absorbent resin, aqueous solution polymerization or reversed phase suspension polymerization is preferably selected, aqueous solution polymerization is more preferably selected, and continuous aqueous solution polymerization is further preferably selected. Regarding reversed phase suspension polymerization, there are records in International Publication No. 2007 / 004529, International Publication No. 2012 / 023433, etc. In addition, continuous aqueous solution polymerization can produce water-absorbent resin with higher productivity, and can be cited as continuous belt polymerization described in U.S. Patent No. 4893999, U.S. Patent No. 6906159, U.S. Patent No. 7091253, U.S. Patent No. 7741400, U.S. Patent No. 8519212, Japanese Patent Publication No. 2005-36100, etc., and continuous kneader polymerization described in U.S. Patent No. 6987151, etc.

[0112] Preferred forms of the continuous aqueous solution polymerization include high-temperature start polymerization, high-concentration polymerization, foaming polymerization, and the like. The "high-temperature start polymerization" refers to the following polymerization form: the temperature of the monomer aqueous solution at the start of the polymerization is preferably 35°C or above, more preferably 40°C or above, further preferably 45°C or above, and especially preferably 50°C or above, and is preferably below the boiling point of the monomer aqueous solution. In addition, "high-concentration polymerization" refers to the following polymerization form: the monomer concentration at the start of the polymerization is preferably 30% by mass or above, more preferably 35% by mass or above, further preferably 40% by mass or above, and especially preferably 45% by mass or above, and is preferably below the saturation concentration of the monomer aqueous solution. "Foaming polymerization" refers to the following polymerization form: the monomer aqueous solution containing a foaming agent or bubbles is polymerized. These polymerization forms can be implemented individually or in combination of two or more.

[0113] As for the method of dispersing bubbles used in the foaming polymerization, there are mentioned a method of reducing the solubility of the gas dissolved in the monomer aqueous solution to disperse the gas as bubbles, a method of introducing gas from the outside to disperse the gas as bubbles, a method of adding a foaming agent to the monomer aqueous solution to foam it, etc. Moreover, these dispersion methods can be appropriately used in combination according to the target physical properties of the water-absorbent resin.

[0114] When the gas is introduced from the outside, specific examples of the gas include oxygen, air, nitrogen, carbon dioxide, ozone, and mixed gases thereof. From the viewpoint of polymerizability and cost, inert gases such as nitrogen and carbon dioxide are preferably used, and nitrogen is more preferably used.

[0115] Usable foaming agents include azo compounds, organic or inorganic carbonate solutions, dispersions, and powders with a particle size of 0.1 μm to 1000 μm. Among them, inorganic carbonates are preferred, and specifically, carbonates and hydrogen carbonates such as sodium carbonate, ammonium carbonate, and magnesium carbonate can be used.

[0116] The foamed hydrogel obtained by foaming polymerization is easier to dry by gel crushing. In addition, by polymerizing the water-absorbing resin into a foamed state, the water absorption rate of the water-absorbing resin can be increased, and the water-absorbing resin can be more easily fixed in an absorbent article. The pores on the surface of the water-absorbing resin, such as pores with a diameter of 1 μm or more and 100 μm or less, can be confirmed by an electron microscope to determine whether it is foamed. The average number of pores per particle of the water-absorbing resin is preferably 1 or more, more preferably 10 or more, and preferably 10,000 or less, more preferably 1,000 or less. The number of pores can be controlled by the foaming polymerization.

[0117] [2-3] Gel crushing process

[0118] This process is a process of crushing the hydrogel, which is carried out in the middle of the polymerization process and / or after the polymerization process. Specifically, the hydrogel can be crushed in the polymerization process or after the polymerization process. That is, this process is a process of crushing the hydrogel to obtain a granular hydrogel (hereinafter referred to as "granular hydrogel"). In order to distinguish it from the "crushing" in the crushing process described later, this process is referred to as "gel crushing". In addition, the object of gel crushing is not only the hydrogel obtained in the polymerization process, but also includes the granulated gel obtained by recycling described later, unless otherwise specified. Unless otherwise specified, the purpose of the gel in other processes is the same.

[0119] The gel pulverization is a process for adjusting the hydrogel to a predetermined size using a kneader, a screw-type extruder such as a meat grinder, or a gel pulverizer such as a cutter mill.

[0120] When the hydrogel is subjected to gel grinding, it is preferred to add warm water and / or water vapor to the gel grinding machine. Adding warm water and / or water vapor is preferred because it is possible to obtain a granular hydrogel with low stickiness and good air permeability, and thus it is easy to dry. The temperature of the warm water is preferably 40°C or higher, more preferably 50°C or higher, and even more preferably 60°C or higher, and preferably 100°C or lower.

[0121] Regarding the implementation method and operating conditions of gel grinding, the contents described in the pamphlet of International Publication No. 2011 / 126079 are preferably applicable to the present invention. If the polymerization form is a kneader polymerization, this is equivalent to carrying out the polymerization step and the gel grinding step at the same time. In addition, in the present invention, a water-absorbent resin in a random crushed state can be obtained through the gel grinding step.

[0122] In the method for producing a water-absorbent resin of the present invention, it is more preferred that the fine powder recycling step includes: a granulation step of mixing the removed fine powder with an aqueous liquid to obtain a granulated gel; and a granulated gel adding step of adding the granulated gel to the hydrogel in at least one step and / or between steps in the process from the end of the gel pulverization step to the completion of the drying step. In the gel pulverization step of the present invention, it is more preferred that the gel pulverization energy is appropriately controlled. The particulate hydrogel obtained by gel pulverization at the gel pulverization energy specified below is evaluated to have a high water absorption rate even from the physical properties of the water-absorbent resin obtained thereafter, which can be evaluated by, for example, FSR described in International Publication No. 2009 / 016055 and Vortex described in JIS K7224 (1996) "Water absorption rate test method for super absorbent resin".

[0123] Here, the "gel grinding energy" in the present invention refers to the mechanical energy required by the gel grinding device per unit mass, i.e., the unit mass of the hydrogel, when the hydrogel is gel-ground, but does not include the energy for heating and cooling the outer cover and the energy of the introduced water and steam. Here, "gel grinding energy" is abbreviated as "GGE" according to the English abbreviation "Gel Grinding Energy".

[0124] If the gel grinding device is driven by three-phase alternating current, GGE can be calculated by the following formula (I).

[0125] GGE [J / g] = {√3×voltage×current×power factor×motor efficiency} / {mass of water-containing gel put into the gel mill per second} ... formula (I)

[0126] The above-mentioned "power factor" and "motor efficiency" are device-specific values ​​that vary depending on the operating conditions of the gel grinding device, and their values ​​range from 0 to 1. These values ​​can be obtained by asking the device manufacturer. In addition, if the gel grinding device is driven by single-phase alternating current, GGE can be calculated by simply replacing "√3" in the above formula (I) with "1". In addition, the unit of voltage is "[V]", the unit of current is "[A]", and the unit of the mass of the water-containing gel is "[g / s]".

[0127] The "power factor" and "motor efficiency" in the GGE are the values ​​when the gel is crushed. Since the current value during no-load operation is sometimes small, the power factor and motor efficiency values ​​during no-load operation are defined by formula (I) as an approximation. The "mass of the hydrous gel fed into the gel crusher per second" (g / s) in the formula (I) is, for example, the value obtained by converting the unit of the supply amount when the hydrous gel is continuously supplied by a quantitative feeder into [g / s]. However, as described later, the hydrous gel may also include granulated gel obtained by recycling.

[0128] The gel grinding energy (GGE) for gel grinding in the present invention is preferably 100 J / g or less, more preferably 80 J / g or less, and further preferably 60 J / g or less, and is preferably 20 J / g or more, more preferably 25 J / g or more, and further preferably 30 J / g or more. When the gel grinding energy is controlled within the above range, the gel can be ground while applying appropriate shear force and compression force to the hydrogel.

[0129] Here, if a screw extruder or a plurality of screw extruders are used after kneader polymerization, that is, if gel grinding is performed by a plurality of apparatuses, the energy consumed by each apparatus is summed up as gel grinding energy (GGE).

[0130] In addition, when the gel grinding energy is controlled as described above, a better effect can be obtained by adding warm water having the above temperature in combination. In addition, the gel grinding based on the gel grinding energy can be performed after the normal gel grinding.

[0131] From the viewpoint of easy drying and the physical properties of the obtained water-absorbent resin, the particle size of the granular hydrogel granulated by the gel pulverization step is preferably in the range of 0.1 mm or more and 10 mm or less. In addition, the mass average particle size (D50) of the granular hydrogel is preferably 0.1 mm or more, more preferably 0.15 mm or more, further preferably 0.20 mm or more, particularly preferably 0.25 mm or more, and is preferably 5 mm or less, more preferably 2 mm or less, further preferably 1 mm or less, particularly preferably 0.80 mm or less. If the mass average particle size (D50) of the granular hydrogel deviates from the above range, drying may be insufficient. In the present invention, the mass average particle size of the hydrogel provided to the drying step is preferably within the above range, and more preferably both the particle size and the mass average particle size satisfy the above range.

[0132] Regarding the particle size of the granular hydrogel, the logarithmic standard deviation of its particle size distribution reflects the narrowness of the particle size distribution, and the logarithmic standard deviation (σζ) is preferably 0.2 or more, and preferably 1.5 or less, more preferably 1.3 or less, and further preferably 1.2 or less. The smaller the value of the logarithmic standard deviation (σζ) of the particle size distribution, the more uniform the particle size, which has the advantage of being able to be dried uniformly. However, if the logarithmic standard deviation (σζ) of the particle size distribution is to be less than 0.2, special operations are required, such as particle size control during polymerization before gel pulverization, or classification of the granular hydrogel after gel pulverization, but this is substantially difficult to achieve from the perspective of productivity and cost.

[0133] In order to increase the specific surface area of ​​the water-absorbent resin described below, it is preferable to use the gel grinding method described in International Publication No. 2011 / 126079. In addition, the gel grinding method can also be used in combination with the above-mentioned foaming polymerization.

[0134] In order to dry uniformly and efficiently, the water content of the particulate hydrogel is preferably 30% by mass or more, more preferably 45% by mass or more, and is preferably 70% by mass or less, more preferably 55% by mass or less.

[0135] [2-4] Drying process

[0136] This step is a step of drying the hydrogel after the gel is crushed. Specifically, this step is a step of drying the granular hydrogel to a desired solid content to obtain a dry polymer; or, in the case where a granulated gel is added to the granular hydrogel, drying both the granulated gel and the granular hydrogel to a desired solid content to obtain a dry polymer. The value of the solid content, that is, the value obtained by subtracting the water content from 100% by mass of the gel, is preferably 80% by mass or more, more preferably 85% by mass or more, further preferably 90% by mass or more, particularly preferably 92% by mass or more, and preferably 99% by mass or less, further preferably 98% by mass or less, particularly preferably 97% by mass or less. When the solid content of the dry polymer is within the above range, pulverization, classification, and surface cross-linking can be carried out efficiently. "Drying completed" in this specification means a state where the solid content has reached 80% by mass. In this step, the dry polymer may be in a coagulum shape, and the water content of the top and bottom and the center / edge of the coagulum may be different. In this case, the dried polymer may be appropriately obtained from different locations, crushed as necessary, and then the moisture content may be measured and the average value may be obtained.

[0137] In this specification, a dried polymer that does not satisfy the above-specified solid content may be referred to as an "undried product". The "dried product" or "particulate hydrogel" in the drying process may include both the particulate hydrogel and the granulated gel. In particular, the drying process of the present invention is a more effective condition for the case where both the particulate hydrogel and the granulated gel are included. Here, similarly to other processes, the hydrogel and its processed product may include the granulated gel and its processed product.

[0138] The drying method in the drying process can include, for example, heating drying, hot air drying, reduced pressure drying, fluidized bed drying, infrared drying, microwave drying, azeotropic dehydration drying with a hydrophobic organic solvent, high humidity drying using high temperature steam, stirring drying, etc. These drying methods can be continuous or batch, but from the viewpoint of production efficiency, continuous is more preferred. In addition, from the viewpoint of drying efficiency, stirring drying and hot air drying are preferred. Regarding stirring drying, stirring drying machines such as paddle dryers or rotary drum dryers are preferably used. In addition, regarding hot air drying, it is preferred to use a ventilation belt dryer to perform hot air drying on its ventilation conveyor belt. By using a ventilation belt dryer, it is possible to prevent the dried polymer and the granular hydrogel on the way from being mechanically damaged and rubbed to produce fine powder, etc., and to efficiently dry.

[0139] From the viewpoint of drying efficiency, the drying temperature during hot air drying, that is, the hot air temperature, is preferably 120°C or higher, more preferably 130°C or higher, and more preferably 150°C or higher, and is preferably 250°C or lower, more preferably 230°C or lower, and more preferably 200°C or lower. In addition, the drying time is selected to be 10 minutes or more, more preferably 20 minutes or more, and more preferably 30 minutes or more, and is preferably 2 hours or less, more preferably 1.5 hours or less, and more preferably 1 hour or less. When the drying temperature and the drying time are within this range, the physical properties of the obtained water-absorbent resin can be within the expected range. Regarding other drying conditions, they may be appropriately set according to the moisture content, total mass and target solid content of the granular hydrogel and granulated gel to be dried. When belt drying is performed, the conditions described in International Publication No. 2006 / 100300, International Publication No. 2011 / 025012, International Publication No. 2011 / 025013, International Publication No. 2011 / 111657, etc. may be appropriately adopted.

[0140] (Ventilation belt dryer)

[0141] The dryer used in the present invention may be a continuous type or a batch type, but from the viewpoint of production efficiency, a continuous ventilated belt dryer is more preferred. When the object to be dried is dried using the continuous ventilated belt dryer, the object to be dried may be continuously provided to the belt of the belt dryer in a layered state (hereinafter referred to as a "gel layer") and dried with hot air. The belt width of the dryer is preferably 0.5 m or more, more preferably 1 m or more, and preferably 10 m or less, more preferably 5 m or less. The belt length is selected to be 20 m or more, more preferably 40 m or more, and preferably 100 m or less, more preferably 50 m or less.

[0142] The moving speed of the dried object on the belt can be appropriately set according to the conveyor belt width, conveyor belt length, production volume, drying time, etc., but from the viewpoint of the load and durability borne by the conveyor belt driving device, the moving speed is preferably 0.3 m / minute or more, more preferably 0.5 m / minute or more, and further preferably 0.7 m / minute or more, and is preferably 5 m / minute or less, more preferably 2.5 m / minute or less, further preferably 2 m / minute or less, and particularly preferably 1.5 m / minute or less.

[0143] The average thickness of the gel layer of the dried material spread on the ventilated belt dryer is preferably 3 cm or more, more preferably 5 cm or more, and further preferably 8 cm or more, and is preferably 30 cm or less, more preferably 20 cm or less, and further preferably 15 cm or less. In order to effectively achieve the above solid content under the above conditions, it is preferred to control the thickness of the gel layer within the above range. On the other hand, if the gel layer is too thick, undried materials tend to remain and drying is uneven, so that even if the above-specified drying process is performed, the proportion of the dried polymer that does not meet the above preferred solid content may be high.

[0144] [2-5] Crushing and Classification Process

[0145] The pulverizing step is a step of pulverizing the dried polymer, and the classification step is a step of removing fine powder from the pulverized polymer. Specifically, the dried polymer obtained in the drying step is pulverized in the pulverizing step, and the particle size is adjusted to a desired range in the classification step to obtain a water-absorbent resin. After the pulverizing step after drying, a water-absorbent resin in a random crushed state can be obtained.

[0146] The pulverizer used in the pulverizing step may include a roller mill, a hammer mill, a spiral mill, a pin mill, and other high-speed rotary pulverizers, a vibration mill, an elbow-type pulverizer, a cylindrical agitator, and the like. Among them, a roller mill is preferably selected from the viewpoint of pulverizing efficiency. In addition, a plurality of these pulverizers may be used in combination.

[0147] As a method for adjusting the particle size in the classification process, sieve classification using a JIS standard sieve (JIS Z8801-1 (2000)) or air flow classification can be cited. Among them, sieve classification is preferably selected from the viewpoint of classification efficiency. Here, from the viewpoint of easy pulverization, a classification process can also be additionally performed before the pulverization process.

[0148] Regarding the particle size distribution of the water-absorbent resin, the mass average particle size (D50) of the water-absorbent resin is preferably 250 μm or more and 600 μm or less, and the proportion of particles of 300 μm to 600 μm is preferably 50% by mass or more, and the proportion of particles below 150 μm is preferably 5% by mass or less. The upper limit of the mass average particle size (D50) is preferably 550 μm, more preferably 500 μm, and further preferably 450 μm. In addition, the proportion of particles of 300 μm to 600 μm is more preferably 55% by mass or more, further preferably 60% by mass or more, and particularly preferably 65% ​​by mass or more. In addition, the proportion of particles below 150 μm is preferably 4% by mass or less, more preferably 3% by mass or less, and further preferably 2% by mass or less. In addition, the proportion of particles exceeding 710 μm is preferably 3% by mass or less, more preferably 2% by mass or less, and further preferably 1% by mass or less. In addition, the logarithmic standard deviation (σζ) of the particle size distribution, which reflects the narrowness of the particle size distribution, is preferably 0.20 or more, more preferably 0.25 or more, and further preferably 0.27 or more, and preferably 0.50 or less, more preferably 0.40 or less, and further preferably 0.35 or less. The smaller the value of the logarithmic standard deviation (σζ) of the particle size distribution, the more uniform the particle size, that is, the less biased the particle distribution. Preferably, the mass average particle size (D50) and the proportion of particles below 150 μm satisfy the above range, more preferably the mass average particle size (D50), the proportion of particles below 150 μm, and the proportion of particles exceeding 710 μm all satisfy the above range, and further preferably the mass average particle size (D50), the proportion of particles below 150 μm, the proportion of particles exceeding 710 μm, and the logarithmic standard deviation all satisfy the above range, and appropriate combinations can be made within the above ranges.

[0149] The above-mentioned requirements for particle size also apply to the water-absorbent resin after the pulverization process and the classification process. Therefore, if surface crosslinking is performed, it is preferred to perform surface crosslinking treatment through the surface crosslinking process in a manner that the particle size of the water-absorbent resin before surface crosslinking, which is adjusted to the above-mentioned range, is maintained unchanged. It is more preferred to set a granulation process after the surface crosslinking process to adjust the particle size. The water-absorbent resin that does not pass through a sieve with a mesh size of 710 μm in the classification process is preferably returned to the pulverization process and pulverized again in the pulverization process. In addition, the water-absorbent resin that passes through a sieve with a mesh size of 150 μm in the classification process is preferably processed in the fine powder recycling process described later.

[0150] [2-6] Surface cross-linking process

[0151] This step is a step of further forming a portion with a high crosslinking density on the surface layer of the water-absorbent resin before surface crosslinking obtained through the above steps as needed, and this step includes a mixing step, a heat treatment step, a cooling step, etc. In the surface crosslinking step, free radical crosslinking, surface polymerization, and a crosslinking reaction with a surface crosslinking agent occur on the surface of the water-absorbent resin before surface crosslinking, thereby obtaining a surface crosslinked water-absorbent resin.

[0152] [2-6-1] Mixing process

[0153] This step is a step of mixing a solution containing a surface crosslinking agent (hereinafter referred to as "surface crosslinking agent solution") with a water-absorbent resin before surface crosslinking in a mixing device to obtain a wetted mixture.

[0154] (Surface cross-linking agent)

[0155] In the present invention, a surface crosslinking agent is used during surface crosslinking. As the surface crosslinking agent, for example, the surface crosslinking agent described in U.S. Patent No. 7183456 can be cited. Considering the reactivity, at least one surface crosslinking agent can be selected from these surface crosslinking agents. In addition, from the viewpoints of the operability of the surface crosslinking agent and the water absorption performance of the water-absorbent resin, it is preferred to select an organic compound having two or more functional groups that can react with a carboxyl group and can form a covalent bond as the surface crosslinking agent.

[0156] Specific examples of the surface crosslinking agent include ethylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, polyethylene glycol, propylene glycol, dipropylene glycol, polypropylene glycol, 1,3-propylene glycol, 1,2-butylene glycol, 1,3-butylene glycol, 1,4-butylene glycol, 2,3-butylene glycol, 1,2-pentanediol, 1,3-pentanediol, 1,4-pentanediol, 1,5-pentanediol, 2,3-pentanediol, 2,4-pentanediol, 1,2-hexanediol, 1,3-pentanediol, 1,4-pentanediol, 1,5-pentanediol, 2,3-pentanediol, 2,4-pentanediol, 1,2-hexanediol, 1,3- 1,4-hexanediol, 1,5-hexanediol, 1,6-hexanediol, 2,3-hexanediol, 2,4-hexanediol, glycerol, polyglycerol, diethanolamine, triethanolamine and other polyol compounds; ethylenediamine, diethylenetriamine, triethylenetetramine, tetraethylenepentamine, pentaethylenehexamine, polyallylamine, polyethyleneimine and other polyamine compounds; halogenated epoxy compounds, polyamine compounds and condensation products of halogenated epoxy compounds; oxazoline compounds such as 1,2-ethylenebisoxazoline; oxazole Alkanone compounds; 1,3-dioxolan-2-one (ethylene carbonate), 4-methyl-1,3-dioxolan-2-one, 4,5-dimethyl-1,3-dioxolan-2-one, 4,4-dimethyl-1,3-dioxolan-2-one, 4-ethyl-1,3-dioxolan-2-one, 4-hydroxymethyl-1,3-dioxolan-2-one, 1,3-dioxan-2-one, 4-methyl-1,3-dioxan-2-one Alkyl carbonate compounds such as 2-ketone, 4,6-dimethyl-1,3-dioxahexane-2-one, 1,3-dioxahexane-2-one; polyglycidyl compounds such as ethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, glycerol polyglycidyl ether, diglycerol polyglycidyl ether, polyglycerol polyglycidyl ether, and glycidol; oxetane compounds; vinyl ether compounds; cyclic urea compounds, etc.

[0157] If a plurality of the surface crosslinking agents are used, the total amount of these surface crosslinking agents used is preferably 0.01 parts by mass or more, and preferably 10 parts by mass or less, more preferably 5 parts by mass or less, and further preferably 2 parts by mass or less, relative to 100 parts by mass of the water-absorbent resin before surface crosslinking. When the amount of the surface crosslinking agent used is within this range, an optimal crosslinking structure can be obtained on the surface layer of the water-absorbent resin before surface crosslinking, thereby obtaining a water-absorbent resin with high physical properties.

[0158] The surface crosslinking agent is preferably added to the water-absorbent resin before surface crosslinking in the form of an aqueous solution. In this case, the amount of water used is preferably 0.1 parts by mass or more, more preferably 0.3 parts by mass or more, and further preferably 0.5 parts by mass or more, and preferably 20 parts by mass or less, more preferably 15 parts by mass or less, and further preferably 10 parts by mass or less, relative to 100 parts by mass of the water-absorbent resin before surface crosslinking. When the amount of water used is within this range, the operability of the surface crosslinking agent solution can be improved, and the surface crosslinking agent can be uniformly mixed into the water-absorbent resin before surface crosslinking.

[0159] In addition, as required, a hydrophilic organic solvent can be used together with the water to form the surface crosslinking agent solution. In this case, the amount of the hydrophilic organic solvent used is preferably 5 parts by mass or less, more preferably 3 parts by mass or less, and further preferably 1 part by mass or less relative to 100 parts by mass of the water-absorbent resin before surface crosslinking. As the hydrophilic organic solvent, specifically, lower alcohols such as methanol; ketones such as acetone; ethers such as dioxane; amides such as N,N-dimethylformamide; sulfones such as dimethyl sulfoxide; polyols such as ethylene glycol, etc. However, when using these hydrophilic organic solvents, it is preferred to limit the amount used to as little as possible.

[0160] In addition, various additives described in the column "[2-7] Additives and their adding step" described later may be added to the surface crosslinking agent solution in an amount of 5 parts by mass or less, or may be added separately in a mixing step.

[0161] (Mixing method, mixing conditions)

[0162] The water-absorbent resin before surface crosslinking and the surface crosslinking agent solution may be mixed by preparing a surface crosslinking agent solution in advance and preferably spraying or dropping the solution onto the water-absorbent resin before surface crosslinking, more preferably spraying the solution to mix.

[0163] The mixing device for performing the mixing preferably has a torque required to uniformly and reliably mix the water-absorbent resin before surface crosslinking with the surface crosslinking agent. The mixing device is preferably a high-speed stirring mixer, more preferably a high-speed stirring continuous mixer. The rotation speed of the high-speed stirring mixer is preferably 100 rpm or more, more preferably 300 rpm or more, and preferably 10000 rpm or less, more preferably 2000 rpm or less.

[0164] From the viewpoint of the miscibility with the surface crosslinking agent solution and the cohesiveness of the humidified mixture, the temperature of the water-absorbent resin before surface crosslinking provided to this step is preferably 35° C. or higher and preferably 80° C. or lower, more preferably 70° C. or lower, and still more preferably 60° C. or lower. In addition, the mixing time is preferably 1 second or longer, more preferably 5 seconds or longer, and preferably 1 hour or shorter, more preferably 10 minutes or shorter.

[0165] [2-6-2] Heat treatment process

[0166] This step is a step of heating the humidified mixture obtained in the mixing step to cause a crosslinking reaction on the surface of the water-absorbent resin before the surface crosslinking. Regarding the heat treatment of the humidified mixture, the humidified mixture may be heated in a static state or in a fluid state by a motive force such as stirring. However, from the point of view that the entire humidified mixture can be heated uniformly, it is preferably heated under stirring. From the above viewpoint, the heat treatment device for the heat treatment may include a paddle dryer, a multi-blade stirrer, a tower dryer, and the like.

[0167] From the viewpoint of the type and amount of the surface crosslinking agent and the water absorption performance of the water-absorbent resin, the heating temperature in this step is preferably 100° C. or higher, more preferably 150° C. or higher, further preferably 170° C. or higher, particularly preferably 180° C. or higher, and preferably 250° C. or lower, more preferably 230° C. or lower. In addition, the heating time is preferably at least 5 minutes, more preferably at least 7 minutes. By controlling the heating temperature and the heating time within the above range, the water absorption performance of the obtained water-absorbent resin can be improved, which is preferred.

[0168] [2-6-3] Cooling process

[0169] This step is an optional step provided after the heat treatment step as needed. This step is a step of forcibly cooling the high-temperature water-absorbent resin after the heat treatment step to a predetermined temperature to rapidly stop the surface crosslinking reaction.

[0170] The water-absorbent resin may be cooled in a static state or in a fluid state by a stirring or other dynamic force. However, it is preferably cooled under stirring because the entire water-absorbent resin can be uniformly cooled. From the above viewpoint, examples of cooling devices for the cooling include a paddle dryer, a multi-blade stirrer, a tower dryer, and the like. These cooling devices may be of the same specifications as the heat treatment device used in the heat treatment step. The heat treatment device can be used as a cooling device by replacing the heat medium with a refrigerant.

[0171] The cooling temperature in this step can be appropriately set depending on the heating temperature in the heat treatment step, the water absorption performance of the water-absorbent resin, etc., and is preferably 40°C or higher, more preferably 50°C or higher, and is preferably 100°C or lower, more preferably 90°C or lower, and further preferably 70°C or lower.

[0172] [2-7] Additives and their adding process

[0173] In the present invention, in addition to the above-mentioned steps, a step of adding the following additives (surface modifier, other additives) to the water-absorbing resin may be carried out as necessary.

[0174] [2-7-1] Surface modifier

[0175] The surface modifier is an additive added to modify the surface of the particles of the water-absorbent resin. Specifically, there can be cited agents for improving liquid permeability, anti-caking agents under moisture absorption, powder flow control agents, binders for water-absorbent resins, etc. In particular, from the viewpoint of improving liquid permeability, at least one compound selected from polyvalent metal salts, cationic polymers, and inorganic microparticles can be used, and two or more compounds can be used in combination as needed. The amount of the surface modifier added can be appropriately set according to the selected compound. In order to achieve the purpose of modifying the surface of the particles of the water-absorbent resin, the process of adding the surface modifier is preferably carried out after the polymerization process, more preferably after the drying process, and further preferably after the surface cross-linking process. In addition, the addition of the surface modifier can be carried out in any one or more processes.

[0176] (polyvalent metal salt)

[0177] If a polyvalent metal salt is used, the polyvalent metal cation of the polyvalent metal salt is preferably divalent or more, more preferably divalent or more, and preferably tetravalent or less, and further preferably trivalent or tetravalent. In addition, examples of polyvalent metals that can be used include aluminum, zirconium, and the like. Therefore, examples of polyvalent metal salts that can be used in this step include aluminum lactate, zirconium lactate, aluminum sulfate, zirconium sulfate, and the like. Among them, from the viewpoint of the effect of improving the flow conductivity (SFC) of the salt water, aluminum lactate or aluminum sulfate is more preferred, and aluminum sulfate is further preferred.

[0178] The amount of the polyvalent metal salt added is preferably 0 mol or more and preferably less than 3.6×10 -5 mole, more preferably less than 1.4×10 -5 mole, and preferably less than 1.0×10 -5 Moore.

[0179] The polyvalent metal-containing solution may further contain a monovalent metal compound such as sodium hydroxide, sodium carbonate, sodium bicarbonate, sodium acetate, sodium lactate, etc. as a regulator for regulating the permeability of the polyvalent metal into the water-absorbent resin.

[0180] (Cationic polymer)

[0181] If a cationic polymer is used, the cationic polymer may be a substance described in U.S. Pat. No. 7,098,284. Among them, vinylamine polymers are more preferred from the viewpoint of improving liquid permeability. In addition, the mass average molecular weight of the cationic polymer is preferably 5,000 or more and 1,000,000 or less.

[0182] The amount of the cationic polymer added is preferably 0 parts by mass or more, and preferably less than 2.5 parts by mass, more preferably less than 2.0 parts by mass, and further preferably less than 1.0 parts by mass, relative to 100 parts by mass of the water-absorbent resin.

[0183] (Inorganic particles)

[0184] If inorganic particles are used, the inorganic particles include those described in U.S. Patent No. 7638570. Among them, silicon dioxide is preferred from the viewpoint of improving liquid permeability. In addition, from the viewpoint of the balance between the absorption capacity under pressure and the hygroscopic fluidity, the inorganic particles are preferably hydrotalcite, calcium phosphate, and aluminum hydroxide.

[0185] When the primary particle diameter of the inorganic fine particles is less than 20 nm, the amount of the inorganic fine particles added is preferably 0 parts by mass or more, and preferably less than 1.2 parts by mass, more preferably less than 1.0 parts by mass, and further preferably less than 0.5 parts by mass, relative to 100 parts by mass of the water-absorbent resin. In addition, when the primary particle diameter of the inorganic fine particles is 20 nm or more, the amount of the inorganic fine particles added is preferably 0 parts by mass or more, and preferably less than 2.0 parts by mass, more preferably less than 1.5 parts by mass, and further preferably less than 1.0 parts by mass, relative to 100 parts by mass of the water-absorbent resin.

[0186] When at least one compound selected from the polyvalent metal salt, cationic polymer and inorganic fine particles is added to the water-absorbent resin, the absorption capacity under pressure of the water-absorbent resin may be reduced. One of the purposes of the present invention is to improve the absorption capacity under pressure of the water-absorbent resin for urination after the second time, so from this point of view, the amount of the compound added is limited. Regarding the amount added, when the absorption capacity under pressure of the water-absorbent resin to which the compound is not added is a (g / g) and the absorption capacity under pressure of the water-absorbent resin to which the compound is added is b (g / g), the amount added is an amount that does not prevent the difference "a-b" (g / g) between the two absorption capacities under pressure to be preferably within 0.30 g / g, more preferably within 0.10 g / g, further preferably within 0.05 g / g, and particularly preferably 0.00 g / g.

[0187] [2-7-2] Other additives

[0188] As other additives, chelating agents, reducing agents, hydroxycarboxylic acid compounds, surfactants, compounds containing phosphorus atoms, oxidants, organic powders such as metal soaps, deodorants, antibacterial agents, pulp and thermoplastic fibers, aromatic substances such as terpene aromatic compounds and phenol aromatic compounds, etc., can be cited. One or more of these can be used. As other additives, chelating agents are preferred, and amino polycarboxylic acids or amino polyphosphoric acids are more preferred. Specifically, Japanese Patent Publication No. 11-060975, International Publication No. 2007 / 004529 Pamphlet, International Publication No. 2011 / 126079 Pamphlet, International Publication No. 2012 / 023433 Pamphlet, Japanese Patent Publication No. 2009-509722, Japanese Patent Publication No. 2005 Chelating agents described in JP-A-097519, JP-A-2011-074401, JP-A-2013-076073, JP-A-2013-213083, JP-A-59-105448, JP-A-60-158861, JP-A-11-241030, JP-A-2-41155, and the like.

[0189] As in the case of the aforementioned polyvalent metal salt, cationic polymer and inorganic fine particles, if other additives (preferably chelating agents) are added to the water-absorbent resin, the absorption capacity under pressure of the water-absorbent resin may decrease. Therefore, the amount of other additives added is also limited. Regarding the amount of addition, when the absorption capacity under pressure of the water-absorbent resin without the aforementioned other additives is set to a (g / g), and the absorption capacity under pressure of the water-absorbent resin to which the aforementioned other additives are added is set to b (g / g), the amount of addition is an amount of addition that does not hinder the following matters: the difference "a-b" (g / g) between the two types of absorption capacity under pressure is preferably within 0.30 g / g, more preferably within 0.10 g / g, further preferably within 0.05 g / g, and particularly preferably 0.00 g / g. This is the same as the requirement for the amount of addition of at least one compound selected from the aforementioned polyvalent metal salt, cationic polymer and inorganic fine particles. Specifically, the amount or content of the other additives is preferably in the range of 0 part by mass or more and 1 part by mass or less relative to the monomer or the water-absorbing resin.

[0190] The additive may be added before, during or after at least one step selected from the above-mentioned monomer aqueous solution preparation step, polymerization step, gel grinding step, drying step, grinding step, classification step, and surface cross-linking step. Preferably, the additive is added before, during or after any step after the polymerization step.

[0191] [2-7-3] Additive Addition Process

[0192] If the additive is added to the water-absorbent resin and the additive is in the form of a liquid or a solution containing an aqueous medium such as water, it is preferred to spray the liquid or solution onto the water-absorbent resin and apply sufficient torque to uniformly and reliably mix the water-absorbent resin and the additive. On the other hand, if the additive is a solid such as a powder, it can be dry-mixed with the water-absorbent resin, and an aqueous liquid such as water can be used as a binder.

[0193] As for the device used for the mixing, specifically, there can be mentioned a stirring type mixer, a cylindrical mixer, a double-walled cone mixer, a V-shaped mixer, a bow tie mixer, a spiral mixer, a flow type rotary disk mixer, an air flow mixer, a double arm kneader, an internal mixer, a pulverizing kneader, a rotary mixer, a spiral extruder, etc. Here, if a stirring type mixer is used, the number of revolutions is preferably 5 rpm or more, more preferably 10 rpm or more, and preferably 10000 rpm or less, more preferably 2000 rpm or less.

[0194] [2-8] Granulation process

[0195] In the present invention, in addition to the above-mentioned steps, a granulation step can be implemented as needed. The granulation step refers to a step of adjusting the particle size of the surface-crosslinked water-absorbent resin obtained by the surface crosslinking step to the expected range, thereby obtaining a water-absorbent resin that is in a state ready for shipment as a final product. However, if there is no crushing step and classification step before the surface crosslinking step, the operations described later after the surface crosslinking step are used as crushing steps and classification steps. The particle size adjustment method in the granulation step can adopt the same adjustment method as the classification step. In addition, if the water-absorbent resin agglomerates in the surface crosslinking step and the surface modifier addition step, it can also be broken up, for example, lightly crushed. In addition, the particle size distribution after the particle size adjustment can also be appropriately designed depending on the purpose, preferably to the same degree as the classification step. Therefore, in a manner that satisfies the expected mass average particle size (D50), the ratio of the mass average particle size (D50), and the logarithmic standard deviation, etc., it is sufficient to use a sieve or the like for classification.

[0196] [2-9] Micropowder recycling process

[0197] In the present invention, in addition to the above-mentioned steps, a step of recycling fine powder can be implemented as needed. This step (fine powder recycling step) is a step of recycling the fine powder removed in the classification step to a stage before the drying step is completed. Specifically, it is a step of recycling the fine powder obtained in the water-absorbent resin production step to a preparation step, preferably a stage before the drying step, to produce a water-absorbent resin.

[0198] Examples of the step before the drying step include a step of preparing a monomer aqueous solution, a step of gel-crushing the hydrogel, and a step of drying the finely granulated gel.

[0199] If the fine powder is to be reused in the step of preparing the monomer aqueous solution, the fine powder can be added to the monomer aqueous solution to prepare a slurry, and then the desired polymerization reaction can be started. Alternatively, instead of adding the fine powder, the granulated gel described below can be added to the monomer aqueous solution, and then the desired polymerization reaction can be started.

[0200] If the fine powder is to be reused in the gel pulverization step of the hydrogel, the hydrogel and the fine powder may be simultaneously supplied to a predetermined gel pulverizer, so that the hydrogel and the fine powder are integrated during discharge.

[0201] The fine powder to be recycled is preferably the fine powder removed in the classification step, and more preferably the fine powder removed in the classification step and the granulation step. However, the fine powder does not necessarily have to be recycled to the water-absorbent resin production process that is strictly the same as the water-absorbent resin production process in which the fine powder is produced, and it can also be recycled to other water-absorbent resin production processes that are different in degree and do not affect the gist of the present invention. For example, the fine powder produced in a certain production line can be recycled to an adjacent production line, and the polymerization conditions can be changed in the process between the fine powder removal process and the fine powder recycling process in the same production line.

[0202] [2-9-1] Granulation process

[0203] This step is a step of mixing the removed fine powder with an aqueous liquid to obtain a granulated gel. The granulated gel refers to a gel in which a plurality of individual particles are aggregated, agglomerated or fused into a larger granular gel under optical microscope observation, and preferably has a strength that is not damaged by classification operations, handling operations, etc.

[0204] (fine powder)

[0205] In the present invention, all fine powders obtained in the process of producing the water-absorbent resin are used as the object, preferably the fine powder removed in the classification step, and more preferably the fine powder removed in the classification step and the granulation step, and an aqueous liquid is added to the fine powder to perform granulation. The mixing ratio (mass ratio) of the fine powder removed in the classification step and the fine powder removed in the granulation step is preferably 99:1 to 50:50, more preferably 98:2 to 60:40, and further preferably 95:5 to 70:30. Since the fine powder removed in the granulation step has already been through the surface cross-linking step, and sometimes has not only been through the surface cross-linking step but also has been through the surface modifier addition step described in the above "surface modifier" column, it is advantageous to use the fine powder removed in the granulation step in a predetermined ratio in the granulation step because the cohesion of the granulated gel can be reduced. In the present invention, for example, fine powder removed from a filter bag or the like in each manufacturing process may be used for granulation, and fine powder removed in a different process and fine powder removed in another manufacturing process (other manufacturing apparatus) may be mixed and used. In addition, the fine powder and the hydrogel dried with it may be the same component or different components, but it is preferred that the fine powder used is derived from the hydrogel dried with it and has the same component as the hydrogel.

[0206] The size of the fine powder provided for granulation is preferably lower than the final product size of the water-absorbent resin. For example, the upper limit of the mass average particle size (D50) of the fine powder specified by the JIS standard sieve classification method is preferably 150μm, and more preferably 106μm. The lower limit of the mass average particle size (D50) of the fine powder is preferably 38μm, and more preferably 45μm. Although this process is for fine powder, the agglomerates exceeding the size of the final product can also be appropriately crushed and used as fine powder for granulation. Preferably, the content of particles having a particle size lower than 150μm specified by the JIS standard sieve classification method is preferably 50% by mass or more, more preferably 70% by mass or more, and further preferably 90% by mass or more, and preferably 100% by mass or less. In addition, from the perspective of granulation strength, the shape of the fine powder is more preferably the irregular shape obtained by aqueous solution polymerization compared to the spherical shape obtained by reverse suspension polymerization. As described above, the fine powder may be fine powder removed after the surface cross-linking step generally performed in the production of the water-absorbent resin, may be fine powder removed before the surface cross-linking step, or may be a mixture thereof.

[0207] Granulated gel can be obtained by adding an aqueous liquid to the fine powder, preferably to a mixture of the fine powders at a predetermined ratio. Granulated gel uses fine powders having various particle sizes obtained in the above-mentioned single process or multiple processes.

[0208] The temperature of the fine powder when mixed with the aqueous liquid is preferably 40°C or more, more preferably 50°C or more, and further preferably 60°C or more, and is preferably 120°C or less, more preferably 100°C or less, and further preferably 90°C or less. By increasing the temperature of the fine powder, the miscibility of the fine powder with the aqueous liquid can be improved, and the desired granulated gel can be easily obtained. On the other hand, if the temperature of the fine powder is raised too high, the heating cost will increase. As needed, the temperature of the fine powder can be appropriately adjusted by the following means: heating from the outside by hot air, etc.; keeping warm after heating in the drying process; or cooling by blowing room temperature air, etc. Preferably, the fine powder is heated or kept warm in a container with a heating means such as a heated steam pipe.

[0209] (Aqueous liquid)

[0210] As for the aqueous liquid used to mix with the micropowder, specifically, aqueous solutions containing the following components can be cited: lower alcohols such as water, methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, tert-butanol, etc.; ketones such as acetone; ethers such as dioxane and tetrahydrofuran; amides such as N, N-dimethylformamide; sulfones such as dimethyl sulfoxide, etc. From the perspective of physical properties and granulation strength, the water content of the aqueous liquid is preferably 90% by mass or more, more preferably 99% by mass or more, and preferably in the range of 100% by mass or less, and it is particularly preferred to be composed of water only. In addition, within the scope that does not affect the effect of the present invention, the aqueous liquid may also contain a small amount of other additives such as crosslinking agents, chelating agents, surfactants, polymerization initiators, oxidants, reducing agents, hydrophilic polymers, etc. The additives may be added in one or more kinds, and the types of the additives when adding more than two kinds are not required. For example, by using an aqueous liquid to which the polymerization initiator and reducing agent described in the polymerization process are added, the occurrence of residual monomers in the granulated gel and the hydrogel can be reduced. A preferred polymerization initiator is a persulfate, and a preferred reducing agent is a (heavy)sulfurous acid (salt). For example, by using an aqueous liquid to which an oxidant is added, it is sometimes possible to suppress the decrease in physical properties such as absorption rate when the granulated gel is dried. A preferred oxidant is at least one oxidant selected from chlorites, hypochlorites, and peroxides, and more preferably hydrogen peroxide. For example, by using an aqueous liquid to which a surfactant is added, the granulated gel can contain a surfactant, thereby effectively suppressing the granulated gel from agglomerating with each other. Examples of the surfactant include anionic surfactants, nonionic surfactants, cationic surfactants, and amphoteric surfactants. In addition, by using an aqueous liquid to which a crosslinking agent and a hydrophilic polymer are added, the cohesive strength of the corresponding granulated gel can be increased, thereby suppressing re-micronization in the subsequent process. The crosslinking agent is selected from the aforementioned internal crosslinking agent and surface crosslinking agent, and the hydrophilic polymer is selected from the aforementioned hydrophilic polymer added to the monomer aqueous solution.

[0211] In addition, if the fine powder contains the aforementioned additives such as the cross-linking agent, chelating agent, surfactant, polymerization initiator, oxidizing agent, reducing agent, etc., the additives may not be added to the aqueous liquid, or only the missing additives may be added to the aqueous liquid. The fine powder preferably contains the chelating agent, surfactant, oxidizing agent, reducing agent, etc. mentioned in the "additive addition step" column.

[0212] When the fine powder is mixed with an aqueous liquid for granulation, it is preferred to use a preheated aqueous liquid. By using a heated aqueous liquid, the fine powder can be granulated uniformly in a short time, thereby improving productivity. The temperature of the aqueous liquid is preferably above 40°C, more preferably above 50°C, further preferably above 60°C, and particularly preferably above 70°C, and is preferably below the boiling point of the aqueous liquid, more preferably below 100°C. The boiling point of the aqueous liquid can be adjusted by adding salts and solvents, and by pressure conditions such as reduced pressure and increased pressure. In addition, as another method, water vapor and an aqueous liquid at room temperature can be added simultaneously to substantially achieve the above-mentioned temperature.

[0213] Relative to 100 parts by mass of micropowder (original form), the addition amount of aqueous liquid is preferably less than 100 parts by mass, more preferably less than 80 parts by mass, and further preferably less than 50 parts by mass, and preferably more than 10 parts by mass, more preferably more than 15 parts by mass, and further preferably more than 20 parts by mass. If the addition amount of aqueous liquid is more than 100 parts by mass, the burden during drying is large. On the other hand, if the addition amount of aqueous liquid is less than 10 parts by mass, the granulation strength may be insufficient, and the mixing of micropowder may also be uneven, which may easily lead to damage to the granulated material.

[0214] (Mixing device)

[0215] Regardless of the aforementioned embodiment, the mixing device used when mixing the aqueous liquid with the micropowder in the present invention is not particularly limited. For example, if it is a container-fixed mixer, a mechanical stirring mixer is preferred. Specifically, a turbulent agitator (turbulizer; manufactured by Hosokawa MICRON Co., Ltd.), a Loedige agitator (manufactured by Loedige Co., Ltd.), and a mortar agitator (manufactured by West Japan Testing Machine Co., Ltd.) can be exemplified. In addition, both a batch mixer and a continuous mixer can be used for mixing.

[0216] In the present invention, it is preferred that the heated aqueous liquid and the heated fine powder are mixed in the above-mentioned mixing device. In the present invention, it is more preferred that on the basis of heating the aqueous liquid and the fine powder, the inside of the mixing device is also heated. Specifically, the wall surface of the mixing device and / or the stirring means such as the stirring blade can be heated. In this way, when the inside of the mixing device, the aqueous liquid, and the fine powder are all heated to a specified temperature, the mixing is carried out, and a granulated gel with a desired particle size can be obtained more effectively and more easily. In the present invention, even if the fine powder, the aqueous liquid, and the mixing device are not heated, such an effect can be obtained, but it is preferred that at least one of them, more preferably two, and further preferably all of them are heated to a specified temperature, so as to obtain a more superior effect.

[0217] During the mixing, the heating temperature in the mixing device, preferably the heating temperature of the inner wall surface of the mixing device and / or the stirring means is preferably 50°C or more, more preferably 55°C or more, further preferably 60°C or more, particularly preferably 65°C or more, most preferably 70°C or more, and preferably 120°C or less, more preferably 100°C or less, and further preferably 90°C or less. By heating the mixing device, preferably by heating the inner wall surface or the stirring means, more preferably by heating both, the micropowder can be uniformly granulated in a short time, thereby improving productivity. The temperature in the mixing device can be appropriately adjusted, for example, by supplying heated gas, or by electrical conduction and heat conduction.

[0218] In the present invention, when the fine powder is mixed with the aqueous liquid, it is preferred to granulate by high-speed mixing. By performing high-speed mixing, the formation of a giant gel-like substance can be suppressed, so that a huge mixing force required for the formation of a giant gel-like substance does not need to be consumed, and the following problem can be avoided: the gel-like agglomerates become a kneaded state, causing the main chain to break or entangle, resulting in the deterioration of the water-absorbing resin.

[0219] The high-speed mixing means that the time from the contact point between the fine powder as the raw material and the aqueous liquid to the generation of the granulated gel in the mixing device is short. That is, the time from the time when the raw material is added to the mixing device to the time when the granulated gel is taken out is short. The mixing time is preferably less than 3 minutes, more preferably less than 1 minute, and preferably more than 1 second, more preferably more than 5 seconds. If the mixing time is long, it is difficult to mix the aqueous liquid and the fine powder uniformly, and it is easy to form a large integrated gel-like object. In addition, if the mixing time is long, the water-soluble component of the obtained water-absorbent resin may increase, or the absorption rate under pressure may decrease, etc., thereby causing the performance of the water-absorbent resin to decrease.

[0220] Therefore, as a means to achieve high-speed mixing, it is preferred to put the raw materials into the mixing device in a short time. In the case of slowly adding the aqueous liquid by methods such as spraying or dripping, if the time of putting in any one or both raw materials increases, the mixing time will also increase, so that the micropowder may form a larger agglomerate, or the water-absorbent resin may be deteriorated due to long-term mixing. The micropowder and the aqueous liquid can be put into the mixing device at the same time, or one can be put in first and then the other at different times. Therefore, for the case of simultaneous input, the time from the start of the input of the two raw materials to the end of the input is preferably less than 60 seconds, more preferably less than 30 seconds, and further preferably less than 10 seconds. In addition, for the case of different input timings, the time from the start of the input of the raw material to the end of the input is preferably less than 60 seconds, more preferably less than 30 seconds, and further preferably less than 10 seconds.

[0221] In addition, in order to further achieve high-speed mixing, it is preferred to use a high-speed stirring paddle mixer. At this time, the number of revolutions of the stirring paddle is preferably more than 100 rpm, more preferably more than 200 rpm, and more preferably more than 300 rpm, and preferably less than 5000 rpm, more preferably less than 4000 rpm, and more preferably less than 3000 rpm. The direction of the rotating shaft of the stirring paddle is not limited, but from the viewpoint of easy discharge of the granulated gel, the vertical direction (plumb line direction) is preferred. In addition, the number of the rotating shafts of the stirring paddle is not limited, but from the viewpoint of easy maintenance, preferably 1 axis or 2 axes, more preferably 1 axis.

[0222] In the present invention, in order to prevent adhesion, the inner wall of the mixer is preferably made of a material having a contact angle with water of 90 degrees or more. A preferred material is a fluororesin such as Teflon (registered trademark). However, it is not necessary to use the above material for all inner walls. In order to obtain a larger stirring force, the inner wall near the stirring paddle can be made of a material having a contact angle with water of less than 90 degrees. From the viewpoint of durability, a preferred material is stainless steel.

[0223] (Conveying process)

[0224] The steps of producing the water-absorbent resin are preferably connected in series. The connection of the steps does not necessarily require a conveying step, but may include, for example, a step of conveying the granulated gel obtained in the granulation step to a predetermined adding position when the granulated gel is reused.

[0225] The granulated gel can be transported in a continuous manner or in a batch manner, preferably in a continuous manner. The conveyor used in the transporting step is, for example, a bucket conveyor, a belt conveyor, a screw conveyor, a chain conveyor, a vibrating conveyor, and a pneumatic conveyor, preferably a bucket conveyor. In addition, it is preferred that the granulated gel being transported is heated and / or kept warm from the outside of the conveyor, so that the temperature of the granulated gel is maintained at the high temperature even during the transport process. Such heating and / or keeping warm can be achieved by providing a means for heating the inner wall surface of the conveyor from the outside and / or a means for keeping warm. If the temperature of the granulated gel during the transport process is low, the granulated gel will adhere to each other and form a coagulation before mixing with the hydrogel, or the granulated gel will harden due to the temperature drop, which are causes of uneven drying in the drying step and easily produce undried products. Therefore, when transporting the granulated gel, it is preferred to maintain the temperature of the obtained granulated gel, and it is more preferred to heat and / or keep the temperature of the obtained granulated gel at the same level as the hydrogel to be mixed.

[0226] If there is no conveying step, the granulated gel is preferably dropped by gravity from the mixing device for mixing the fine powder and the aqueous liquid to the position to be mixed with the hydrogel. In this case, the distance from the mixing device to the position to be mixed with the hydrogel is preferably within 10 m, more preferably within 5 m, and even more preferably within 3 m. In addition, for the same reason as the conveyor, the pipe through which the granulated gel passes is preferably heated and / or kept warm.

[0227] If the granulated gel is retained for a long time in the device and piping in the heating and / or heat-retaining state, the surface of the granulated gel may dry and harden. Therefore, the granulated gel obtained in the granulation step is preferably mixed with the water-containing gel in a state heated to a specified temperature as soon as possible. Specifically, in the granulation step, the time from the start of mixing of the fine powder and the aqueous liquid to the addition of the obtained granulated gel to the water-containing gel in the re-addition step is preferably within 5 minutes, more preferably within 3 minutes, and further preferably within 1 minute. In addition, even if mixing with the water-containing gel cannot be achieved within the time, the granulated gel whose temperature has been lowered can be reheated to a state heated at a specified temperature, so that the cohesion can be reduced, thereby softening the granulated gel. Therefore, by reheating the granulated gel whose temperature has been lowered and then mixing it with the water-containing gel, a good mixing state can be obtained as in the case where mixing is achieved within the specified time.

[0228] In order to solve the problem of drying of the surface of the granulated gel, the dew point of the atmosphere in which the granulated gel is located in the process from the granulation step to the re-addition step, that is, in the conveying step before adding the granulated granulated gel to the water-containing gel, is preferably 50°C or more, more preferably 55°C or more, and further preferably 60°C or more, and is preferably 99°C or less, more preferably 95°C or less, and further preferably 90°C or less. In addition, in the present invention, it is preferred that the dew point of the atmosphere in the granulation step and / or the re-addition step is controlled within the above range in addition to controlling the dew point in the conveying step within the above range. Specifically, the atmosphere in the device when the fine powder and the aqueous liquid are mixed in the granulation step and the atmosphere in the device when the granulated gel is added to the water-containing gel are preferably controlled within the above range. The "dew point of the atmosphere" refers to the dew point of the air present in the atmosphere. For example, the dew point of the atmosphere can be adjusted to the above range by blowing water vapor or by controlling the circulation rate of hot air.

[0229] [2-9-2] Granulation gel addition step

[0230] This step is a step of adding granulated gel to the hydrogel in at least one step from the polymerization step to the drying step before the drying step is completed and / or between these steps. Specifically, it is preferred to add granulated gel to the hydrogel in at least one step selected from the following: in the polymerization step; after the polymerization step and before the gel crushing step; in the gel crushing step; after the gel crushing step and before the drying step; in the drying step. Here, since a hydrogel is also obtained in the polymerization step, the granulated gel can be added in the polymerization step. In addition, in the gel crushing step, the granulated gel can be added to the hydrogel and the gel can be supplied to the gel crusher. In the drying step, a polymer having a solid content of less than 80% by mass can generally be regarded as a hydrogel. That is, since a hydrogel still exists in the middle stage of the drying step, the granulated gel can be added in the drying step. Preferably, the granulated gel is added to the hydrogel after the gel pulverizing step and before the drying step, or during the drying step, and more preferably, the granulated gel is added to the hydrogel after the gel pulverizing step and before the drying step. When the granulated gel is added to the pulverized hydrogel in this way, the difference in particle size between the two is small, and the mixture is easily mixed, and uneven drying is less likely to occur. In particular, when a pulverizing treatment in which the gel pulverizing energy is controlled is performed, the hydrogel can be in a granulated shape, and thus uneven drying can be further suppressed. "Before the step" and "after the step" mean that all steps before the step or all steps after the step. That is, "including all steps before the step or all steps after the step" means that the granulated gel can be added to any step such as a conveying step and a storage step between the steps. For example, "after the gel pulverizing step" includes the intermediate process from the end of the gel pulverizing step to the conveying to the next step, as well as the next step.

[0231] In the granulated gel adding step, the solid content of the granulated gel is 50% by mass or more and 90% by mass or less. The solid content of the granulated gel will be described later.

[0232] (temperature)

[0233] In the present invention, the granulated gel is added to the hydrogel. At this time, the temperature of the granulated gel and the temperature of the hydrogel are both within the range of 50°C or higher and 100°C or lower, preferably 55°C or higher, more preferably 60°C or higher, and preferably 95°C or lower, more preferably 90°C or lower. Within such a temperature range, a good mixing state of the two can be achieved. If the temperature of the granulated gel and the hydrogel is lower than 50°C, the granulated gel may become hard as described above, or coagulation may be formed when the hydrogel and the granulated gel are mixed. That is, if coagulation is formed during mixing, the hydrogel and the granulated gel will further adhere to each other to form a huge coagulation, resulting in a poor mixing state. In addition, even if the mixing is completed, if coagulation exists during drying, poor drying is likely to occur, that is, undried products are likely to be formed. In addition, if the coagulation is continuously heated and dried until the desired water content is reached, the other granulated gel and the hydrogel that have been dried will become over-dried, resulting in thermal deterioration and increase of soluble components, thereby deteriorating the quality of the water-absorbent resin. This problem occurs even if the temperature of one gel is 50° C. or higher and the temperature of the other gel is lower than 50° C. On the contrary, if the temperature of the granulated gel and the water-containing gel exceeds 100° C., the gel surface may dry and the gel may become hard.

[0234] In the present invention, from the viewpoint of reducing uneven drying, the difference between the temperature of the granulated gel and the temperature of the water-containing gel within the above temperature range is preferably as small as possible, and the temperature difference between the two is preferably within 40° C., more preferably within 30° C., and further preferably within 20° C. The temperature of the granulated gel and the temperature of the water-containing gel can be appropriately adjusted by the following means: using a heating treatment and a heat-retaining treatment during the production process; or heating with hot air from the outside; or cooling by cooling, low-temperature air, etc.

[0235] [2-9-3] Gel mixing process

[0236] (Mechanical mixing)

[0237] In the present invention, by controlling the granulated gel and the hydrous gel within the above temperature range, the hydrous gel and the granulated gel can be loosened and slightly mixed with each other by slight impact and self-weight when the granulated gel is added to the hydrous gel. In a preferred embodiment of the present invention, the hydrous gel and the added granulated gel are mechanically mixed in at least one step in the process from the granulated gel addition step to the completion of drying in the drying step and / or between these steps. In the present invention, although the granulated gel is added to the hydrous gel before the completion of the drying step as described above, the granulated gel and the hydrous gel are dried in a mixed state regardless of the addition time. In addition, if the granulated gel and the hydrous gel are in a uniform state, the generation of undried matter can be further suppressed. Here, "uniformly present" means that the granulated gel and the hydrous gel are in a mixed state after stirring; or the granulated gel and the hydrous gel are evenly dispersed so that the ratio of the granulated gel and the hydrous gel per unit area is substantially the same. In order to achieve the effect of the present invention, the time from the addition of the granulated gel to the start of mechanical mixing is preferably within 5 minutes, more preferably within 2 minutes, and even more preferably within 1 minute. In addition, the time from the granulation step to the start of mechanical mixing is preferably within 10 minutes, more preferably within 5 minutes, and even more preferably within 2 minutes. At the time of starting mechanical mixing, the temperature of the aqueous gel to which the granulated gel is added is also required to be within the range of 50°C or more and 100°C or less, preferably 55°C or more, more preferably 60°C or more, and preferably 95°C or less, and even more preferably 90°C or less.

[0238] In the present invention, in order to make the granulated gel and the hydrogel be in a uniformly mixed state as much as possible, the granulated gel and / or the hydrogel are mechanically mixed. For the mechanical mixing, a device that can achieve any of the above-mentioned coexistence states can be used. As a stirring method, for example, rotary stirring by the rotation of a stirring blade and a container itself, stirring by a feeder that performs a oscillating motion, etc. can be cited. As an apparatus for implementing the stirring method, a rotary stirring device, a swing-head belt feeder, and a oscillating conveyor can be cited.

[0239] If mechanical mixing is performed in the polymerization step, the rotary stirring device is preferably a kneader-type polymerizer. If mechanical mixing is performed in the gel pulverization step, the rotary stirring device is preferably, for example, a kneader or a meat grinder.

[0240] If mechanical mixing is performed after the gel pulverizing step and before the drying step, or during the drying step, or before the drying is completed in the drying step, a swing-head type belt feeder or a rotary stirring device is preferably used. That is, it is preferred that the granulated gel and the water-containing gel are provided to a swing-head type belt feeder or a rotary stirring device for mixing. Specifically, by using a swing-head type belt feeder or a rotary stirring device to perform the mechanical mixing in the process from after the gel pulverizing step to before the drying step, or by using a rotary stirring device to perform the mechanical mixing in the drying step, it is possible to perform drying in a more homogeneous state, thereby being able to suppress the generation of uneven drying and undried matter.

[0241] When a swing-head type belt feeder is used, the granulated gel is added to the hydrous gel being transported on the conveyor belt by the swing-head type feeder, and the granulated gel can be evenly dispersed. Alternatively, the hydrous gel can be added to the granulated gel being transported on the conveyor belt by the swing-head type feeder, or the granulated gel and the hydrous gel can be supplied to the swing-head type feeder and then supplied to the conveyor belt by the swing-head type feeder. The end of the swing belt of the swing-head type belt feeder reciprocates relative to the conveyor belt, so that even if the distribution of the granulated gel and the hydrous gel in the swing-head type belt feeder is uneven, they can be distributed substantially evenly on the conveyor belt.

[0242] The head swing angle θ and belt speed of the swing-head feeder can be arbitrarily selected in consideration of the speed and supply amount of the conveyor belt. The conveyor belt stroke during one round trip is preferably within 1 m, more preferably within 0.5 m. If the conveyor belt stroke distance during one round trip is too long, the uneven distribution of the granulated gel will be more significant. The conveyor belt is preferably a conveyor belt of a ventilated belt dryer.

[0243] In addition, as a rotary stirring device, there can be exemplified a type in which the rotating shaft is in a horizontal direction and the container itself rotates, a type in which the rotating shaft is in a horizontal direction and the container itself is fixed, a type in which the rotating shaft is in a vertical direction and the container itself is fixed, and the like. These devices can be either continuous or batch type. In addition, a rotary disc leveler for the drying process can be used to level the water-containing gel stacked in the dryer while mixing. In addition, it is preferred to use a stirring dryer for the drying process to mix while drying. The stirring speed of the above-mentioned device is not particularly limited, and is preferably 50 rpm or more, more preferably 100 rpm or more, and preferably 500 rpm or less, and more preferably 300 rpm or less. In addition, the mixing (retention) time performed by the stirring device is preferably within 180 seconds, more preferably within 60 seconds, and further preferably within 30 seconds, and preferably 0.1 seconds or more, and more preferably 1 second or more.

[0244] (Solid content)

[0245] Regarding the conditions of the re-addition step (the step of adding the granulated gel to the hydrogel after granulation), it is further preferred in the present invention to appropriately control the solid content of the granulated gel and the solid content of the hydrogel. That is, if the solid content of the granulated gel and the hydrogel is too small (in other words, if the water content relative to 100% of the gel is too high), incomplete drying may occur locally or agglomerates may be easily formed. In the present invention, the solid content of the granulated gel and / or the solid content of the hydrogel is preferably within an appropriate range. The solid content of the hydrogel is preferably 30% by mass or more, more preferably 45% by mass or more, and is preferably 70% by mass or less, more preferably 55% by mass or less, and further preferably 50% by mass or less. The solid content of the granulated gel is preferably 50% by mass or more, more preferably 55% by mass or more, and further preferably 60% by mass or more, and is preferably 90% by mass or less, more preferably 85% by mass or less, and further preferably 80% by mass or less. Preferred conditions include that the temperature of the granulated gel and the water-containing gel is within the above range, and the solid content of these gels is within the above range. Other preferred conditions include that the solid content of the granulated gel in the re-addition step is within the above range, and the gel pulverization energy in the gel pulverization step is within the above range.

[0246] In addition, in the present invention, in consideration of further achieving uniform drying, it is preferred that the solid content of the granulated gel be higher than the solid content of the hydrogel when any of the above solid content is satisfied, and more preferably when both of the above solid content are satisfied. The higher the solid content of the granulated gel, the lower the drying burden. Specifically, the difference "A-B" between the solid content "A(%)" of the granulated gel and the solid content "B(%)" of the hydrogel is preferably 6 or more, more preferably 11 or more, and further preferably 16 or more, and is preferably 60 or less, more preferably 50 or less, and further preferably 40 or less. When the difference in the solid content of the two is within the above range, the drying burden is small, and uneven drying can be further suppressed, thereby avoiding manufacturing failures and quality problems.

[0247] In the present invention, the ratio between the granulated gel and the hydrogel can be appropriately determined according to the amount of the separated fine powder and the setting of the solid content of the granulated gel. From the viewpoint of the physical properties of the water-absorbent resin, the amount of the granulated gel added is usually 10 parts by mass or more, preferably 15 parts by mass or more, more preferably 20 parts by mass or more, and preferably 50 parts by mass or less, more preferably 40 parts by mass or less, and further preferably 30 parts by mass or less, relative to 100 parts by mass of the hydrogel (original form). When the ratio between the granulated gel and the hydrogel is within the above range, the swelling rate of the gel can be increased. According to the method of the present invention, even if the ratio of the granulated gel is 10 parts by mass or more, it is possible to suppress uneven drying. However, if the ratio of the granulated gel is too much, the final quality and physical properties of the water-absorbent resin as the final product may be greatly affected by the recycled fine powder, i.e., the granulated gel.

[0248] The water-containing gel to which the granulated gel is added is processed in the drying step. The drying conditions of the mixed gel are the same as those of the drying step, so the description thereof is omitted. In addition, the pulverization step and classification step performed after the drying step are also the same as those of the pulverization step and classification step, and the surface crosslinking step and granulation step can be performed as needed to obtain a water-absorbent resin as a product. In addition, the fine powder obtained in the classification step can also be processed in the recycling step.

[0249] [2-10] Other processes

[0250] In the present invention, in addition to the above-mentioned steps, at least one step selected from a transportation step, a storage step, a packaging step, a custody step, etc. may be included as necessary.

[0251] [3] Water-absorbent resin

[0252] By carrying out the above-mentioned various steps, the water-absorbent resin of the present invention can be obtained. That is, a water-absorbent resin having both a large gel expansion force under pressure and a large gel expansion rate under pressure can be obtained.

[0253] The gel expansion force of the water-absorbent resin of the present invention under a pressure of 4.83 kPa is preferably 26 N or more, more preferably 27 N or more, and further preferably 28 N or more. Therefore, when the water-absorbent resin of the present invention is used in an absorbent body having a low content ratio of a fiber material such as pulp, and the absorbent body is used in an absorbent article such as a thin diaper, the absorption rate under pressure for absorbing urination after the second time is higher than before. As described later, the "gel expansion force" specified in the present invention refers to the force of the water-absorbent resin to expand against a load after reaching a specified absorption rate. That is, the "gel expansion force" is used as an index to evaluate the ability of an absorbent article such as a thin diaper, which has swelled after absorbing the first urination, to absorb urine even under pressure when absorbing urination after the second time. If the gel swelling force is less than 26 N, the absorption capacity under pressure of the water-absorbent resin for absorbing the second and subsequent urinations will be insufficient, and the amount of liquid captured under pressure by the absorbent body containing the water-absorbent resin will be insufficient. Furthermore, the liquid capturing function of absorbent articles such as thin diapers containing the absorbent body will be insufficient, which is not preferred.

[0254] The upper limit of the gel expansion force of the water-absorbent resin of the present invention under a pressure of 4.83 kPa is not particularly limited, but is preferably 40N, and more preferably 35N.

[0255] As a method for evaluating the initial swelling power of a water-absorbent resin similar to the gel swelling power in the present invention, the International Publication WO2018 / 181548 and the like have proposed a method for evaluating the initial swelling power. 2 The force of an unswollen water-absorbent resin when it expands under very light pressure of 0.02 psi (0.01 psi). In addition, Japanese Patent No. 3210009 and the like propose a method for evaluating gel expansion pressure. In this method, the force of a water-absorbent resin when it further expands under no pressure is measured for a water-absorbent resin that has reached a specified absorption ratio under no pressure. In contrast, the gel expansion force in the present invention is measured for a water-absorbent resin under 4.83 kPa (49 g / cm 2 The water-absorbent resin that reaches the specified absorption rate under the pressure of 4.83 kPa (49 g / cm 2 ; 0.7psi) under pressure when further expanded, so the gel expansion force in the present invention is different from the function evaluated by the evaluation method of the aforementioned prior art literature.

[0256] That is, the evaluation of the gel expansion force in the present invention is an evaluation method performed for the following assumption: an absorbent article including the absorbent body or the water-absorbent resin is used, and the urination is performed under pressure, and multiple urinations are absorbed. Compared with the evaluation method proposed in the above-mentioned prior art documents, which is performed under very light pressure or no pressure, the evaluation of the gel expansion force in the present invention can be said to be an evaluation method performed in further consideration of the harsh environment when the absorbent article is actually used.

[0257] In addition, the present invention aims to provide an absorbent having an excellent amount of liquid captured under pressure for absorbing urine excreted after the second time, and a water-absorbent resin having an excellent absorption ratio under pressure for absorbing urine excreted after the second time. The evaluation method proposed in the above-mentioned prior art document is meaningless for predicting the absorption of urine excreted after the second time under pressure, and a method for evaluating the force of further expansion of the absorbent resin under pressure after swelling in one stage as described in the present invention is needed.

[0258] The gel expansion force under 4.83 kPa pressure can be controlled by adjusting the absorption ratio (CRC, AAP) of the water-absorbent resin, the particle shape (random particle shape with cavity and void), the particle size, etc. By adjusting these, the gel expansion force under 4.83 kPa pressure can be controlled to be 26N or more.

[0259] In addition to satisfying the aforementioned gel expansion force, the water-absorbent resin of the present invention preferably has a gel expansion rate of 8.5 or more, more preferably 9.0 or more, and even more preferably 9.5 or more under a pressure of 4.83 kPa. Thus, when the water-absorbent resin of the present invention is used in an absorbent body having a small content ratio of a fiber material such as pulp, and an absorbent article such as a thin diaper containing the absorbent body, the absorption capacity under pressure for absorbing urination after the second time can be further improved.

[0260] The upper limit of the gel expansion rate of the water-absorbent resin of the present invention under a pressure of 4.83 kPa is not particularly limited, but is preferably 15.0, more preferably 14.0.

[0261] Regarding conventional evaluation methods for water-absorbent resins, methods for evaluating absorption speed without or with pressure have been proposed, but these methods evaluate the absorption speed of the unswollen water-absorbent resin after it first comes into contact with an absorbent such as saline. In contrast, the evaluation method for the gel expansion rate of the present invention measures the speed of further expansion of the water-absorbent resin under pressure after it has reached a predetermined absorption ratio under pressure. Therefore, similar to the evaluation of the gel expansion force, it can be said that the gel expansion rate of the present invention is an evaluation method for the following hypothetical situation: the absorbent article is actually used and the absorbent article needs to absorb multiple urinations under pressure.

[0262] The volume occupancy rate of particles having a cavity volume rate of 15% or more in the total volume of the water-absorbent resin of the present invention is preferably 40% or more, more preferably 42% or more, and further preferably 44% or more. A water-absorbent resin having a larger cavity volume rate tends to have a larger specific surface area. The cavity volume rate evaluates the volume of the concave portion on the surface of the particle, but the volume of the concave portion cannot be fully evaluated by measuring the specific surface area alone. As the cavity volume rate increases, the gaps between the gel particles after the water-absorbent resin swells also increase, so the amount of aqueous liquid that can be retained by the cavity volume portion of the gel particles and the gaps between the gel particles increases. As a result, the gel expansion force is controlled. As a result, when the water-absorbent resin of the present invention is used for an absorbent having a small content ratio of fiber materials such as pulp, and an absorbent article such as a thin diaper containing the absorbent, the absorption rate under pressure for absorbing urination after the second time can be further improved.

[0263] Here, if Figure 1 As shown, the cavity referred to in the present invention refers to a cavity that is connected to the outside of the water-absorbent resin 1 (exposed to the surface of the water-absorbent resin 1) among the cavities formed in the water-absorbent resin 1. The cavity also includes depressions and grooves formed on the surface of the water-absorbent resin 1. Specifically, the cavity refers to a hole, a through hole, a depression, a groove, etc. existing on the surface of the water-absorbent resin 1 that can be confirmed by acquiring 3D image data using a microfocus X-ray CT system (inspeXio SMX-100CT; manufactured by Shimadzu Corporation) under the conditions described below and analyzing the 3D image data using a high-speed 3D analysis software (TRI / 3D-VOL-FCS64; manufactured by Ratoc System Engineering Co., Ltd.) under the conditions described below.

[0264] The volume occupancy rate of particles having a void volume ratio of 1% by volume or less in the total volume of the water-absorbent resin of the present invention is preferably 65% ​​by volume or more, more preferably 67% by volume or more, further preferably 70% by volume or more, further preferably 72% by volume or more, further preferably 73% by volume or more, as a result of which the gel expansion force is controlled. As a result, when the water-absorbent resin of the present invention is used in absorbent articles such as thin diapers, the absorption rate under pressure for absorbing urination after the second time can be further improved. After swelling, the water-absorbent resin having a large void volume ratio is easily crushed by pressure, so when it is used in an absorbent body having a small content ratio of fiber materials such as pulp, and an absorbent article such as a thin diaper containing the absorbent body, the absorption rate under pressure for absorbing urination after the second time is reduced.

[0265] Here, if Figure 1 As shown, the void referred to in the present invention refers to a void such as a closed bubble that is not communicated with the outside of the water-absorbent resin 1 (existing in the water-absorbent resin 1) among the cavities of the water-absorbent resin 1. Specifically, the void refers to a void such as a closed bubble existing in the water-absorbent resin 1 that can be confirmed by acquiring 3D image data using a microfocus X-ray CT system (inspeXio SMX-100CT; manufactured by Shimadzu Corporation) under the conditions described below and analyzing the 3D image data using high-speed 3D analysis software (TRI / 3D-VOL-FCS64; manufactured by Ratoc System Engineering Co., Ltd.) under the conditions described below.

[0266] The volume occupancy rate of particles having a cavity volume rate of 15 volume % or more and a cavity volume rate of 1 volume % or less in the total volume of the water-absorbent resin is preferably 20 volume % or more, more preferably 25 volume % or more. As a result, the gel swelling force is controlled. Thus, when the water-absorbent resin of the present invention is used in an absorbent body having a low content ratio of fiber materials such as pulp, and an absorbent article such as a thin diaper containing the absorbent body, the absorption capacity under pressure for absorbing urination after the second time can be further improved.

[0267] The water-absorbent resin of the present invention preferably has an absorption capacity under no pressure (CRC) of 25 g / g or more, more preferably 27 g / g or more, and even more preferably 28 g / g or more. As a result, the gel swelling force is controlled. Therefore, when the water-absorbent resin of the present invention is used in an absorbent body having a low content ratio of a fiber material such as pulp, and an absorbent article such as a thin diaper containing the absorbent body, the absorption capacity under pressure for absorbing urination after the second time can be further improved.

[0268] The upper limit of the absorption capacity without pressure (CRC) is not particularly limited, but in order to make the absorption capacity against pressure (AAP) and saline flow conductivity (SFC) reach the expected range, the absorption capacity without pressure (CRC) is preferably below 40 g / g, and more preferably below 38 g / g.

[0269] The absorbent resin of the present invention preferably has an absorption capacity under pressure (AAP) of 20 g / g or more, more preferably 23 g / g or more, further preferably 24 g / g or more, particularly preferably 24.5 g / g or more, and most preferably 25 g / g or more under a pressure of 4.83 kPa. As a result, the gel swelling force is controlled. Therefore, when the absorbent resin of the present invention is used in an absorbent body having a small content ratio of a fiber material such as pulp, and an absorbent article such as a thin diaper containing the absorbent body, the absorption capacity under pressure for absorbing the total amount of urine to be absorbed by the absorbent article such as the diaper can be further improved. Regarding the absorption capacity under pressure (AAP), the upper limit is not particularly limited, but it is preferably not more than the absorption capacity under no pressure (CRC) and is 35 g / g or less.

[0270] On the basis of satisfying the gel expansion force, it is also preferred that the saline flow conductivity (SFC) used to evaluate the liquid diffusivity of the water-absorbent resin of the present invention is 15 (×10 -7 cm 3 ·sec / g) or more, more preferably 18(×10 -7 cm 3 ·sec / g) or more, more preferably 20(×10 -7 cm 3 ·sec / g) or more, and preferably 55(×10 -7 cm 3 ·sec / g) or less, more preferably 53(×10 -7 cm 3 ·sec / g) or less. SFC is 15(×10 -7 cm 3 ·sec / g) and above and 55(×10 -7 cm 3 ·sec / g) or less, the water-absorbent resin of the present invention can bear the liquid diffusion capacity that pulp in the conventional absorbent has borne. Therefore, when the water-absorbent resin of the present invention is used in an absorbent having a small content ratio of fiber materials such as pulp, and an absorbent article such as a thin diaper containing the absorbent, the liquid diffusion capacity will not be reduced due to gel agglomeration, so that the absorbent and the absorbent articles such as diapers can show good performance.

[0271] The upper limit of the saline flow conductivity (SFC) is not particularly limited. However, the saline flow conductivity (SFC) and the absorption capacity under no pressure (CRC) are in a mutually balancing relationship, so if the saline flow conductivity (SFC) is too high, the absorption capacity under no pressure (CRC) within the expected range cannot be obtained.

[0272] The mass average particle size (D50) of the water-absorbent resin of the present invention is preferably 250 μm or more, more preferably 300 μm or more, and preferably 550 μm or less, more preferably 500 μm or less. In addition, the mass of the water-absorbent resin having a particle size of less than 150 μm in the total mass of the water-absorbent resin of the present invention preferably accounts for 3% by mass or less, more preferably 2% by mass or less. As a result, the gel swelling force is controlled, and the function of maintaining the balance (equilibrium) between the CRC, AAP, and SFC is exerted. Therefore, when the water-absorbent resin of the present invention is used for an absorbent having a low content ratio of fiber materials such as pulp, and an absorbent article such as a thin diaper containing the absorbent, the absorption rate under pressure for absorbing urination after the second time can be further improved.

[0273] The mass of the water-absorbent resin having a particle size of more than 710 μm preferably accounts for 2 mass % or less, and more preferably 1 mass % or less of the total mass of the water-absorbent resin of the present invention. Therefore, when the water-absorbent resin of the present invention is used in an absorbent having a low content ratio of a fiber material such as pulp, or in sanitary products such as thin diapers containing the absorbent, the roughness of the water-absorbent resin can be reduced, and the wearing feeling can be improved.

[0274] In order to control the gel swelling force, the absorption capacity (CRC, AAP), particle shape (random particle shape with recesses and cavities) and particle size of the water-absorbent resin can be adjusted. Preferably, the CRC, AAP, recess volume ratio, cavity volume ratio and particle size of the water-absorbent resin are adjusted, and more preferably, at least one (preferably two or more, more preferably three or more, particularly preferably four or more, and most preferably all) selected from the CRC, AAP, recess volume ratio, cavity volume ratio and particle size of the water-absorbent resin is adjusted to the above range.

[0275] In addition to satisfying the above-mentioned gel swelling force, the water-absorbent resin of the present invention preferably has a gel thickness of 5 mm reaching time of 150 seconds or less, more preferably 140 seconds or less. Thus, when the water-absorbent resin of the present invention is used in an absorbent body having a low content ratio of fiber materials such as pulp, and an absorbent article such as a thin diaper containing the absorbent body, the absorption capacity under pressure for absorbing urination after the second time can be further improved.

[0276] Furthermore, the water-absorbent resin of the present invention having at least the gel expansion force in the above range has an absorption capacity under pressure of 14 cm2 for the second urination.3 / g or more, preferably 14.2cm 3 / g or more, more preferably 14.4cm 3 / g or more, and more preferably 14.6cm 3 / g or above.

[0277] The WI value as the initial color tone of the water-absorbent resin of the present invention is preferably 45 or more, more preferably 50 or more, and still more preferably 52 or more. Therefore, when the water-absorbent resin of the present invention is used in an absorbent having a low content ratio of a fiber material such as pulp and the absorbent is used in the upper layer of an absorbent article such as a thin diaper, the absorbent article can maintain a clean white state, which is preferred.

[0278] [4] Application of water-absorbent resin (absorbent)

[0279] The use of the water-absorbent resin of the present invention is not particularly limited, but is preferably used in absorbent bodies of absorbent articles such as diapers, and more preferably in absorbent bodies having a large water-absorbent resin mass ratio used in absorbent articles such as thin diapers.

[0280] Regarding the structure of the absorbent, in addition to the absorbent resin, it generally also contains fiber materials such as wood crushed pulp (hydrophilic fibers). If the absorbent contains a water-absorbent resin and hydrophilic fibers, the structure of the absorbent can be, for example, an absorbent containing a mixture of water-absorbent resin and hydrophilic fibers uniformly mixed. Specifically, examples include: a structure formed by simply mixing water-absorbent resin and hydrophilic fibers uniformly; a structure formed by stacking layered hydrophilic fibers on a layer formed by uniformly mixing water-absorbent resin and hydrophilic fibers; a structure formed by arranging a water-absorbent resin between a layer formed by uniformly mixing water-absorbent resin and hydrophilic fibers and layered hydrophilic fibers; etc. In addition, it can also be a structure formed by arranging a water-absorbent resin between layered hydrophilic fibers. However, the structure of the absorbent is not limited to the above-mentioned structures.

[0281] Examples of the hydrophilic fibers include, in addition to the aforementioned wood crushed pulp (mechanical pulp obtained from wood), chemical pulp, semi-chemical pulp, dissolving pulp and other cellulose fibers; rayon, acetate and other artificial cellulose fibers and other hydrophilic fibers. Among the hydrophilic fibers exemplified above, cellulose fibers are preferred. In addition, the hydrophilic fibers may also contain synthetic fibers such as polyamide, polyester, and polyolefin. The hydrophilic fibers are not limited to the fibers exemplified above.

[0282] In addition, the mass ratio of the water-absorbent resin in the mass of the absorbent body is preferably 75% to 100% by mass, more preferably 80% to 100% by mass, further preferably 85% to 100% by mass, and particularly preferably 90% to 100% by mass. When the mass ratio of the water-absorbent resin in the mass of the absorbent body is within the above range, thinning, which is a trend in recent years for absorbent articles, can be achieved, and thus it is preferred. In addition, when the mass ratio of the water-absorbent resin in the mass of the absorbent body is within the above range, when the absorbent body is used in the upper layer of an absorbent article, the absorbent article can maintain a clean white state, and thus it is preferred.

[0283] In addition, in order to improve the strength and shape retention of the absorbent before and during use, an adhesive adhesive may be used. As the adhesive adhesive, heat-melting fibers such as polyolefin fibers such as polyethylene, polypropylene, ethylene-propylene copolymer, 1-butene-ethylene copolymer, and adhesive emulsions may be exemplified. These adhesive adhesives may be used alone or in combination of two or more. The mass ratio between the water-absorbent resin and the adhesive adhesive is preferably in the range of 50 / 50 to 99 / 1, more preferably in the range of 70 / 30 to 95 / 5, and further preferably in the range of 80 / 20 to 95 / 5.

[0284] In addition, other structures of the absorbent body may be, for example, a structure in which a layer containing the aforementioned absorbent resin and hydrophilic fibers is sandwiched by non-woven fabrics from above and / or below, wherein the layer containing the aforementioned absorbent resin and hydrophilic fibers includes: a layer formed by uniformly mixing the absorbent resin and the hydrophilic fibers; a structure formed by stacking layered hydrophilic fibers on a layer in which the absorbent resin and the hydrophilic fibers are uniformly mixed; a structure formed by arranging an absorbent resin between a layer in which the absorbent resin and the hydrophilic fibers are uniformly mixed and the layered hydrophilic fibers; a structure formed by arranging the absorbent resin between layered hydrophilic fibers; and the like. The nonwoven fabric can be any nonwoven fabric known in the technical field, and is not particularly limited. Examples include polyolefin fibers such as polyethylene (PE) and polypropylene (PP); polyester fibers such as polyethylene terephthalate (PET), polypropylene terephthalate (PTT), and polyethylene naphthalate (PEN); polyamide fibers such as nylon; rayon fibers; nonwoven fabrics made of other synthetic fibers, and nonwoven fabrics made by mixing cotton, silk, linen, and pulp (cellulose) fibers. The mass per unit area of ​​the nonwoven fabric can be 5 to 300 g / m 2 In addition, the thickness of the nonwoven fabric may be 20 to 800 μm. The liquid diffusion area of ​​the nonwoven fabric described below may be 1 to 100 m 2 .

[0285] The shape of the absorbent body is not particularly limited, but is preferably formed into a sheet shape, a fiber shape, a tube shape, or the like, and more preferably formed into a sheet shape.

[0286] Furthermore, the absorbent of the present invention must have a gel expansion force of 26 N or more under a pressure of 4.83 kPa, and preferably has an absorption ratio under pressure of 14 cm for absorbing the second and subsequent urination. 3 / g or more, and more preferably, it further contains an absorbent resin that satisfies the various physical properties described in the aforementioned "[3] Absorbent resin" column. As a result, the amount of liquid captured under pressure by the absorbent of the present invention for urination after the second time can be improved. The amount of liquid captured under pressure for urination after the second time is preferably 34.5g or more, more preferably 35.0g or more, and even more preferably 35.5g or more. In addition, the total amount of liquid captured under pressure for urination after the first and second times is preferably 72.0g or more, more preferably 72.5g or more, and even more preferably 73.0g or more. As a result, when the absorbent of the present invention is used in absorbent articles such as thin diapers, the absorption ratio under pressure of the absorbent for urination after the second time can be improved, and the liquid capture function of the absorbent article for urination after the second time can be improved.

[0287] Regarding the uses of the water-absorbent resin of the present invention, in addition to being used in the absorbent contained in the absorbent articles such as the sanitary articles, it can also be preferably used in various uses such as pet urine absorbents, urine gelling agents for portable toilets, preservatives for fruits and vegetables, leaking absorbents for meat and seafood, cold preservation agents, disposable hand warmers, gelling agents for batteries, soil water-retaining agents for agriculture and horticulture (plants and soil, etc.), anti-condensation agents, industrial waterproofing agents and bag filling agents, and artificial snow.

[0288] [5] Use of absorbent body (absorbent articles)

[0289] The use of the absorbent body of the present invention is not particularly limited, but is preferably used in absorbent articles such as diapers, and more preferably used in absorbent articles such as thin diapers.

[0290] If the absorbent article is, for example, a diaper, the diaper can be made in the following manner: an absorbent layer containing the absorbent body of the present invention is sandwiched between a liquid-permeable front gasket located on the side in contact with human skin when worn and a liquid-impermeable back gasket located on the outside when worn. The liquid-permeable front gasket (hereinafter referred to as the liquid-permeable gasket) is made of a material having an aqueous liquid-permeable property. Examples of materials for the liquid-permeable gasket include nonwoven fabrics; fabrics; porous synthetic resin films composed of polyethylene, polypropylene, polyester, polyamide, etc. The liquid-impermeable back gasket (hereinafter referred to as the liquid-impermeable gasket) is made of a material having an aqueous liquid-impermeable property. Examples of materials for the liquid-impermeable gasket include synthetic resin films composed of polyethylene, polypropylene, ethylene vinyl acetate, polyvinyl chloride, etc.; composite material films composed of these synthetic resins and nonwoven fabrics; composite material films composed of the synthetic resin and fabrics, etc. The liquid-impermeable gasket may also have a vapor-permeable property. In addition, in absorbent articles such as diapers, a diffusion layer composed of nonwoven fabric, cellulose, cross-linked cellulose, etc. for assisting liquid diffusion may be provided between the liquid permeable pad and the absorbent layer. In addition, absorbent articles such as diapers may be further provided with a tape or the like for fixing the diaper after wearing, which is well known to those skilled in the art.

[0291] The absorbent layer contains an absorbent, but is not particularly limited thereto. For example, deodorants, antibacterial agents, fragrances, various inorganic powders, foaming agents, pigments, dyes, hydrophilic short fibers, fertilizers, oxidants, reducing agents, water, salts, etc. may be added to the absorbent layer to impart various functions to the absorbent or absorbent article. In addition, a solution in which the absorbent layer does not contain the aforementioned additives (a solution in which the absorbent layer contains only the absorbent) may also be adopted.

[0292] The method for producing the absorbent layer is not particularly limited. The method for sandwiching the absorbent layer between the liquid-permeable sheet and the liquid-impermeable sheet, that is, the method for producing the absorbent article is not particularly limited.

[0293] Furthermore, the absorbent article of the present invention has an absorbent body having an improved liquid-capturing capacity under pressure for absorbing the second and subsequent urinations, and therefore the absorbent article exhibits an excellent liquid-capturing function for the second and subsequent urinations.

[0294] Regarding the uses of the absorbent body of the present invention, in addition to being used in the above-mentioned absorbent articles, it can also be preferably used for various purposes such as pet urine absorbent, urine gelling agent for portable toilets, preservatives for fruits and vegetables, leakage absorbent for meat and seafood, cold preservation agent, disposable hand warmer, gelling agent for battery, soil water retention agent for agriculture and horticulture (plants and soil, etc.), anti-condensation agent, industrial water-stopping agent and bag filling agent, and artificial snow.

[0295] (Example)

[0296] Hereinafter, the present invention will be described in further detail with reference to Examples and Comparative Examples, but the present invention is not limited to these Examples.

[0297] [Example 1]

[0298] (Step of Preparing Monomer Aqueous Solution)

[0299] Into a 2L polypropylene container, 422.0 parts by mass of acrylic acid, 173.9 parts by mass of a 48.5% by mass sodium hydroxide aqueous solution, 2.5 parts by mass of polyethylene glycol diacrylate (average molecular weight: 523), 2.6 parts by mass of a 1.0% by mass diethylenetriamine pentaacetic acid trisodium aqueous solution, and 403.3 parts by mass of deionized water were added and mixed to prepare a monomer aqueous solution. Due to the neutralization heat and dissolution heat generated during the mixing process, the liquid temperature of the monomer aqueous solution exceeded 40°C.

[0300] (Polymerization process)

[0301] Next, the monomer aqueous solution was cooled while stirring, and when the liquid temperature reached 40°C, 178.7 parts by mass of a 48.5% by mass sodium hydroxide aqueous solution adjusted to 40°C was added to the monomer aqueous solution in an open state to the atmosphere for about 20 seconds, and mixed (starting the second stage of neutralization). Thus, a monomer aqueous solution (1) was prepared. However, due to the neutralization heat and dissolution heat generated during the mixing process, the liquid temperature of the monomer aqueous solution (1) rose to about 78°C. In addition, a precipitate was observed at first when the monomer aqueous solution and the sodium hydroxide aqueous solution were mixed, but it gradually dissolved thereafter, and the prepared monomer aqueous solution (1) became a transparent uniform solution.

[0302] Then, nitrogen gas was introduced into the monomer aqueous solution (1) under stirring at a pressure of 0.1 MPa and a flow rate of 0.1 L / min for 5 seconds using a Kinoshita glass ball filter (filter particles No. 4; manufactured by Kinoshita Rika Kogyo Co., Ltd.). Next, 18.4 parts by mass of a 4.5% by mass sodium persulfate aqueous solution was added to the monomer aqueous solution (1). Then, the monomer aqueous solution (1) was immediately poured into a stainless steel cylinder-type container (bottom surface 340×340 mm, height 25 mm, inner surface Teflon (registered trademark) coating) in an atmosphere-open state. The time from the start of the second stage neutralization to the pouring of the monomer aqueous solution (1) into the cylinder-type container was 65 seconds. In addition, the cylinder-type container was heated with a hot plate (NEO HOTPLATE HI-1000; manufactured by Inouchi Seieido Co., Ltd.) to a surface temperature of 50°C.

[0303] After the monomer aqueous solution (1) is poured into the cylinder-shaped container, the polymerization reaction starts within 1 minute. During the polymerization reaction, water vapor is generated while expanding and bubbling in all directions, so that the monomer aqueous solution (1) is continuously polymerized. Thereafter, the obtained polymer shrinks to a size slightly larger than the bottom surface of the cylinder-shaped container. Two minutes after the polymerization reaction starts, the water-containing gel (1) is taken out of the cylinder-shaped container. This series of operations is performed in an open state to the atmosphere.

[0304] (Gel crushing process)

[0305] Next, the hydrogel (1) obtained in the polymerization reaction was cut into small pieces each weighing about 60 g, and then the gel was crushed using a meat grinder (HL-G22SN; die hole diameter 6.0 mm; manufactured by REMACOM Co., Ltd.) to obtain a granular hydrogel (1). The amount of the hydrogel (1) fed was about 360 g / min, and in parallel with the feeding of the hydrogel (1), deionized water adjusted to 90° C. was added to the meat grinder at an addition rate of 25 g / min while the gel was crushed.

[0306] The D50 (mass average particle size) of the granular aqueous gel (1) was 320 μm, and the σζ (logarithmic standard deviation of particle size distribution) was 0.91.

[0307] (Drying process)

[0308] Next, the granular hydrogel (1) was spread on a metal net with a mesh size of 300 μm and placed in a hot air dryer. Then, hot air at 190° C. was blown for 30 minutes to dry the granular hydrogel (1) to obtain a dried polymer (1). The dried polymer (1) did not contain any undried matter.

[0309] (Grading process)

[0310] Next, the dried polymer (1) was put into a roll mill (WML type roll mill; manufactured by Inoguchi Giken Co., Ltd.) and pulverized, and then classified using two types of JIS standard sieves with mesh sizes of 710 μm and 150 μm. This operation obtained a water-absorbent resin (1) before surface cross-linking in a randomly crushed state that passed through the sieve with a mesh size of 710 μm and remained on the sieve with a mesh size of 150 μm.

[0311] (Surface cross-linking process)

[0312] Next, a surface crosslinking agent aqueous solution consisting of 0.4 parts by mass of ethylene carbonate, 0.7 parts by mass of propylene glycol, 2.9 parts by mass of deionized water, and 0.001 parts by mass of polyoxyethylene (20) sorbitan monostearate (manufactured by Kao Corporation) was sprayed and uniformly mixed with respect to 100 parts by mass of the water-absorbent resin (1) before surface crosslinking. Then, the obtained mixture was heat-treated at 200° C. for 40 minutes to perform surface crosslinking. Next, the mixture was classified using two types of JIS standard sieves with mesh sizes of 710 μm and 150 μm. By this operation, a surface crosslinked water-absorbent resin (1) that passed through a sieve with a mesh size of 710 μm and remained on a sieve with a mesh size of 150 μm was obtained. The physical properties of the surface crosslinked water-absorbent resin (1) are shown in Table 2. The WI value, which is the initial color tone of the water-absorbent resin (1), is 52.4.

[0313] [Example 2]

[0314] The same operation as in Example 1 was carried out except that the surface crosslinking agent aqueous solution used in Example 1 was changed to a surface crosslinking agent aqueous solution composed of 0.2 parts by mass of 1,6-hexanediol, 0.6 parts by mass of triethylene glycol, 2.6 parts by mass of deionized water, and 0.001 parts by mass of polyoxyethylene (20) sorbitan monostearate (produced by Kao Corporation), thereby obtaining a surface crosslinked water-absorbent resin (2). The physical properties of the surface crosslinked water-absorbent resin (2) are shown in Table 2.

[0315] The WI value, which is the initial color tone of the water-absorbent resin (2), was 53.0.

[0316] The granular hydrogel (2) obtained through the gel pulverization step had a D50 (mass average particle size) of 330 μm and a σζ (logarithmic standard deviation of particle size distribution) of 0.92.

[0317] [Example 3]

[0318] The same operation as in Example 1 was carried out except that the amount of deionized water added in the gel pulverization step in Example 1 was changed to 50 g / min, thereby obtaining a particulate hydrogel (3).

[0319] The D50 (mass average particle size) of the granular aqueous gel (3) was 400 μm, and σζ (logarithmic standard deviation of particle size distribution) was 0.95.

[0320] (Drying process)

[0321] Next, the granular hydrogel (3) was spread on a metal net with a mesh size of 300 μm and placed in a hot air dryer. Then, hot air at 190° C. was blown for 30 minutes to dry the granular hydrogel (3) to obtain a dried polymer (3). The dried polymer (3) did not contain any undried matter.

[0322] (Grading process)

[0323] Next, the dried polymer (3) was put into a roll mill (WML type roll mill; manufactured by Inoguchi Giken Co., Ltd.) and pulverized, and then classified using two types of JIS standard sieves with mesh sizes of 710 μm and 150 μm. This operation provided a water-absorbent resin (3) before surface crosslinking in a randomly crushed state that passed through the sieve with a mesh size of 710 μm and remained on the sieve with a mesh size of 150 μm, and a fine powder (3-1) that passed through the sieve with a mesh size of 150 μm.

[0324] (Surface cross-linking process)

[0325] Next, a surface crosslinking agent aqueous solution consisting of 0.4 parts by mass of ethylene carbonate, 0.7 parts by mass of propylene glycol, 2.9 parts by mass of deionized water, and 0.001 parts by mass of polyoxyethylene (20) sorbitan monostearate (manufactured by Kao Corporation) was sprayed and uniformly mixed with respect to 100 parts by mass of the water-absorbent resin (3) before surface crosslinking. Then, the obtained mixture was heated at 200° C. for 40 minutes to perform surface crosslinking. Next, the mixture was classified using two types of JIS standard sieves with mesh sizes of 710 μm and 150 μm. By this operation, a surface crosslinked water-absorbent resin (3) that passed through a sieve with a mesh size of 710 μm and remained on a sieve with a mesh size of 150 μm and a fine powder (3-2) that passed through a sieve with a mesh size of 150 μm were obtained.

[0326] (Granulation process)

[0327] Next, the fine powder (3-1) and the fine powder (3-2) were mixed at a mass ratio of 17:3 (w:w) to obtain a fine powder (3-3). The D50 (mass average particle size) of the fine powder (3-3) was 85 μm. Next, 60 parts by mass of the fine powder (3-3) were heated to 70°C, put into a food grinder (MK-K48P / Panasonic), and while stirring, 49 parts by mass of deionized water adjusted to 80°C was added and mixed for 30 seconds to obtain a granulated gel (3-3).

[0328] (Granulation gel adding process)

[0329] Next, after 1 minute from the start of the above-mentioned granulation, 80 parts by mass of the granulated gel (3-3) were added to 320 parts by mass of the granulated water-containing gel (3) obtained by repeating the above-mentioned operation. Immediately thereafter, the mixture was mixed for 10 seconds using a mortar stirrer (manufactured by West Japan Testing Equipment Co., Ltd.) preheated to 80°C, thereby obtaining a mixed gel (3-4). The temperatures of the granulated gel (3-3) and the granulated water-containing gel (3) immediately before mixing using the mortar stirrer were 55°C and 50°C, respectively. In addition, the granulated gel (3-3) and the granulated water-containing gel (3) had good miscibility when mixed using the mortar stirrer.

[0330] (Drying process)

[0331] Next, the mixed gel (3-4) was spread on a metal net with a mesh size of 300 μm and placed in a hot air dryer. Then, hot air at 190° C. was blown for 30 minutes to dry the mixed gel (3-4) to obtain a dried polymer (3-4). The dried polymer (3-4) did not contain undried matter.

[0332] (Grading process)

[0333] Next, the dried polymer (3-4) was put into a roll mill (WML type roll mill; manufactured by Inoguchi Giken Co., Ltd.) and pulverized, and then classified using two types of JIS standard sieves with mesh sizes of 710 μm and 150 μm. This operation obtained a water-absorbent resin (3-4) before surface cross-linking in a randomly crushed state that passed through the sieve with a mesh size of 710 μm and remained on the sieve with a mesh size of 150 μm.

[0334] (Surface cross-linking process)

[0335] Next, a surface crosslinking agent aqueous solution consisting of 0.4 parts by mass of ethylene carbonate, 0.7 parts by mass of propylene glycol, 2.9 parts by mass of deionized water, and 0.001 parts by mass of polyoxyethylene (20) sorbitan monostearate (manufactured by Kao Corporation) was sprayed and uniformly mixed with respect to 100 parts by mass of the water-absorbent resin (3-4) before surface crosslinking. Then, the obtained mixture was heat-treated at 200° C. for 40 minutes to perform surface crosslinking. Next, the mixture was classified using two types of JIS standard sieves with mesh sizes of 710 μm and 150 μm. By this operation, a surface crosslinked water-absorbent resin (3-4) was obtained that passed through a sieve with a mesh size of 710 μm and remained on a sieve with a mesh size of 150 μm. The various physical properties of the surface crosslinked water-absorbent resin (3-4) are shown in Table 2.

[0336] The WI value as the initial color tone of the water-absorbent resin (3-4) was 54.7.

[0337] [Example 4]

[0338] The same operation as in Example 3 was performed except that the surface crosslinking agent aqueous solution used in Example 3 was changed to a surface crosslinking agent aqueous solution composed of 0.2 parts by mass of 1,6-hexanediol, 0.6 parts by mass of triethylene glycol, 2.6 parts by mass of deionized water, and 0.001 parts by mass of polyoxyethylene (20) sorbitan monostearate (produced by Kao Corporation), thereby obtaining a surface crosslinked water-absorbent resin (4-4). The physical properties of the surface crosslinked water-absorbent resin (4-4) are shown in Table 2.

[0339] The WI value as the initial color tone of the water-absorbent resin (4-4) was 52.6.

[0340] The granular hydrogel (4) obtained through the gel pulverization step had a D50 (mass average particle size) of 410 μm and a σζ (logarithmic standard deviation of particle size distribution) of 0.94.

[0341] [Comparative Example 1]

[0342] (Step of Preparing Monomer Aqueous Solution)

[0343] Into a 2 L polypropylene container, 421.7 parts by mass of acrylic acid, 140.4 parts by mass of a 48.5% by mass sodium hydroxide aqueous solution, 2.4 parts by mass of polyethylene glycol diacrylate (average molecular weight: 523), 11.3 parts by mass of a 1.0% by mass diethylenetriamine pentaacetic acid trisodium aqueous solution, and 390.3 parts by mass of deionized water were added and mixed to prepare a monomer aqueous solution. Due to the neutralization heat and dissolution heat generated during the mixing process, the liquid temperature of the monomer aqueous solution exceeded 40°C.

[0344] (Polymerization process)

[0345] Next, the monomer aqueous solution was cooled while stirring, and when the liquid temperature reached 38.3°C, 4.4 parts by mass of a 1.0% by mass polyoxyethylene (20) sorbitan monostearate (manufactured by Kao Corporation) aqueous solution was added. Furthermore, when the liquid temperature reached 38.0°C, 211.9 parts by mass of a 48.5% by mass sodium hydroxide aqueous solution adjusted to 40°C was added to the monomer aqueous solution in an open state for about 20 seconds, and mixed (starting the second stage of neutralization). Thus, a monomer aqueous solution (1') was prepared. However, due to the neutralization heat and dissolution heat generated during the mixing process, the liquid temperature of the monomer aqueous solution (1') rose to about 81°C. In addition, when the mixing of the monomer aqueous solution and the sodium hydroxide aqueous solution was started, a precipitate was observed at first, but then gradually dissolved, and the prepared monomer aqueous solution (1') became a transparent uniform solution.

[0346] Then, nitrogen gas was introduced into the monomer aqueous solution (1') under stirring at a pressure of 0.1 MPa and a flow rate of 0.1 L / min for 10 seconds using a Kinoshita glass ball filter (filter particles No. 4; manufactured by Kinoshita Rika Industry Co., Ltd.). Next, 17.6 parts by mass of a 4.0% by mass sodium persulfate aqueous solution was added to the monomer aqueous solution (1'). Then, the monomer aqueous solution (1') was immediately poured into a stainless steel cylinder container (bottom surface 340×340 mm, height 25 mm, inner surface Teflon (registered trademark) coating) in an atmosphere-open state. The time from the start of the second stage neutralization to the pouring of the monomer aqueous solution (1') into the cylinder container was 55 seconds. In addition, the cylinder container was heated with a hot plate (NEOHOTPLATE HI-1000; manufactured by Inouchi Seieido Co., Ltd.) to a surface temperature of 40°C.

[0347] After the monomer aqueous solution (1') was poured into the cylinder-shaped container, the polymerization reaction started 59 seconds later. During the polymerization reaction, water vapor was generated while expanding and bubbling in all directions, so that the monomer aqueous solution (1') was continuously polymerized. Thereafter, the obtained polymer shrank to a size slightly larger than the bottom surface of the cylinder-shaped container. Three minutes after the polymerization reaction started, the water-containing gel (1') was taken out of the cylinder-shaped container. Among them, this series of operations were carried out in an open state to the atmosphere.

[0348] (Gel crushing process)

[0349] Next, the hydrogel (1') obtained in the polymerization reaction was cut into small pieces each weighing about 60 g, and then the gel was crushed using a meat grinder (HL-G22SN; die diameter 6.0 mm; manufactured by REMACOM Co., Ltd.) to obtain a granular hydrogel (1'). The amount of the hydrogel (1') fed was about 230 g / min, and in parallel with the feeding of the hydrogel (1'), deionized water adjusted to 90°C was added to the meat grinder at an addition amount of 50 g / min while the gel was crushed.

[0350] The granular aqueous gel (1') had a D50 (mass average particle size) of 350 μm and a σζ (logarithmic standard deviation of particle size distribution) of 0.93.

[0351] (Drying process)

[0352] Next, the granular hydrogel (1') was spread on a metal net with a mesh size of 300 μm and placed in a hot air dryer. Then, hot air at 180°C was blown for 30 minutes to dry the granular hydrogel (1') to obtain a dry polymer (1'). The dry polymer (1') did not contain any undried matter.

[0353] (Grading process)

[0354] Next, the dried polymer (1') was put into a roll mill (WML type roll mill; manufactured by Inoguchi Giken Co., Ltd.) and pulverized, and then classified using two types of JIS standard sieves with mesh sizes of 710 μm and 45 μm. This operation obtained a surface-crosslinked water-absorbent resin (1') in a random crushed state that passed through the sieve with a mesh size of 710 μm and remained on the sieve with a mesh size of 45 μm.

[0355] (Surface cross-linking process)

[0356] Next, with respect to 100 parts by mass of the water-absorbent resin (1') before surface crosslinking, a surface crosslinking agent aqueous solution consisting of 0.3 parts by mass of ethylene carbonate, 0.6 parts by mass of propylene glycol, 3.0 parts by mass of deionized water, and 0.001 parts by mass of polyoxyethylene (20) sorbitan monostearate (manufactured by Kao Corporation) was sprayed and uniformly mixed. Then, the obtained mixture was heat-treated at 208°C for 40 minutes to perform surface crosslinking. Next, the mixture was classified using two JIS standard sieves with mesh sizes of 710 μm and 45 μm. By this operation, a water-absorbent resin (1') after surface crosslinking that passed through a sieve with a mesh size of 710 μm and remained on a sieve with a mesh size of 45 μm was obtained. The various physical properties of the water-absorbent resin (1') after surface crosslinking are shown in Table 2.

[0357] [Comparative Example 2]

[0358] (Step of Preparing Monomer Aqueous Solution)

[0359] Into a 2 L polypropylene container, 404.7 parts by mass of acrylic acid, 344.6 parts by mass of a 48.5% by mass sodium hydroxide aqueous solution, 2.2 parts by mass of polyethylene glycol diacrylate (average molecular weight: 523), and 405.6 parts by mass of deionized water were added and mixed to prepare a monomer aqueous solution (2'). Due to the neutralization heat and dissolution heat generated during the mixing process, the liquid temperature of the monomer aqueous solution (2') exceeded 90°C.

[0360] (Polymerization process)

[0361] Next, the monomer aqueous solution (2') was kept at a temperature of 90°C, and 22.2 parts by mass of a 3.2% by mass sodium persulfate aqueous solution was added while stirring. Then, the monomer aqueous solution (2') was immediately poured into a stainless steel cylinder-shaped container (bottom surface 340×340 mm, height 25 mm, inner surface Teflon (registered trademark) coating) in an open state. The cylinder-shaped container was heated with a heating plate (NEO HOTPLATE HI-1000; manufactured by Inouchi Seieido Co., Ltd.) to a surface temperature of 50°C.

[0362] After the monomer aqueous solution (2') is poured into the cylinder-shaped container, the polymerization reaction starts immediately. During the polymerization reaction, water vapor is generated while expanding and bubbling in all directions, so that the monomer aqueous solution (2') is continuously polymerized. Thereafter, the obtained polymer shrinks to a size slightly larger than the bottom surface of the cylinder-shaped container. Three minutes after the polymerization reaction starts, the water-containing gel (2') is taken out of the cylinder-shaped container. Among them, this series of operations are carried out in an open state to the atmosphere.

[0363] (Gel crushing process)

[0364] Next, the hydrogel (2') obtained in the polymerization reaction was cut into small pieces each weighing about 60 g, and then the gel was crushed using a meat grinder (HL-G22SN; die diameter 8.0 mm; manufactured by REMACOM Co., Ltd.) to obtain a granular hydrogel (2'). The amount of the hydrogel (2') fed was about 360 g / min, and in parallel with the feeding of the hydrogel (2'), deionized water adjusted to 80°C was added to the meat grinder at an addition amount of 50 g / min while the gel was crushed.

[0365] Then, the obtained granular hydrogel (2') was immediately pulverized again using a meat grinder (HL-G22SN; die diameter 8.0 mm; manufactured by REMACOM Co., Ltd.) to obtain a granular hydrogel (2'). When the granular hydrogel (2') was pulverized again, deionized water was not added to the meat grinder.

[0366] The granular aqueous gel (2') had a D50 (mass average particle size) of 400 μm and a σζ (logarithmic standard deviation of particle size distribution) of 0.97.

[0367] (Drying process)

[0368] Next, the granular hydrogel (2') was spread on a metal net with a mesh size of 300 μm and placed in a hot air dryer. Then, hot air at 190°C was blown for 20 minutes to dry the granular hydrogel (2') to obtain a dry polymer (2'). The dry polymer (2') did not contain any undried matter.

[0369] (Grading process)

[0370] Next, the dry polymer (2') was put into a roller mill (WML roller mill; manufactured by Inoguchi Giken Co., Ltd.) for pulverization, and then classified using two types of JIS standard sieves with mesh sizes of 850 μm and 150 μm. The agglomerated dry polymer remaining on the sieve with a mesh size of 850 μm was repeatedly pulverized and classified until the entire amount of the polymer passed through the sieve with a mesh size of 850 μm. This operation provided a water-absorbent resin (2') before surface cross-linking that passed through the sieve with a mesh size of 850 μm and remained on the sieve with a mesh size of 150 μm, and a fine powder (2'-1) that passed through the sieve with a mesh size of 150 μm.

[0371] (Surface cross-linking process)

[0372] Next, a surface crosslinking agent aqueous solution consisting of 0.3 parts by mass of ethylene carbonate, 0.5 parts by mass of propylene glycol, and 2.7 parts by mass of deionized water was sprayed and uniformly mixed with respect to 100 parts by mass of the water-absorbent resin (2') before surface crosslinking. Then, the obtained mixture was heat-treated at 200°C for 40 minutes to perform surface crosslinking. Next, the mixture was classified using two JIS standard sieves with mesh sizes of 850 μm and 150 μm. As for the agglomerate-like mixture remaining on the sieve with a mesh size of 850 μm, the agglomerate was repeatedly crushed and classified until the entire amount could be sieved through the sieve with a mesh size of 850 μm. Through this operation, a surface crosslinked water-absorbent resin (2') that passed through a sieve with a mesh size of 850 μm and remained on a sieve with a mesh size of 150 μm, and a fine powder (2'-2) that passed through a sieve with a mesh size of 150 μm were obtained.

[0373] (Granulation process)

[0374] Next, the fine powder (2'-1) and the fine powder (2'-2) were mixed at a mass ratio of 17:3 (w:w) to obtain fine powder (2'-3). The D50 (mass average particle size) of the fine powder (2'-3) was 91 μm. Next, 60 parts by mass of the fine powder (2'-3) were heated to 67°C, put into a food grinder (MK-K48P; manufactured by Panasonic) heated to 80°C, and while stirring, 40 parts by mass of deionized water adjusted to 82°C was added for 5 seconds, and then further mixed for 15 seconds to obtain granulated gel (2'-3).

[0375] (Granulation gel adding process)

[0376] Next, after 2 minutes from the start of the above-mentioned granulation, 80 parts by mass of the granulated gel (2'-3) were added to 360 parts by mass of the granulated water-containing gel (2') obtained by repeating the above-mentioned operation. Immediately thereafter, the mixture was mixed for 10 seconds using a mortar stirrer (manufactured by West Japan Testing Equipment Co., Ltd.) preheated to 80°C, thereby obtaining a mixed gel (2'-4). The temperatures of the granulated gel (2'-3) and the granulated water-containing gel (2') immediately before mixing using the mortar stirrer were 70°C and 55°C, respectively. In addition, the granulated gel (2'-3) and the granulated water-containing gel (2') had good miscibility when mixed using the mortar stirrer.

[0377] (Drying process)

[0378] Next, the mixed gel (2'-4) was spread on a metal net with a mesh size of 300 μm and placed in a hot air dryer. Then, hot air at 190° C. was blown for 20 minutes to dry the mixed gel (2'-4) to obtain a dried polymer (2'-4). The dried polymer (2'-4) did not contain undried matter.

[0379] (Grading process)

[0380] Next, the dry polymer (2'-4) was put into a roll mill (WML type roll mill; manufactured by Inoguchi Giken Co., Ltd.) for pulverization, and then classified using two types of JIS standard sieves with mesh sizes of 850 μm and 150 μm. The agglomerated dry polymer remaining on the sieve with a mesh size of 850 μm was repeatedly pulverized and classified until the entire amount of the polymer passed through the sieve with a mesh size of 850 μm. By this operation, a water-absorbent resin (2'-4) before surface cross-linking, which passed through the sieve with a mesh size of 850 μm and remained on the sieve with a mesh size of 150 μm, was obtained.

[0381] (Surface cross-linking process)

[0382] Next, a surface crosslinking agent aqueous solution consisting of 0.3 parts by mass of ethylene carbonate, 0.5 parts by mass of propylene glycol, and 2.7 parts by mass of deionized water was sprayed onto 100 parts by mass of the water-absorbent resin (2'-4) before surface crosslinking and uniformly mixed. The resulting mixture was then heated at 200°C for 40 minutes to perform surface crosslinking.

[0383] Next, while stirring and cooling the mixture, an additive aqueous solution consisting of 1 part by mass of a 27% by mass aluminum sulfate aqueous solution and 0.2 parts by mass of a 60% by mass sodium lactate aqueous solution was added. Then, the obtained mixture was classified using two JIS standard sieves with mesh sizes of 850 μm and 150 μm. As for the agglomerate-like mixture remaining on the sieve with a mesh size of 850 μm, the agglomerates were repeatedly crushed and classified until the entire amount could be sieved through the sieve with a mesh size of 850 μm. Through this operation, a surface-crosslinked water-absorbent resin (2'-4) was obtained that passed through a sieve with a mesh size of 850 μm and remained on a sieve with a mesh size of 150 μm. The physical properties of the surface-crosslinked water-absorbent resin (2'-4) are shown in Table 2.

[0384] [Comparative Example 3]

[0385] (Step of Preparing Monomer Aqueous Solution)

[0386] Into a 2 L polypropylene container, 400.0 parts by mass of acrylic acid, 3.2 parts by mass of polyethylene glycol diacrylate (average molecular weight: 523), 0.08 parts by mass of allyl methacrylate, and 0.04 parts by mass of IRGACURE (registered trademark) 819 were added and mixed. Then, 640.0 parts by mass of a 24.0% by mass sodium hydroxide aqueous solution was slowly added to the container and mixed, thereby preparing a monomer aqueous solution (3') having a liquid temperature of 40°C.

[0387] (Polymerization process)

[0388] Next, while stirring the monomer aqueous solution (3') at a liquid temperature of 40°C, 24.0 parts by mass of a 4% sodium persulfate aqueous solution was added. Then, the monomer aqueous solution (3') was immediately poured into a stainless steel cylinder-shaped container (bottom surface 340×340 mm, height 25 mm, inner surface Teflon (registered trademark) coating) in an atmosphere-open state. In addition, while pouring the monomer aqueous solution (3') into the cylinder-shaped container, the monomer aqueous solution (3') was irradiated with ultraviolet rays. The cylinder-shaped container was heated with a heating plate (NEO HOTPLATE HI-1000; manufactured by Inouchi Seieido Co., Ltd.) to a surface temperature of 50°C.

[0389] Soon after the monomer aqueous solution (3') is poured into the cylinder-shaped container, the polymerization reaction begins. One minute after the polymerization reaction begins, the ultraviolet irradiation is stopped, and after another two minutes, the water-containing gel (3') is taken out of the cylinder-shaped container. This series of operations is performed in an open state to the atmosphere.

[0390] (Gel crushing process)

[0391] Next, the hydrogel (3') obtained in the polymerization reaction was cut into small pieces each weighing about 60 g, and then the gel was crushed using a meat grinder (HL-G22SN; die diameter 8.0 mm; manufactured by REMACOM Co., Ltd.) to obtain a granular hydrogel (3'). The amount of the hydrogel (3') fed was about 360 g / min, and in parallel with the feeding of the hydrogel (3'), deionized water adjusted to 80°C was added to the meat grinder at an addition amount of 25 g / min while the gel was crushed.

[0392] The granular aqueous gel (3') had a D50 (mass average particle size) of 550 μm and a σζ (logarithmic standard deviation of particle size distribution) of 1.01.

[0393] (Drying process)

[0394] Next, the granular hydrogel (3') was spread on a metal mesh with a mesh size of 300 μm and placed in a hot air dryer. Then, hot air at 180°C was blown for 30 minutes to dry the granular hydrogel (3') to obtain a dried polymer (3'). The 180°C hot air was blown from the bottom of the metal mesh to the top for the first 15 minutes and from the top of the metal mesh to the bottom for the last 15 minutes. The dried polymer (3') did not contain any undried matter.

[0395] (Grading process)

[0396] Next, the dried polymer (3') was put into a roll mill (WML type roll mill; manufactured by Inoguchi Giken Co., Ltd.) and pulverized, and then classified using two types of JIS standard sieves with mesh sizes of 850 μm and 150 μm. This operation provided a water-absorbent resin (3') before surface crosslinking in a randomly crushed state that passed through the sieve with a mesh size of 850 μm and remained on the sieve with a mesh size of 150 μm, and a fine powder (3'-1) that passed through the sieve with a mesh size of 150 μm.

[0397] (Granulation process)

[0398] Next, 100 parts by mass of the fine powder (3'-1) was heated to 70°C and placed in a Loedige mixer. While stirring, 100 parts by mass of deionized water adjusted to 70°C was added and mixed for about 1 minute to obtain a granulated gel (3'-1).

[0399] (Granulation gel adding process)

[0400] Next, after 2.5 minutes from the start of the above-mentioned granulation, 80 parts by mass of the granulated gel (3'-1) were added to 320 parts by mass of the granulated water-containing gel (3') obtained by repeating the above-mentioned operation. Immediately thereafter, the mixture was mixed for 10 seconds using a mortar stirrer (manufactured by West Japan Testing Equipment Co., Ltd.) preheated to 80°C, thereby obtaining a mixed gel (3'-2). The temperatures of the granulated gel (3'-1) and the granulated water-containing gel (3') immediately before mixing using the mortar stirrer were 55°C and 52°C, respectively. In addition, the granulated gel (3'-1) and the granulated water-containing gel (3') had good miscibility when mixed using the mortar stirrer.

[0401] (Drying process)

[0402] Next, the mixed gel (3'-2) is spread on a metal mesh with a mesh size of 300 μm and placed in a hot air dryer. Then, hot air at 180°C is blown for 30 minutes to dry the mixed gel (3'-2) to obtain a dried polymer (3'-2). The 180°C hot air is blown from the bottom of the metal mesh to the top for the first 15 minutes and from the top of the metal mesh to the bottom for the last 15 minutes. The dried polymer (3'-2) does not contain undried matter.

[0403] (Grading process)

[0404] Next, the dried polymer (3'-2) was put into a roll mill (WML type roll mill; manufactured by Inoguchi Giken Co., Ltd.) and pulverized, and then classified using two types of JIS standard sieves with mesh sizes of 850 μm and 150 μm. This operation obtained a water-absorbent resin (3'-2) before surface cross-linking in a randomly crushed state that passed through the sieve with a mesh size of 850 μm and remained on the sieve with a mesh size of 150 μm.

[0405] (Surface cross-linking process)

[0406] Next, a surface crosslinking agent aqueous solution consisting of 1.0 parts by mass of ethylene carbonate and 4.0 parts by mass of deionized water was sprayed and uniformly mixed with respect to 100 parts by mass of the water-absorbent resin (3'-2) before surface crosslinking. Then, the obtained mixture was heat-treated at 180°C for 40 minutes to perform surface crosslinking. Next, the mixture was classified using two JIS standard sieves with mesh sizes of 850 μm and 150 μm. Through this operation, a surface crosslinked water-absorbent resin (3'-2) was obtained that passed through a sieve with a mesh size of 850 μm and remained on a sieve with a mesh size of 150 μm. The various physical properties of the surface crosslinked water-absorbent resin (3'-2) are shown in Table 2.

[0407] [Comparative Example 4]

[0408] (Step of Preparing Monomer Aqueous Solution)

[0409] Into a 2 L polypropylene container, 400.0 parts by mass of acrylic acid, 3.2 parts by mass of polyethylene glycol diacrylate (average molecular weight: 523), 0.4 parts by mass of hexanediol diacrylate, and 0.04 parts by mass of IRGACURE (registered trademark) 819 were added and mixed. Then, 640.0 parts by mass of a 24.0% by mass sodium hydroxide aqueous solution was slowly added to the container and mixed, thereby preparing a monomer aqueous solution (4') having a liquid temperature of 40°C.

[0410] (Polymerization process)

[0411] Next, while stirring the monomer aqueous solution (4') at a liquid temperature of 40°C, 24.0 parts by mass of a 4% sodium persulfate aqueous solution was added. Then, the monomer aqueous solution (4') was immediately poured into a stainless steel cylinder-shaped container (bottom surface 340×340 mm, height 25 mm, inner surface Teflon (registered trademark) coating) in an atmosphere-open state. In addition, while pouring the monomer aqueous solution (4') into the cylinder-shaped container, the monomer aqueous solution (4') was irradiated with ultraviolet rays. The cylinder-shaped container was heated with a heating plate (NEO HOTPLATE HI-1000; manufactured by Inouchi Seieido Co., Ltd.) to a surface temperature of 50°C.

[0412] Soon after the monomer aqueous solution (4') is poured into the cylinder-shaped container, the polymerization reaction begins. One minute after the polymerization reaction begins, the ultraviolet irradiation is stopped, and after another two minutes, the water-containing gel (4') is taken out of the cylinder-shaped container. This series of operations is performed in an open state to the atmosphere.

[0413] (Gel crushing process)

[0414] Next, the hydrogel (4') obtained in the polymerization reaction was cut into small pieces each weighing about 60 g, and then the gel was crushed using a meat grinder (HL-G22SN; die diameter 8.0 mm; manufactured by REMACOM Co., Ltd.) to obtain a granular hydrogel (4'). The amount of the hydrogel (4') fed was about 360 g / min, and in parallel with the feeding of the hydrogel (4'), deionized water adjusted to 80°C was added to the meat grinder at an addition amount of 25 g / min while the gel was crushed.

[0415] The granular aqueous gel (4') had a D50 (mass average particle size) of 540 μm and a σζ (logarithmic standard deviation of particle size distribution) of 1.04.

[0416] (Drying process)

[0417] Next, the granular hydrogel (4') was spread on a metal mesh with a mesh size of 300 μm and placed in a hot air dryer. Then, hot air at 180°C was blown for 30 minutes to dry the granular hydrogel (4') to obtain a dried polymer (4'). The 180°C hot air was blown from the bottom of the metal mesh to the top for the first 15 minutes and from the top of the metal mesh to the bottom for the last 15 minutes. The dried polymer (4') did not contain any undried matter.

[0418] (Grading process)

[0419] Next, the dried polymer (4') was put into a roll mill (WML type roll mill; manufactured by Inoguchi Giken Co., Ltd.) and pulverized, and then classified using two types of JIS standard sieves with mesh sizes of 850 μm and 150 μm. This operation provided a water-absorbent resin (4') before surface crosslinking in a randomly crushed state that passed through the sieve with a mesh size of 850 μm and remained on the sieve with a mesh size of 150 μm, and a fine powder (4'-1) that passed through the sieve with a mesh size of 150 μm.

[0420] (Granulation process)

[0421] Next, 100 parts by mass of the fine powder (4'-1) was heated to 70°C and placed in a Loedige mixer. While stirring, 100 parts by mass of deionized water adjusted to 70°C was added and mixed for about 1 minute to obtain a granulated gel (4'-1).

[0422] (Granulation gel adding process)

[0423] Next, after 2.5 minutes from the start of the above-mentioned granulation, 100 parts by mass of the granulated gel (4'-1) was added to 300 parts by mass of the granulated water-containing gel (4') obtained by repeating the above-mentioned operation. Immediately thereafter, the mixture was mixed for 10 seconds using a mortar stirrer (manufactured by West Japan Testing Equipment Co., Ltd.) preheated to 80°C to obtain a mixed gel (4'-2). The temperatures of the granulated gel (4'-1) and the granulated water-containing gel (4') immediately before mixing using the mortar stirrer were 55°C and 52°C, respectively. In addition, the granulated gel (4'-1) and the granulated water-containing gel (4') had good miscibility when mixed using the mortar stirrer.

[0424] (Drying process)

[0425] Next, the mixed gel (4'-2) is spread on a metal mesh with a mesh size of 300 μm and placed in a hot air dryer. Then, hot air at 180°C is blown for 30 minutes to dry the mixed gel (4'-2) to obtain a dried polymer (4'-2). The 180°C hot air is blown from the bottom of the metal mesh to the top for the first 15 minutes and from the top of the metal mesh to the bottom for the last 15 minutes. The dried polymer (4'-2) does not contain undried matter.

[0426] (Grading process)

[0427] Next, the dried polymer (4'-2) was put into a roll mill (WML type roll mill; manufactured by Inoguchi Giken Co., Ltd.) and pulverized, and then classified using two types of JIS standard sieves with mesh sizes of 850 μm and 150 μm. This operation obtained a water-absorbent resin (4'-2) before surface cross-linking in a randomly crushed state that passed through the sieve with a mesh size of 850 μm and remained on the sieve with a mesh size of 150 μm.

[0428] (Surface cross-linking process)

[0429] Next, a surface crosslinking agent aqueous solution consisting of 0.5 parts by mass of ethylene carbonate, 3.0 parts by mass of methanol, and 3.0 parts by mass of deionized water was sprayed and uniformly mixed with respect to 100 parts by mass of the water-absorbent resin (4'-2) before surface crosslinking. Then, the obtained mixture was heat-treated at 180°C for 40 minutes to perform surface crosslinking. Next, the mixture was classified using two JIS standard sieves with mesh sizes of 850 μm and 150 μm. Through this operation, a surface crosslinked water-absorbent resin (4'-2) was obtained that passed through a sieve with a mesh size of 850 μm and remained on a sieve with a mesh size of 150 μm. The various physical properties of the surface crosslinked water-absorbent resin (4'-2) are shown in Table 2.

[0430] [Comparative Example 5]

[0431] (Step of Preparing Monomer Aqueous Solution)

[0432] Into a 2L polypropylene container, 11.0 parts by mass of a 0.5% by mass IRGACURE (registered trademark) 819 solution diluted with acrylic acid, 26.0 parts by mass of a 5.0% by mass polyethylene glycol diacrylate (average molecular weight: 400) solution diluted with acrylic acid, 14.0 parts by mass of a 5.0% by mass trimethylolpropane triacrylate solution (ethoxylated TMPTA, TMP(EO)9TA, M-3190; manufactured by MIWON Specialty Chemical Co., Ltd.) diluted with acrylic acid, and 445.2 parts by mass of acrylic acid were added and mixed. Then, 800.0 parts by mass of a 24.0% by mass sodium hydroxide aqueous solution was slowly added to the container and mixed, thereby preparing a monomer aqueous solution (5'). The neutralization rate of acrylic acid in the monomer aqueous solution (5') was 70 mol%. In addition, due to the neutralization heat and dissolution heat generated during the mixing process, the liquid temperature of the obtained monomer aqueous solution (5') exceeded 50°C.

[0433] (Polymerization process)

[0434] Next, the monomer aqueous solution (5') was cooled while stirring, and when the liquid temperature reached 45°C, 30.0 parts by mass of a 5.0% sodium bicarbonate aqueous solution, an aqueous solution obtained by dissolving 1.6 parts by mass of aluminum sulfate in 28.0 parts by mass of a 5.0% sodium bicarbonate aqueous solution, and 60.0 parts by mass of a 1.0% OFX-0193 (XIAMETER (registered trademark)) aqueous solution were added and mixed. The obtained mixture was stirred for about 2 seconds and then poured into a stainless steel cylinder container (bottom surface 150×150 mm, height 90 mm, inner surface Teflon (registered trademark) coating) in an open state to the atmosphere. In addition, while pouring the mixture into the cylinder container, ultraviolet rays were also irradiated to the mixture. The surface temperature of the cylinder container was heated to 80°C.

[0435] After the mixture is poured into the cylinder-shaped container, the polymerization reaction starts after about 30 seconds. Two minutes after the polymerization reaction starts, the ultraviolet irradiation is stopped and the water-containing gel (5') is taken out of the cylinder-shaped container. This series of operations is performed in an open state to the atmosphere.

[0436] (Gel crushing process)

[0437] Next, the hydrogel (5') obtained in the polymerization reaction was cut into small pieces each weighing about 60 g, and then the gel was crushed using a meat grinder (HL-G22SN; die diameter 8.0 mm; manufactured by REMACOM Co., Ltd.) to obtain a granular hydrogel (5'). The amount of the hydrogel (5') fed was about 360 g / min, and in parallel with the feeding of the hydrogel (5'), deionized water adjusted to 80°C was added to the meat grinder at an addition amount of 50 g / min while the gel was crushed.

[0438] The granular aqueous gel (5') had a D50 (mass average particle size) of 910 μm and a σζ (logarithmic standard deviation of particle size distribution) of 1.02.

[0439] (Drying process)

[0440] Next, the granular hydrogel (5') was spread on a metal mesh with a mesh size of 300 μm and placed in a hot air dryer. Then, hot air at 180°C was blown for 30 minutes to dry the granular hydrogel (5') to obtain a dried polymer (5'). The 180°C hot air was blown from the bottom of the metal mesh to the top for the first 15 minutes and from the top of the metal mesh to the bottom for the last 15 minutes. The dried polymer (5') contained no undried matter.

[0441] (Grading process)

[0442] Next, the dried polymer (5') was put into a roll mill (WML type roll mill; manufactured by Inoguchi Giken Co., Ltd.) and pulverized, and then classified using two types of JIS standard sieves with mesh sizes of 850 μm and 150 μm. This operation obtained a water-absorbent resin (5') before surface cross-linking in a randomly crushed state that passed through the sieve with a mesh size of 850 μm and remained on the sieve with a mesh size of 150 μm.

[0443] (Surface cross-linking process)

[0444] Next, with respect to 100 parts by mass of the water-absorbent resin (5') before surface crosslinking, a surface crosslinking agent aqueous solution consisting of 0.4 parts by mass of ethylene carbonate, 3.0 parts by mass of methanol, 3.0 parts by mass of deionized water, and 0.5 parts by mass of Aerosil200 (manufactured by EVONIK) was sprayed and uniformly mixed. Then, the obtained mixture was heat-treated at 190°C for 30 minutes to perform surface crosslinking. Next, the mixture was classified using two JIS standard sieves with mesh sizes of 850 μm and 150 μm. Through this operation, a water-absorbent resin (5') after surface crosslinking that passed through a sieve with a mesh size of 850 μm and remained on a sieve with a mesh size of 150 μm was obtained. The various physical properties of the water-absorbent resin (5') after surface crosslinking are shown in Table 2.

[0445] [Comparative Example 6]

[0446] (Step of Preparing Monomer Aqueous Solution)

[0447] Into a 1 L polypropylene container, 291.0 parts by mass of acrylic acid, 247.0 parts by mass of a 48.5% by mass sodium hydroxide aqueous solution, 0.4 parts by mass of polyethylene glycol diacrylate (average molecular weight: 523), 1.8 parts by mass of a 1.0% by mass diethylenetriamine 5-acetic acid 5-sodium aqueous solution, 3.6 parts by mass of a 1.0% by mass IRGACURE (registered trademark) 814 solution diluted with acrylic acid, and 255.0 parts by mass of deionized water were added and mixed to prepare a monomer aqueous solution (6'). Due to the neutralization heat and dissolution heat generated during the mixing process, the liquid temperature of the monomer aqueous solution (6') exceeded 90°C.

[0448] (Polymerization process)

[0449] Next, the monomer aqueous solution (6') was kept at a liquid temperature of 90°C, and 1.8 parts by mass of a 3.0% by mass sodium persulfate aqueous solution was added while stirring. Then, the monomer aqueous solution (6') was immediately poured into a stainless steel cylinder-shaped container (bottom surface 340×340 mm, height 25 mm, inner surface Teflon (registered trademark) coating) in an atmosphere-open state. In addition, while pouring the monomer aqueous solution (6') into the cylinder-shaped container, the monomer aqueous solution (6') was irradiated with ultraviolet rays. The cylinder-shaped container was heated with a heating plate (NEO HOTPLATE HI-1000; manufactured by Inouchi Seieido Co., Ltd.) to a surface temperature of 50°C.

[0450] Soon after the monomer aqueous solution (6') is poured into the cylinder-shaped container, the polymerization reaction begins. During the polymerization reaction, water vapor is generated while expanding and bubbling in all directions, so that the monomer aqueous solution (6') is continuously polymerized. Thereafter, the obtained polymer shrinks to a size slightly larger than the bottom surface of the cylinder-shaped container. Three minutes after the start of the polymerization reaction, the ultraviolet irradiation is stopped and the water-containing gel (6') is taken out of the cylinder-shaped container. This series of operations is carried out in an open state to the atmosphere.

[0451] (Gel crushing process)

[0452] Next, the hydrogel (6') obtained in the polymerization reaction was cut into small pieces each weighing about 60 g, and then the gel was crushed using a meat grinder (HL-G22SN; die diameter 6.0 mm; manufactured by REMACOM Co., Ltd.) to obtain a granular hydrogel (6'). The amount of the hydrogel (6') fed was about 360 g / min, and in parallel with the feeding of the hydrogel (6'), deionized water adjusted to 90°C was added to the meat grinder at an addition amount of 50 g / min while the gel was crushed.

[0453] The granular aqueous gel (6') had a D50 (mass average particle size) of 750 μm and a σζ (logarithmic standard deviation of particle size distribution) of 1.01.

[0454] (Drying process)

[0455] Next, the granular hydrogel (6') was spread on a metal net with a mesh size of 300 μm and placed in a hot air dryer. Then, hot air at 180°C was blown for 30 minutes to dry the granular hydrogel (6') to obtain a dried polymer (6'). The dried polymer (6') did not contain any undried matter.

[0456] (Grading process)

[0457] Next, the dried polymer (6') was put into a roll mill (WML type roll mill; manufactured by Inoguchi Giken Co., Ltd.) and pulverized, and then classified using two types of JIS standard sieves with mesh sizes of 850 μm and 150 μm. This operation provided a water-absorbent resin (6') before surface crosslinking in a randomly crushed state that passed through the sieve with a mesh size of 850 μm and remained on the sieve with a mesh size of 150 μm, and a fine powder (6'-1) that passed through the sieve with a mesh size of 150 μm.

[0458] (Granulation process)

[0459] Next, 100 parts by mass of the fine powder (6'-1) was placed in a Loedige mixer, and 100 parts by mass of deionized water adjusted to 60° C. was added halfway through the stirring, followed by mixing for about 1 minute to obtain a granulated gel (6'-1).

[0460] (Drying process)

[0461] Next, the granulated gel (6'-1) was spread on a metal net with a mesh size of 300 μm and placed in a hot air dryer. Then, hot air at 170°C was blown for 30 minutes to dry the granulated gel (6'-1) to obtain a dried polymer (6'-1). The dried polymer (6'-1) did not contain undried matter.

[0462] (Grading process)

[0463] Next, the dried polymer (6'-1) was put into a roll mill (WML type roll mill; manufactured by Inoguchi Giken Co., Ltd.) and pulverized, and then classified using two types of JIS standard sieves with mesh sizes of 850 μm and 150 μm. This operation obtained a water-absorbent resin (6'-1) before surface cross-linking in a randomly crushed state that passed through the sieve with a mesh size of 850 μm and remained on the sieve with a mesh size of 150 μm.

[0464] Next, 80 parts by mass of the water-absorbent resin (6') before surface crosslinking and 20 parts by mass of the water-absorbent resin (6'-1) before surface crosslinking were mixed to obtain a water-absorbent resin (6'-2) before surface crosslinking.

[0465] (Surface cross-linking process)

[0466] Next, with respect to 100 parts by mass of the water-absorbent resin (6'-2) before surface crosslinking, a surface crosslinking agent aqueous solution consisting of 3.3 parts by mass of cationic colloidal silica (trade name: Klebosol 30CAL25 30% aqueous solution; manufactured by AZ Electronic Material Co., Ltd.), 0.5 parts by mass of 1,3-propylene glycol, 1.0 parts by mass of methanol, and 3.0 parts by mass of deionized water was sprayed and uniformly mixed. Then, the obtained mixture was heated at 200°C for 40 minutes to perform surface crosslinking. Next, classification was performed using two JIS standard sieves with mesh sizes of 850μm and 150μm. Through this operation, a water-absorbent resin (6'-2) after surface crosslinking that passed through a sieve with a mesh size of 850μm and remained on a sieve with a mesh size of 150μm was obtained. The various physical properties of the water-absorbent resin (6'-2) after surface crosslinking are shown in Table 2.

[0467] Various physical properties of the surface-crosslinked water-absorbent resins obtained in Examples 1 to 4 and Comparative Examples 1 to 6 were measured. The measurement methods are as follows. Table 2 shows the measurement results.

[0468] <Measurement method>

[0469] [CRC (absorption ratio without pressure)]

[0470] The CRC (absorption capacity without pressure) of the water-absorbent resin of the present invention is measured according to the EDANA method (WSP241.3 (10)). Specifically, 0.2 g of the water-absorbent resin is placed in a nonwoven bag, and the bag is immersed in an excess amount of a 0.9 mass % sodium chloride aqueous solution for 30 minutes to allow the water-absorbent resin to swell freely, and then the bag is dehydrated by a centrifugal separator (centrifugal force: 250 G), and then the CRC (absorption capacity without pressure) (unit: g / g) is measured.

[0471] [AAP (Absorption under Pressure)]

[0472] The AAP (absorption under pressure) of the water-absorbent resin of the present invention is measured according to the EDANA method (WSP242.3 (10)). However, in the present invention, the pressure condition is changed to 4.83 kPa (49 g / cm 2 Specifically, 0.9 g of the water-absorbent resin was subjected to 4.83 kPa (49 g / cm 2 The sample was swollen in an excess of 0.9 mass % sodium chloride aqueous solution under a pressure of 4.83 kPa (0.7 psi) for 1 hour, and then its AAP (absorption capacity under pressure) (unit: g / g) was measured. That is, in this specification, AAP (absorption capacity under pressure) is the value measured under a pressure of 4.83 kPa.

[0473] [SFC (Saline Flow Conductivity)]

[0474] The SFC (saline flow conductivity) of the water-absorbent resin of the present invention (unit: ×10 -7 cm 3 ·sec / g) was measured according to the measurement method described in U.S. Patent No. 5,669,894.

[0475] [Solid content]

[0476] The solid content of the water-absorbent resin of the present invention is calculated using the water content measured according to the EDANA method (WSP 230.3 (10)). However, in the present invention, the amount of the water-absorbent resin as a sample is changed to 1.0 g and the drying temperature is changed to 180° C. from the measurement conditions specified in WSP 230.3 (10). In addition, the value calculated by the formula "100-water content (mass %)" is used as the solid content of the water-absorbent resin (unit: mass %).

[0477] In addition, the solid content of the granular hydrogel or granulated gel is also calculated using the water content measured according to the EDANA method (WSP 230.3 (10)). However, in the present invention, the amount of the granular hydrogel or granulated gel as a sample is changed to 2.0 g and the drying temperature is changed to 180° C. from the measurement conditions specified in WSP 230.3 (10). And the value calculated by the formula "100-water content (mass %)" is used as the solid content of the granular hydrogel or granulated gel (unit: mass %).

[0478] In addition, regarding the solid content of the bulk dry polymer, a sample (water-absorbent resin) was collected from any position in the drying process and crushed to a particle size of 5 mm or less. Then, in the same manner as the method for measuring the solid content of the water-absorbent resin, the water content measured according to the EDANA method (WSP230.3 (10)) was used to calculate. And the value calculated by the formula "100-water content (mass %)" was used as the solid content of the bulk dry polymer (unit: mass %). Here, the samples were collected from any 5 positions in the drying process, and the average value of the obtained values ​​was used as the solid content of the bulk dry polymer.

[0479] [D50 (mass average particle size)]

[0480] The D50 (mass average particle size) (unit: μm) of the water-absorbent resin of the present invention is measured according to the measurement method described in "(3) Mass-Average Particle Diameter (D50) and Logarithmic Standard Deviation (σζ) of Particle Diameter Distribution" in U.S. Patent No. 7,638,570.

[0481] [D50 (mass average particle size) of granular hydrogel]

[0482] The mass average particle size (D50) of the pulverized granular hydrogel in terms of solid content was measured. Specifically, 20 g of the granular hydrogel (solid content α mass %) at a temperature of 20 to 25° C. was added to 500 g of a 20 mass % sodium chloride aqueous solution (hereinafter referred to as “EMAL aqueous solution”) containing 0.08 mass % of EMAL20C (surfactant; manufactured by Kao Corporation) to obtain a dispersion, and the dispersion was stirred at 300 rpm for 1 hour using a stirring bar having a length of 50 mm and a diameter of 7 mm (here, a cylindrical polypropylene container having a height of 21 cm and a diameter of 8 cm, and a capacity of about 1.14 L).

[0483] After the stirring was completed, the dispersion was injected into the center of each JIS standard sieve (diameter 21 cm; mesh size of each sieve: 8 mm / 4 mm / 2 mm / 1 mm / 0.60 mm / 0.30 mm / 0.15 mm / 0.075 mm) stacked on a turntable. After the granular hydrogel was completely washed onto the sieve with 100 g of EMAL aqueous solution, the sieve was rotated by hand (20 rpm) while a shower head (72 holes, 6.0 L / min) was used to spray the sieve from 30 cm above the sieve within a spray range (50 cm 2) was poured over the entire sieve so as to cover the entire sieve, thereby classifying the granular hydrogel. The granular hydrogel on the first sieve after classification was drained for about 2 minutes and then weighed. The same operation was performed on the sieves after the second sieve to classify, and after draining, the granular hydrogel remaining on each sieve was weighed.

[0484] The mass ratio X (unit: mass %) of the granular hydrogel remaining on each sieve relative to the mass ratio of the granular hydrogel as a whole is calculated by the following formula (1). For a granular hydrogel having a solid content of α mass % remaining on the sieve, the mesh size R (α) (unit: mm) of the corresponding sieve used for the granular hydrogel is calculated by the following formula (2). X and R (α) of the granular hydrogel remaining on each sieve are plotted on logarithmic probability paper to prepare a graph (particle size distribution) showing the relationship between the cumulative weight ratio of X and R (α). From the graph, the particle size when the residual percentage is equivalent to 50 mass % is read and taken as the mass average particle size (D50) of the granular hydrogel.

[0485] X=(w / W)×100 Formula (1)

[0486] R(α)=(20 / W) 1 / 3 ×r Formula (2)

[0487] Here, X, w, W, R(α) and r are the following values.

[0488] X: Mass % of the granular hydrogel remaining on each sieve after classification and draining (unit: mass %)

[0489] w: The mass of the granular hydrogel remaining on each sieve after classification and draining (unit: g)

[0490] W: The total mass of the granular hydrogel remaining on each sieve after classification and draining (unit: g)

[0491] R(α): The corresponding mesh size when the particulate hydrogel is classified, converted to a solid content α mass % (unit: mm; converted value)

[0492] r: JIS standard sieve mesh size obtained by classifying the granular hydrogel swollen in a 20 mass % sodium chloride aqueous solution containing 0.08 mass % EMAL 20C (surfactant; manufactured by Kao Corporation) (unit: mm; measured value)

[0493] [σζ(logarithmic standard deviation of particle size distribution)]

[0494] The σζ (logarithmic standard deviation of particle size distribution) (unitless) of the water-absorbent resin of the present invention is measured according to the measurement method described in "(3) Mass-Average Particle Diameter (D50) and Logarithmic Standard Deviation (σζ) of Particle Diameter Distribution" in U.S. Patent No. 7,638,570.

[0495] On the other hand, σζ (logarithmic standard deviation of particle size distribution) of the particulate aqueous gel is measured by the following method.

[0496] That is, the mass % of the granular hydrogel remaining on each sieve was calculated by the same method as the measurement method of D50 (mass average particle size) of the granular hydrogel, and the particle size distribution of the granular hydrogel was plotted on logarithmic probability paper. Based on the plotted graph, the corresponding particle size when "oversize cumulative % value R" = 84.1 mass % (this is referred to as X1) and the corresponding particle size when "oversize cumulative % value R" = 15.9 mass % (this is referred to as X2) were obtained, and σζ (logarithmic standard deviation of particle size distribution) was obtained based on the following formula (3).

[0497] σζ=0.5×ln(X2 / X1)…Equation (3)

[0498] The smaller the value of σζ, the narrower the particle size distribution.

[0499] [Gel thickness 5mm arrival time]

[0500] After changing the pressure condition to 4.83 kPa (49 g / cm 2 In the AAP (absorption under pressure) measurement at 0.7 psi), a laser displacement meter manufactured by KEYENCE (amplifier unit: IL-1000, sensor head: IL-S100, power supply unit: KZ-U3), a data logger (midiLOGGER GL220 manufactured by GRAPHTEC Co., Ltd.), and Microsoft Excel were used to calculate the moving distance of the weight in the vertical direction, thereby measuring the time (unit: second) for the water-absorbent resin of the present invention to reach a gel thickness of 5 mm.

[0501] The measurement was performed in a room whose temperature was adjusted to 23.0±0.5°C and whose humidity was adjusted to between 35% and 50%. The 0.9 mass % sodium chloride aqueous solution used for the measurement was a solution whose temperature was adjusted to 23±0.5°C.

[0502] The specific determination method is as follows. Figure 2As shown, first, the pressure condition was changed to 4.83 kPa (49 g / cm 2 ; 0.7psi) are used for measuring the AAP of the cylinder 3, the piston 2, and the weight 1. 0.9g of water-absorbent resin is placed in the cylinder 3, and the piston 2 is inserted into the cylinder 3 containing the water-absorbent resin. When inserting, care is taken to prevent the water-absorbent resin from being sandwiched between the inner wall of the cylinder 3 and the piston 2. Then, the weight 1 is placed on the piston 2. The weight 1 used is cylindrical and has a flat top surface. The bottom surface of the cylinder 3 is mesh-shaped. Hereinafter, a set of devices consisting of the water-absorbent resin, the cylinder 3, the piston 2, and the weight 1 prepared by the above steps is referred to as a unit set A.

[0503] Then, if Figure 3 As shown in the figure, a surface heater 10 set at 23°C is placed on a horizontal laboratory table, and a SUS tray 9 used for AAP measurement is placed on the surface heater 10. Then, a glass filter 7 used for AAP measurement is placed in the center of the SUS tray 9, with the surface of the glass filter 7 with fewer irregularities on the upper side. Then, a 0.9 mass % sodium chloride aqueous solution 8 is poured into the SUS tray 9 until the water level of the 0.9 mass % sodium chloride aqueous solution 8 is the same as the top surface height of the glass filter 7. When pouring, be careful not to let bubbles enter the glass filter. Next, a filter paper 6 used for AAP measurement is placed in the center of the glass filter 7, with the surface of the filter paper 6 with fewer irregularities on the upper side.

[0504] In addition, in order to measure the vertical position information of the weight 1 when the water-absorbent resin swells, a laser displacement meter manufactured by KEYENCE (the amplifier unit 15 is IL-1000, the sensor head 14 is IL-S100, and the power supply unit 16 is KZ-U3) is set. The power supply unit 16 is connected to the sensor head 14 via the amplifier unit 15. In addition, the clamp 13 is installed on the upper part of the bracket 11 through the fitting sleeve 12, and the clamp 13 supports the sensor head 14. The setting requirement of the sensor head 14 is that after the unit group A is set in the center of the filter paper 6, the laser irradiated from the sensor head 14 is perpendicular to the top surface of the weight 1 in the unit group A, specifically, the laser is irradiated along the irradiation direction indicated by the arrow 18. In addition, in order to appropriately reflect the irradiated laser, a white tape 5 (product name: lead-free tape; model 21-10W; manufactured by Nitto Denko Corporation) is pasted on the laser-irradiated portion of the top surface of the weight 1. The situation where there is tape on the top surface of weight 1 is as follows Figure 4As shown in the plan view. Thus, the position information (numerical data) of the weight 1 in the vertical direction can be measured. The position information of the weight 1 measured by the sensor head 14 is transmitted to the data logger (midiLOGGERGL220 manufactured by GRAPHTEC Co., Ltd.) 17 and stored in the data logger 17. The data logger 17 is connected between the amplifier unit 15 and the power supply unit 16, and is set to be able to continuously store the position information of the weight 1 at intervals of 1 second.

[0505] Under the measurement environment, the measurement starts when the unit group A is placed in the center of the filter paper. At the same time, the laser displacement meter also starts measuring the position information of the weight 1. After 1 hour from the start of the measurement, the laser displacement meter ends the measurement of the position information of the weight 1. Figure 3 The measurement state at the stage where the unit set A is placed on the filter paper and the measurement is started is shown.

[0506] The position information of the weight 1 obtained by the above measurement was extracted from the data recorder 17, and the following analysis was performed on Microsoft Excel. First, the time when the weight 1 sank the lowest within 10 seconds from the start of swelling was set as the "time point of gel thickness 0 mm". After the "time point of gel thickness 0 mm", the water-absorbent resin swells and pushes the weight upward in the vertical direction. Therefore, the absolute value of the difference between the position information value of the "time point of gel thickness 0 mm" and the position information value measured after the "time point of gel thickness 0 mm" represents the distance α (gel thickness α mm) that the swollen water-absorbent resin pushes the weight 1 upward in the vertical direction. The distance α was calculated for each measured elapsed time, and the time taken for the distance to reach 5 mm (the time from the time point of gel thickness 0 mm to the time point of gel thickness 5 mm) (calculated by Microsoft Excel) was taken as the "time to reach gel thickness 5 mm".

[0507] The above measurement was performed twice using the same sample (water-absorbent resin), and the average value thereof was used as the time to reach a gel thickness of 5 mm in the present invention.

[0508] [Gel expansion force, gel expansion rate]

[0509] After changing the pressure condition to 4.83 kPa (49 g / cm 2In the AAP (absorption under pressure) measurement at a pressure of 0.7 psi (0.1 psi), a tensile testing machine (AG-1kNX; manufactured by Shimadzu Corporation) as a tracer (Autograph) and calculation software (TRAPEZIUM X) were used to measure the force applied to push the piston and the weight in the vertical direction when the water-absorbent resin swollen to a "gel thickness of 5 mm" further swelled. The measured numerical data were analyzed using Microsoft Excel to determine the gel expansion force (unit: N) and gel expansion rate (unitless) of the water-absorbent resin of the present invention.

[0510] The specific determination method is as follows. Figure 2 As shown, first, the pressure condition was changed to 4.83 kPa (49 g / cm 2 ; 0.7psi) after the cylinder 3, piston 2, and weight 1 used for the AAP measurement, 0.9g of water-absorbent resin was placed in the cylinder 3, and the piston 2 was inserted into the cylinder 3 with the water-absorbent resin. When inserting, care was taken to prevent the water-absorbent resin from being sandwiched between the inner wall of the cylinder 3 and the piston 2. Then, the weight 1 was placed on the piston 2. The weight 1 used was cylindrical and the top surface was flat. Hereinafter, a set of equipment consisting of the water-absorbent resin, cylinder 3, piston 2, and weight 1 prepared by the above steps will be referred to as unit set A. The operations so far were carried out in a room adjusted to 23±0.5℃ and the humidity between 35% and 50%, and the operations thereafter were carried out in a room adjusted to 23±0.5℃ and the humidity between 35% and 60%.

[0511] A load cell 19 (SLBL-50N; manufactured by Shimadzu Corporation) and a compression jig (S346-51687-08 with a Φ20 upper platen 20 and S346-51687-12 with a Φ118 lower platen 21) were installed on the tracer (AG-1kNX; manufactured by Shimadzu Corporation), and an AAP measuring instrument was placed on the lower platen 21 with a sufficient gap between the upper platen 20 and the lower platen 21. The state in which the load cell 19, the compression jig and the AAP measuring instrument were installed on the tracer 30 is shown in FIG. Figure 5. Here, “placing the AAP measurement instrument on the lower platen 21” refers to the following operation: placing the SUS tray 9 used for AAP measurement on the lower platen 21 in such a manner that the central portion of the lower platen 21 overlaps with the central portion of the SUS tray 9, and then placing the glass filter 7 used for AAP measurement in the central portion of the SUS tray 9 so that the surface of the glass filter 7 with fewer irregularities is on the upper side, and then placing the filter paper 6 used for AAP measurement in the central portion of the glass filter 7 so that the surface of the filter paper 6 with fewer irregularities is on the upper side, and then placing the unit group A in the central portion of the filter paper 6.

[0512] In addition, in the calculation software (TRAPEZIUM X), the following measurement conditions were set: from the time of measurement start, the upper platen 20 set at a certain position was automatically lowered at a speed of 0.1 mm per second, and then, when the upper platen 20 came into contact with the top surface of the weight 1 in the unit group A, the upper platen 20 was fixed at the contact position. In addition, the following measurement conditions were set: the force of the swollen water-absorbent resin pushing up the piston 2 and the weight 1 was continuously measured at intervals of 0.5 seconds via the fixed upper platen 20. Specifically, "Create new test conditions" was clicked on the calculation software, and the following test conditions were set.

[0513] 〔system〕

[0514] Test mode: single

[0515] Test type: Compression

[0516] Load Cell Polarity: Compression

[0517] Moving direction: Downward

[0518] Unit: SI

[0519] Format: Rounded

[0520] 〔sensor〕

[0521] (Test force)

[0522] Channel: Test force amplifier

[0523] Name: Test force

[0524] Max: 50N

[0525] Limit: 40N (check)

[0526] Stress Name: Stress

[0527] Use True Stress: Uncheck

[0528] (stroke)

[0529] Name: Stroke

[0530] Limit: 500mm (check)

[0531] Stroke (deformation) Name: Stroke (deformation)

[0532] Use true deformation: Uncheck

[0533] Perform deflection correction: Uncheck

[0534] (Displacement Meter)

[0535] Displacement meter 1

[0536] Channel: None

[0537] (Amplitude meter)

[0538] Channel: None

[0539] (other)

[0540] Other 1

[0541] Channel: None

[0542] 〔Test control〕

[0543] Stretch Origin: Starting from the Beginning

[0544] Region 1

[0545] Controlled Action: Apply Load

[0546] Control: Stroke

[0547] V1: 0.100000mm / sec

[0548] Setting between area 1 and area 2

[0549] Target value channel

[0550] Test force

[0551] 0.01N

[0552] Area 2

[0553] Controlled Action: Hold

[0554] Control: Stroke

[0555] Setting between area 2 and area 3

[0556] Keep time

[0557] 6000sec

[0558] Area 3

[0559] Control action: OFF

[0560] (End condition)

[0561] Fracture settings: Uncheck all options

[0562] Action after the test: Stop

[0563] Starting point of fracture detection: 0.035%

[0564] (sampling)

[0565] Time: 0.5 sec

[0566] (Preparatory load)

[0567] Uncheck all

[0568] 〔Test piece〕

[0569] Material: Plastic

[0570] Shape: Flat

[0571] Number of batches: 1

[0572] Number of sub-batches: 1

[0573] Dimensions in mm

[0574] 〔Data processing project〕

[0575] No special settings required

[0576] 〔chart〕

[0577] Arbitrary setting

[0578] 〔Report〕

[0579] Arbitrary setting

[0580] Next, I clicked "Select conditions and execute test" on the calculation software, selected the test conditions, and opened the test execution screen. In addition, I right-clicked "Test force" on the screen and performed a correction so that the "test force" displayed on the screen was less than 0.02N.

[0581] For the procedure of the method for measuring the gel swelling power and gel swelling rate of the water-absorbent resin under the above-mentioned measuring environment, refer to Figure 6 to explain.

[0582] First, if Figure 6As shown in (a), the upper platen 20 is manually lowered to contact the top surface of the weight 1 in the unit group A, and the position of the upper platen 20 when contact occurs is set to 0mm. Specifically, based on the position of the upper platen 20, right-click "Stroke" on the test execution screen to perform a zero reset. The manual operation mentioned here refers to the operation using the buttons and dials of the intelligent controller (manufactured by Shimadzu Corporation) connected to the tracer. In addition, the "manual operation" described below also refers to the same operation. In addition, when the weight 1 contacts the upper platen, a slight force is generated by the weight 1 to push the upper platen 20 upward, so the increase in the "test force" can be confirmed on the test execution screen. Here, the point in time when the "test force" reaches 0.1N or more and less than 0.5N due to the "increase in test force" is defined as "contact". Next, as Figure 6 As shown in (b), the upper platen 20 is manually raised by 7.5 mm, and this position of the upper platen 20 is set as the "measurement start position". The reason for the 7.5 mm rise is as follows: Regarding the measurement of the gel expansion force, it is estimated that the swelling of the water-absorbent resin will cause the weight 1 to rise by 5.0 mm (equivalent to a gel thickness of 5 mm), and after the start of the test, when the upper platen 20 descends and contacts the weight 1 at the point where the gel thickness reaches 5 mm, the descending distance of the upper platen 20 should be 2.5 mm, and the 7.5 mm rise is the sum of these estimated values. The point at which the gel thickness reaches 5 mm is known in advance, so the start time of the test is set 25 seconds before this point, so that the descending distance of the upper platen 20 can be estimated (in the above case, since the descending speed of the upper platen 20 is set at 0.1 mm per second, it can be set to 0.1 mm per second × 25 seconds = 2.5 mm).

[0583] Then, if Figure 6 As shown in (c), the upper platen 20 is manually raised further from the "measurement start position (7.5 mm)", the unit group A and the filter paper 6 are lifted from the glass filter 7 without touching the upper platen 20, and then a 0.9 mass % sodium chloride aqueous solution 8 is injected into the SUS tray 9 until the water level of the 0.9 mass % sodium chloride aqueous solution 8 is the same as the top surface height of the glass filter 7. Here, the liquid temperature of the 0.9 mass % sodium chloride aqueous solution 8 used is adjusted to 23 ± 0.5 ° C. In addition, at this time, care is taken not to allow bubbles to enter the glass filter 7.

[0584] In this state, if Figure 6 As shown in (d), the filter paper 6 is placed again in the center of the glass filter 7, and the unit group A is gently placed in the center of the filter paper 6, whereby the water-absorbent resin starts to swell. In addition, when the unit group A is placed on the filter paper 6, the time measurement is also started. Immediately after the swelling starts, Figure 6As shown in (e) of FIG. 8 , the upper platen 20 is manually lowered to the “measurement start position (7.5 mm)”.

[0585] Next, based on the end time of "5 mm gel thickness reaching time" calculated from the start of swelling, click "Start Test" on the test execution screen 25 seconds before the end time, so as to Figure 6 The upper platen 20 is automatically lowered at a speed of 0.1 mm per second as shown in (f). The purpose of lowering the upper platen 20 25 seconds before the start of the swelling is to make the upper platen 20 drop 2.5 mm at the end of the "5 mm gel thickness reaching time" calculated from the start of swelling, so that the upper platen 20 is in contact with the top surface of the weight 1 in the unit group A. Thus, at the end of the "5 mm gel thickness reaching time" calculated from the start of swelling, the upper platen is in contact with the top surface of the weight 1 in the unit group A, and then as shown in (f) Figure 6 As shown in (g), the contact time point was used as the measurement start point, and the force with which the particulate hydrous gel pushed up the piston 2 and the weight 1 was measured every 0.5 seconds for 60 consecutive minutes.

[0586] Then, the force of the particulate hydrogel pushing up the piston and the weight obtained in the above 60-minute measurement was analyzed on Microsoft Excel to calculate the gel swelling force and gel swelling rate of the water-absorbent resin.

[0587] That is, the maximum force from the start of measurement (0 seconds) to the time when 1000 seconds have passed was determined on Microsoft Excel from the push-up force and was defined as the gel swelling force (N).

[0588] In addition, a graph was created on Microsoft Excel with the horizontal axis representing the measurement time (minutes) and the vertical axis representing the corresponding thrust (N). Based on the graph, the slope of the curve represented by the data from the start of the measurement (0 seconds) to 100 seconds was calculated using the SLOPE function, and the value of the slope was used as the gel swelling rate (unitless).

[0589] The above-mentioned measurement was performed twice using the same sample (water-absorbent resin), and the average value was used as the gel swelling force and the gel swelling rate of the present invention.

[0590] [Volume ratio of particles having a cavity volume ratio of 15% by volume or more, volume ratio of particles having a cavity volume ratio of 1% by volume or less]

[0591] The volume occupancy rate (unit: volume %) of particles having a cavity volume ratio of 15% or more and the volume occupancy rate (unit: volume %) of particles having a void volume ratio of 1% or less in the total volume of the water-absorbent resin of the present invention were obtained by acquiring 3D image data of the water-absorbent resin using a microfocus X-ray CT system (inspeXio SMX-100CT; manufactured by Shimadzu Corporation), analyzing the 3D image data using high-speed 3D analysis software (TRI / 3D-VOL-FCS64; manufactured by Ratoc System Engineering Co., Ltd.), and then calculating using statistical analysis software JMP (registered trademark) 14 (SAS Institute Inc., Cary, NC, USA) and Microsoft Excel. Here, the cavity volume ratio and the void volume ratio were obtained using a water-absorbent resin having a particle size of 300 μm to 600 μm. Specifically, the microfocus X-ray CT system was used to obtain 3D image data of a water-absorbent resin with a particle size of 500 μm to 600 μm, a water-absorbent resin with a particle size of 425 μm to 500 μm, and a water-absorbent resin with a particle size of 300 μm to 425 μm, respectively, and analyzed using the above-mentioned high-speed 3D analysis software. Then, these analysis results were collectively calculated using JMP and Excel.

[0592] A more specific calculation method is described by taking a water-absorbent resin with a particle size of 500 μm to 600 μm as an example. First, the extraction method of the water-absorbent resin with a particle size of 500 μm to 600 μm is described. First, JIS standard sieves (The IIDATESTING SIEVE; manufactured by Iida Seisakusho Co., Ltd.; diameter 8 cm, the mesh sizes of the sieves are 600 μm, 500 μm, 425 μm, and 300 μm, respectively) are stacked from top to bottom in order of mesh size from large to small, and a receiving dish (manufactured by Iida Seisakusho Co., Ltd.; diameter 8 cm) is placed on the bottom layer. Next, 10.0 g of the water-absorbent resin is dropped into the top sieve (mesh size of the sieve: 600 μm), and the lid (manufactured by Iida Seisakusho Co., Ltd.; diameter: 8 cm) is placed. Next, the stacked assembly of the cover, four sieves and the receiving dish was shaken for 5 minutes using IIDA SIEVE SHAKER (model ES-65, serial number 0632). After the shaking, only the water-absorbent resin remaining on the sieve with a mesh size of 500 μm was extracted, and this was used as the water-absorbent resin with a particle size of 500 μm to 600 μm. The above operation was carried out in a room where the temperature was adjusted to 20.0 to 25.0° C. and the humidity was adjusted to between 35% and 50%. Here, in the above operation, if the water-absorbent resin with a particle size of 425 μm to 500 μm was to be extracted, only the water-absorbent resin remaining on the sieve with a mesh size of 425 μm was to be extracted, and if the water-absorbent resin with a particle size of 300 μm to 425 μm was to be extracted, only the water-absorbent resin remaining on the sieve with a mesh size of 300 μm was to be extracted.

[0593] Next, 0.3 g of thermosetting spherical particles (Epostar MV1002; manufactured by Nippon Shokubai Co., Ltd.) was placed in a plastic covered cylindrical container (inner diameter of about 1 cm, height of about 5 cm), and then 0.1 g of a water-absorbent resin with a particle size of 500 μm to 600 μm was placed, and the mixture was shaken thoroughly to uniformly disperse the water-absorbent resin in the thermosetting spherical particles, thereby preparing a sample. Next, a double-sided tape was attached to the bottom of the cylindrical container to fix it to the sample stage of the microfocus X-ray CT system, and 3D image data was acquired under the following conditions.

[0594] [Table 1]

[0595]

[0596] Next, analysis was performed in the following steps using the high-speed three-dimensional analysis software.

[0597] 1. From the menu bar, select Particle Measurement, 3D Particle, Particle Separation, and Giant Particle Separation.

[0598] 2. Select "LW" in the "Binarize" tab on the EVC screen, set the W value to the original initial value, and change the L value to a value "1" greater than the initial value to extract the circular measurement target area. Then, this process is performed on all layered images. The image data extracted by this operation is stored as (A) in "bin5ch" (b5) on the BC screen.

[0599] 3. Select "LW" in the "Binarize" tab on the EVC screen, set the W value to the original initial value, and change the L value from the initial value to "37580" to extract all the water-absorbent resins in the measurement target area. Then, this process is applied to all the layered images. The particle image data extracted by this operation is stored as (B) in "binDch" (bD) on the BC screen.

[0600] 4. Based on the particle image data (B), first select "ErsSml" in the "Binary" tab on the EVC screen to exclude particles with a particle size of less than 10voxcel that are considered to be noise. Next, select "Invert" in the "Binary" tab on the EVC screen to invert the area where particles are extracted and the area where particles are not extracted. Next, select "Ers Sml" in the "Binary" tab on the EVC screen to exclude particles with a particle size of less than 1voxcel that are considered to be noise. Next, select "Labeling" in the "3D" tab on the EVC screen, further select volume and Max, and only extract the area with the largest volume. Here, after confirming that "Label Count" is displayed as 1, select "Invert" again in the "Binary" tab on the EVC screen to exclude noise in the measurement object area, and extract all particles in the form of their cavities being filled. The particle image data extracted by the above operation is taken as (C) and saved in "bin2ch" (b2) on the BC screen.

[0601] 5. In the "LOp" tab (inter-channel logical operation processing), select "2" for object 1 and "D" for object 2, further select "SUB", and press "Execute" to subtract particle image data (B) from particle image data (C). Then, select "Ers Sml" in the "Binary" tab on the EVC screen, exclude particles with a particle size of 1voxcel or less that are considered to be noise, and extract the cavity (Void). The particle image data extracted by these operations is saved as (D) in "bin6ch" (b6) on the BC screen.

[0602] 6. Based on the particle image data (C), select "8-connected neighborhood" in the "3D" tab on the EVC screen, perform two expansions, and then perform two contractions. The particle image data extracted by this operation is (E) and saved in "bin1ch" (b1) on the BC screen.

[0603] 7. In the "LOp" tab (inter-channel logical operation processing), select "2" for object 1 and "D" for object 2, select "SUB", and press "Execute" to subtract particle image data (C) from particle image data (E). This operation extracts the pits. The obtained particle image data is stored as (F) in "bin7ch" (b7) on the BC screen.

[0604] 8. Based on the particle image data (E), on the giant particle separation screen, select "small particle extraction" (do not select large particle extraction), set the constriction ratio, "Repair Filter Size", and "Repair Mrg SmlDiameter" to "0", thereby separating the particles and color-coding the particles.

[0605] 9. Select "Labeling" in the "3D" tab on the EVC screen, further select "Coordinate Value" (loop), and set the microparticle size to "100" to perform particle separation operations. The particle image data extracted through these operations is (G) and saved in "bin1ch" (b1) on the BC screen.

[0606] 10. Select "Particle Measurement", "Void in 3D Particles", and "Measurement after Separation" from the menu bar.

[0607] 11. On the measurement screen after separation, select "voxcel" as the unit, then select "edge particle removal", further select "surface area calculation" and "void calculation" as measurement items, select "Binary 5ch" to specify it as the ROI to be measured, and perform calculation processing.

[0608] 12. The data obtained by the calculation process in item 10 above was extracted using Excel's CSV format.

[0609] Through the above operation, the volume (unit: mm2) of all water-absorbent resin particles present in the measurement target area was obtained for each particle. 3 ), cavity volume (unit: mm 3 ) and cavity volume (unit: mm3 The cavity volume and the cavity volume of each particle are values ​​calculated based on the state that the cavity and the cavity in the water-absorbent resin are filled. In addition, the water-absorbent resin present in the measurement target area contains about 50 to 500 particles.

[0610] Next, the water-absorbent resin having a particle size of 425 μm to 500 μm and the water-absorbent resin having a particle size of 300 μm to 425 μm were analyzed in the same procedure as above.

[0611] Next, the volume (unit: mm2) of each particle of the water-absorbent resin having a particle size of 300 μm to 600 μm obtained by the above operation was measured. 3 ), cavity volume (unit: mm 3 ) and cavity volume (unit: mm 3 ) are all imported into the same processing table of Excel. Here, the Excel file format used is XLSX format.

[0612] Next, in the processing table, the void volume ratio (unit: volume %) of each particle was calculated based on the following formula (4).

[0613] Cavity volume ratio = H / (I-J)×100…Formula (4)

[0614] in,

[0615] H: cavity volume (unit: mm 3 )

[0616] I: Volume (unit: mm 3 )

[0617] J: cavity volume (unit: mm 3 )

[0618] Next, in the processing table, the cavity volume ratio (unit: volume %) of each particle was calculated based on the following formula (5).

[0619] Porosity volume ratio = J / (I-H) × 100…Formula (5)

[0620] in,

[0621] H: cavity volume (unit: mm 3 )

[0622] I: Volume (unit: mm 3 )

[0623] J: cavity volume (unit: mm 3 )

[0624] Next, in the processing table, the true volume of each particle (unit: mm 3 ).

[0625] True volume = I - H - J ... Formula (6)

[0626] in,

[0627] H: cavity volume (unit: mm 3 )

[0628] I: Volume (unit: mm 3 )

[0629] J: cavity volume (unit: mm 3 )

[0630] Next, the void volume ratio, cavity volume ratio and true volume of each particle of the water-absorbent resin having a particle size of 300 μm to 600 μm obtained by the above operation were all imported into a statistical analysis software (JMP) to create a data table.

[0631] Then, the volume fraction (unit: volume %) of particles having a void volume fraction of 1 volume % or less and the volume fraction (unit: volume %) of particles having a cavity volume fraction of 15 volume % or more were calculated in the following steps.

[0632] 1. First, in the analysis function of the statistical analysis software (JMP), "Univariate Distribution" was selected, and the column with the true volume input was selected as "Y, Column". "OK" was pressed, and the total of the summary statistics in the analysis results was confirmed. The sum of the true volumes of all the water-absorbent resins (unit: mm 3 ). Set the sum obtained here to (K).

[0633] 2. Next, the data filtering function of the statistical analysis software (JMP) was used to select only the water-absorbent resins having a void volume ratio of 1 volume % or less.

[0634] 3. Next, in the analysis function of the statistical analysis software (JMP), "Univariate distribution" was selected, and the column in which the true volume was input was selected as "Y, column". "OK" was pressed, and the total of the summary statistics in the analysis results was confirmed. Thus, the sum of the true volumes of the water-absorbent resin selected in the above step 2 was calculated (unit: mm 3 ). Let the sum obtained here be (L).

[0635] 4. Next, the data filtering function of the statistical analysis software (JMP) was used to select only the water-absorbent resins having a cavity volume ratio of 15% by volume or more.

[0636] 5. Next, in the analysis function of the statistical analysis software (JMP), "Univariate distribution" was selected, and the column in which the true volume was input was selected as "Y, column". "OK" was pressed to confirm the total of the summary statistics in the analysis results, thereby calculating the sum of the true volumes of the water-absorbent resin selected in the above step 4 (unit: mm 3 ). Set the sum obtained here to (M).

[0637] 6. Then, based on the values ​​of (K), (L), and (M) calculated through the above steps 1, 3, and 5, the volume ratio (unit: volume %) of particles with a cavity volume ratio of less than 1 volume % and the volume ratio (unit: volume %) of particles with a cavity volume ratio of more than 15 volume % were calculated based on the following formulas (7) and (8).

[0638] Volume ratio of particles with a void volume ratio of 1 volume % or less = L / K×100…Formula (7)

[0639] Volume ratio of particles having a cavity volume ratio of 15% or more by volume = M / K × 100 ... Formula (8)

[0640] [Absorption ratio under pressure for the second urination]

[0641] Absorption capacity under pressure of the water-absorbent resin of the present invention for the second urination (unit: cm 3 / g) is measured according to the following method. Here, the absorption ratio under pressure is an index used to simulate the ability of a thin absorbent body that has swelled after absorbing the first urination to absorb urine even under pressure when absorbing the second and subsequent urinations. The absorbent body in diapers is mostly a mixture of water-absorbent resin and fiber materials such as crushed wood pulp. In the present invention, as the condition when the thinning trend is the strongest, an absorbent body that does not use fiber materials such as crushed wood pulp, that is, substantially 100% of water-absorbent resin is envisioned, and its absorption ratio under pressure is measured.

[0642] The specific determination method is as follows. Figure 7As shown in FIG. 1 , first, a cylinder 24, a piston 25, a cover 23 having two through holes for covering the cylinder 24, and a weight 22 used in the SFC measurement are prepared, 3.0 g of a water-absorbent resin 4 is placed in the cylinder 24, and then the piston 25 is inserted into the cylinder 24 in which the water-absorbent resin 4 is placed. When inserting, care is taken to prevent the water-absorbent resin 4 from being caught between the inner wall of the cylinder 24 and the piston 25. Then, the cover 23 is closed, and the weight 22 is placed on the upper part of the piston 25. Hereinafter, a set of the apparatus consisting of the water-absorbent resin 4, the cylinder 24, the piston 25, the cover 23, and the weight 22 prepared here is referred to as a unit set B. The operations so far were performed in a room adjusted to a temperature of 23±0.5°C and a humidity of 35% to 50%, and the subsequent operations were performed in a room adjusted to a temperature of 23±0.5°C and a humidity of 35% to 60%.

[0643] Next, with Figure 3 In the same manner, a surface heater 10 set at 23°C is placed on a horizontal laboratory table, and a SUS tray 9 used for AAP measurement is placed on the surface heater 10. Then, a glass filter 7 used for AAP measurement is placed in the center of the SUS tray 9, with the surface of the glass filter 7 with fewer irregularities on the upper side. Then, a filter paper 6 used for AAP measurement is placed in the center of the glass filter 7, with the surface of the filter paper 6 with fewer irregularities on the upper side. Then, the unit group B replacing the unit group A is placed in the center of the filter paper 6.

[0644] In addition, in order to measure the vertical position information of the weight 22 when the water-absorbent resin swells, a laser displacement meter manufactured by KEYENCE (amplifier unit 15 is IL-1000, sensor head 14 is IL-S100, power supply unit 16 is KZ-U3) was set up. The measurement environment is as follows: Figure 3 The unit group A in the embodiment is replaced by the unit group B, and the 0.9 mass % sodium chloride aqueous solution is not added to the SUS tray 9. Figure 3 As shown in FIG. 1 , the sensor head 14 is set such that the laser irradiated from the sensor head 14 is perpendicular to the top surface of the weight 22 in the unit group B. In addition, in order to properly reflect the irradiated laser, a white tape (product name: lead-free tape; model 21-10W; manufactured by Nitto Denko Corporation) is pasted on the portion of the top surface of the weight 22 irradiated by the laser. The situation where the tape is pasted on the top surface of the weight 22 is as follows. Figure 8As shown. Thus, the position information (numerical data) of the weight 22 in the vertical direction can be measured. The position information of the weight 22 measured by the sensor head 14 is transmitted to the data logger (midiLOGGER GL220 manufactured by GRAPHTEC Co., Ltd.) 17 and stored in the data logger 17. The data logger 17 is connected between the amplifier unit 15 and the power supply unit 16, and is set to continuously store the position information of the weight 22 at intervals of 1 second.

[0645] Under this measurement environment, 40 g of a 0.9 mass % sodium chloride aqueous solution 8 adjusted to 23 ± 0.5 ° C was measured with a 60 mL syringe, and the front end of the syringe was inserted into the hole of the cover 23 in the unit group B, and the 0.9 mass % sodium chloride aqueous solution was added to the cylinder 24 in about 6 seconds to make the water-absorbent resin 4 start to swell. Here, at the same time as the start of adding the 0.9 mass % sodium chloride aqueous solution, the laser displacement measuring instrument also started to read the position information of the weight 22. Two minutes after the start of the addition of the 0.9 mass % sodium chloride aqueous solution, 50 g of the 0.9 mass % sodium chloride aqueous solution adjusted to 23 ± 0.5 ° C was added to the cylinder from the hole of the cover in the unit group B in about 6 seconds (start of the second liquid absorption). After 8 minutes from the start of the second addition of the 0.9 mass % sodium chloride aqueous solution (start of the second liquid absorption), the laser displacement measuring instrument finished reading the position information of the weight 22 (end of the measurement).

[0646] Then, the absorption capacity under pressure during the period from the start of the second addition of the 0.9 mass % sodium chloride aqueous solution to the time when 8 minutes had passed was calculated based on the following formula (4) as the absorption capacity under pressure for absorbing the second urination (unit: cm 3 / g).

[0647] Absorption ratio under pressure for the second urination = A×C / 1000 / B…Formula (4)

[0648] in,

[0649] A: Cross-sectional area based on the inner diameter of the cylinder into which the water-absorbent resin is placed (unit: mm 2 )

[0650] B: Amount of water-absorbent resin added (unit: g)

[0651] C: The distance that the weight 22 moved in the vertical direction from the start of the second addition of the 0.9 mass % sodium chloride aqueous solution to the elapse of 8 minutes, calculated by analyzing the weight position information read by the laser displacement meter using Microsoft Excel (the difference between the weight 22 position information (value) at the start of the second liquid absorption and the weight 22 position information (value) at the end of the measurement; unit: mm)

[0652] [Initial color tone]

[0653] The initial color tone of the water-absorbent resin of the present invention is measured using the Hunter Lab colorimetric system. As a measuring device, LabScan (registered trademark) XE manufactured by Hunter Lab was used, as a measuring condition, reflective measurement was selected, and as a measuring aperture, 1.75 inches was selected. As an initial color tone measuring container, a container having an inner diameter of 9.5 cm, a height of 0.6 cm, and made of aluminum or stainless steel was used.

[0654] As a specific measurement method, first, a water-absorbent resin is put into an initial color tone measurement container until the water-absorbent resin overflows. Next, the water-absorbent resin protruding beyond the top surface of the container is scraped flat with a ruler or the like to level the powder surface. Then, the WI value of the surface of the water-absorbent resin is measured at a room temperature of 20°C to 25°C and a relative humidity of 50 RH%.

[0655] Here, if the water-absorbent resin is a water-absorbent resin just produced or just before shipment, or a water-absorbent resin stored in an atmosphere of 30° C. or less and 50% RH for less than 1 year after production, its color tone is regarded as the initial color tone.

[0656] [Table 2]

[0657]

[0658] As is apparent from Table 2, the water-absorbent resin of the present invention not only maintains the AAP value, but also improves the gel expansion force under a pressure of 4.83 kPa, and more preferably, improves the gel expansion force and the gel expansion rate, so that even when a second urination occurs after absorbing the first urination (further absorption of urine under pressure), the absorption rate under pressure is higher than that of the conventional (comparative example). That is, the absorption rate under pressure for absorbing the second urination is higher than that of the conventional (comparative example).

[0659] In contrast, the water-absorbent resin of the comparative example had a low gel expansion force under a pressure of 4.83 kPa, and both the gel expansion force and the gel expansion rate were low, so the absorption capacity under pressure for absorbing the second urination was insufficient.

[0660] Next, absorbent bodies were prepared using the surface-crosslinked water-absorbent resins obtained in Examples 1 to 4 and Comparative Examples 1 to 6. The preparation method is as follows.

[0661] [Production of absorber]

[0662] In the present invention, as the condition where the thinning trend of absorbent articles such as diapers is the strongest, an absorbent body that does not use fiber materials such as wood crushed pulp, that is, substantially 100% of the water-absorbent resin is conceived and manufactured. Specifically, Fig. 9 As shown in the figure, 3.0 g of the water-absorbent resin 4 was placed in the cylinder 24 used for the SFC measurement, and then a non-woven fabric simulating a liquid-permeable front pad (made by spunbond method, with a thickness of 0.1 mm and a mass per unit area of ​​13 g / m2) was placed on the water-absorbent resin 4 in the cylinder 24. 2 , liquid diffusion area is 18mm 2 ) 26. The nonwoven fabric 26 used here was cut into a circle having a diameter 0.2 mm shorter than the inner diameter of the cylinder 24. In addition, the thickness, unit area mass and liquid diffusion area of ​​the nonwoven fabric 26 were measured by the measurement method described later. Next, the liquid capture amount under pressure was measured using the prepared absorbent. The measurement method is as follows. In addition, the measurement results are shown in Table 3.

[0663] [Liquid capture capacity under pressure of absorbent body]

[0664] The amount of liquid captured under pressure (unit: g) of the absorbent of the present invention is measured by the following method. Here, the amount of liquid captured under pressure of the absorbent is different from the absorption capacity under pressure for the absorption of the second urination described above in that the liquid temperature of the 0.9 mass % sodium chloride aqueous solution used (preferably, colored with 0.04 g of Brilliant Blue FCF (Blue No. 1) per 1000 g of the 0.9 mass % sodium chloride aqueous solution) is changed to 36.5±0.5°C, which is close to the temperature of human urine, so that the function of the absorbent is appropriately evaluated in consideration of the actual use of the absorbent article, which is different from the absorption capacity under pressure for the absorption of the second urination.

[0665] The specific determination method is as follows. First, Fig.10As shown in FIG. 1 , a piston 25 used for the SFC measurement, a cover 23 having two through holes for covering the cylinder 24, and a weight 22 are prepared, and the piston 25 is inserted into the cylinder 24 containing the prepared absorbent. When inserting, care is taken to prevent the water-absorbent resin 4 and the nonwoven fabric 26 from being sandwiched between the inner wall of the cylinder 24 and the piston 25. Then, the cover 23 is closed, and the weight 22 is placed on the upper part of the piston 25. Hereinafter, a set of the apparatus consisting of the water-absorbent resin 4, the nonwoven fabric 26, the cylinder 24, the piston 25, the cover 23, and the weight 22 prepared here is referred to as a unit set C. The operations so far were carried out in a room adjusted to a temperature of 23±0.5°C and a humidity of 35% to 50%, and the subsequent operations were carried out in a room adjusted to a temperature of 23±0.5°C and a humidity of 35% to 60%.

[0666] The mass of the unit group C is measured and the measured mass is set as (A). Fig.11 As shown in the measurement environment, a surface heater 10 set at 23°C is placed on a horizontal experimental table, and a SUS tray 9 used for AAP measurement is placed on the surface heater 10. Then, a glass filter 7 used for AAP measurement is placed in the center of the SUS tray 9, wherein the surface of the glass filter 7 with fewer irregularities is placed on the upper side. Then, a filter paper 6 used for AAP measurement is placed in the center of the glass filter 7, wherein the surface of the filter paper 6 with fewer irregularities is placed on the upper side. Then, the unit group C is placed in the center of the filter paper 6.

[0667] Under this measurement environment, 40 g of a 0.9 mass % sodium chloride aqueous solution (preferably, colored with 0.04 g of brilliant blue FCF (blue No. 1) relative to 1000 g of the 0.9 mass % sodium chloride aqueous solution) adjusted to 36.5±0.5°C is measured with a 60 mL syringe, and the tip of the syringe is inserted into the hole of the cap 23 in the unit group C, and the 0.9 mass % sodium chloride aqueous solution is added to the cylinder 24 over about 6 seconds to start swelling the water-absorbent resin 4. Here, the time is counted from the start of the addition of the 0.9 mass % sodium chloride aqueous solution, and the mass of the unit group C is quickly measured when 2 minutes have passed, and the measured mass is set to (B). In the measurement of the mass, when the unit group C is moved from the filter paper 6 to the electronic scale, the unit group C is not disassembled, but its structure is maintained. Specifically, the outer wall portion of the cylinder 24 is grasped by hand to carry it, and at this time, care is taken not to touch the cap 23, the piston 25, and the weight 22 provided on the upper part of the piston 25. In addition, when measuring the mass, the filter paper 6 on the glass filter 7 is replaced with an unused filter paper in parallel. After measuring the mass, the unit group C is placed again on the center of the unused filter paper 6, and the syringe is used again in substantially the same manner as described above, and 40 g of a 0.9 mass % sodium chloride aqueous solution (preferably, colored with 0.04 g of brilliant blue FCF (blue No. 1) relative to 1000 g of the 0.9 mass % sodium chloride aqueous solution) adjusted to 36.5±0.5°C is added to the cylinder 24 from the hole of the cover 23 in the unit group C over about 6 seconds. The mass measurement operation of the unit group C and the replacement operation of the filter paper 6 are completed within 30 seconds. That is, the second addition of the 0.9 mass % sodium chloride aqueous solution is started within 2 minutes and 30 seconds from the start of the first addition of the 0.9 mass % sodium chloride aqueous solution. Then, the time was counted from the time when the second addition of the 0.9 mass % sodium chloride aqueous solution was started, and when 3 minutes had passed, the mass of the unit group C was quickly measured, and the measured mass was set as (C). When the mass was measured, when the unit group C was moved from the filter paper 6 to an electronic scale, the unit group C was not disassembled as described above, but its structure was maintained.

[0668] Then, the amount of liquid captured under pressure during the period from the start of the second addition of the 0.9 mass % sodium chloride aqueous solution to the time when 3 minutes had passed was calculated based on the following formula (5) as the amount of liquid captured under pressure by the absorbent for the second urination (unit: g). Here, the amount of liquid captured under pressure by the absorbent for the second urination is an indicator for evaluating the ability of the absorbent to absorb urine even under pressure when the absorbent, which has swelled after absorbing the first urination, absorbs the second and subsequent urinations.

[0669] The amount of liquid captured by the absorber under pressure for the second urination = (C) - (B) ... Formula (5)

[0670] In addition, based on the following formula (6), the total amount of liquid captured under pressure during the period from the start of the first addition of the 0.9 mass % sodium chloride aqueous solution to the elapse of 2 minutes and the total amount of liquid captured under pressure during the period from the start of the second addition of the 0.9 mass % sodium chloride aqueous solution to the elapse of 3 minutes were calculated, and this total amount was used as the total liquid captured under pressure (unit: g) absorbed by the absorbent for the first and second urination.

[0671] Total liquid capture under pressure of the absorber for the first and second urination = (C) - (A) Formula (6)

[0672] Here, in the present measurement, when measuring (B) and (C), if 0.9 mass % sodium chloride aqueous solution remains on the layer of the swollen water-absorbent resin, it is regarded as impossible to measure. In other words, if 0.9 mass % sodium chloride aqueous solution remains on the layer of the swollen water-absorbent resin visually observed during the measurement, it is regarded as impossible to measure the "liquid capture capacity under pressure absorbed by the absorbent body for the second urination" and the "total liquid capture capacity under pressure absorbed by the absorbent body for the first and second urination" for the water-absorbent resin.

[0673] [Thickness of nonwoven fabric]

[0674] The thickness (unit: mm) of the nonwoven fabric used in measuring the amount of liquid captured under pressure of the absorbent was measured by the following measurement method. That is, a large-scale dial-type thickness gauge (thickness measuring device) (manufactured by Ozaki Seisakusho Co., Ltd.; model: JB; probe specifications: upper and lower bases of the reference table) was used. ) to measure the thickness of the nonwoven fabric. The number of measurements was measured at 5 different locations, and the average value of the 5 locations was used as the measured value. When measuring the thickness, in order to minimize the application of pressure to the nonwoven fabric, the hand was slowly released from the handle to measure the thickness.

[0675] [Weight per unit area of ​​nonwoven fabric]

[0676] The mass per unit area (unit: g / m2) of the nonwoven fabric used in measuring the amount of liquid captured under pressure of the absorbent body was measured by the following measurement method. 2 That is, the mass of a rectangular nonwoven fabric cut into a width of more than 10 cm and a length of more than 40 cm was measured, and then the measured mass was divided by the area of ​​the cut nonwoven fabric to calculate the mass per unit area.

[0677] [Liquid diffusion area of ​​nonwoven fabric]

[0678] The liquid diffusion area (unit: mm) of the nonwoven fabric used in measuring the liquid capture capacity under pressure of the absorbent body was measured by the following measurement method. 2 ) was measured. That is, a 30cm diameter stainless steel sieve with a mesh size of 2mm and a mesh wire diameter of 0.9mm was placed on a horizontal laboratory table, and a non-woven fabric cut into 10cm squares was placed on the mesh of the sieve. A 0.50mm-caliber injection needle was installed on a syringe with a capacity of 1mL, and 1.00g of a 0.9% sodium chloride aqueous solution containing 20ppm of brilliant blue FCF (blue No. 1) was measured, and the sodium chloride aqueous solution was injected into the center of the non-woven fabric on the sieve in a direction perpendicular to the non-woven fabric. At this time, in order to prevent the sodium chloride aqueous solution that has passed through the non-woven fabric and the screen from reattaching to the screen or non-woven fabric, sufficient space is provided between the bottom of the screen and the laboratory table. At the point when the non-woven fabric absorbs the sodium chloride aqueous solution and the liquid diffusion is completed, the diffusion area of ​​the sodium chloride aqueous solution is measured.

[0679] [Table 3]

[0680]

[0681] As is apparent from Table 3, by maintaining the AAP value of the water-absorbent resin and increasing the gel expansion force under 4.83 kPa pressure, more preferably increasing the gel expansion force and the gel expansion rate, the absorbent containing the water-absorbent resin can have a higher liquid capture amount under pressure than before even in the case where a second urination occurs after absorbing the first urination (further absorption of urine under pressure). That is, the liquid capture amount under pressure for absorbing the second urination is higher than before. In addition, the total liquid capture amount under pressure for absorbing the first and second urination is also higher than before.

[0682] In contrast, the water-absorbent resin of the comparative example has a low gel expansion force under a pressure of 4.83 kPa, and both the gel expansion force and the gel expansion rate are low, so the amount of liquid captured under pressure by the absorbent body containing the water-absorbent resin for the second urination is insufficient. In addition, the total amount of liquid captured under pressure by the absorbent body for the first and second urination is also insufficient.

[0683] An embodiment of the present invention includes the following aspects.

[0684] [1] An absorbent body comprising a water-absorbent resin having a gel expansion force of 26 N or more under a pressure of 4.83 kPa.

[0685] [2] The absorbent body according to [1], wherein the mass ratio of the water-absorbent resin in the total mass of the absorbent body is 75 mass % or more and 100 mass % or less.

[0686] [3] An absorbent article comprising the absorbent body described in [1] or [2].

[0687] [4] A water-absorbent resin having a gel expansion force of 26 N or more under a pressure of 4.83 kPa.

[0688] [5] The water-absorbent resin according to [4], characterized in that the gel expansion rate under a pressure of 4.83 kPa is 8.5 or more.

[0689] [6] The water-absorbent resin according to [4] or [5], wherein the volume of the particles having a cavity volume fraction of 15% by volume or more accounts for 40% by volume or more of the total volume of the water-absorbent resin.

[0690] [7] The water-absorbent resin according to any one of [4] to [6], wherein the volume of particles having a void volume fraction of 1% by volume or less accounts for 65% by volume or more of the total volume of the water-absorbent resin.

[0691] [8] The water-absorbent resin according to any one of [4] to [7], wherein the water-absorbent resin has a non-loaded absorption capacity (CRC) of 25 g / g or more.

[0692] [9] The water-absorbent resin according to any one of [4] to [8], wherein the absorption against pressure (AAP) at a pressure of 4.83 kPa is 20 g / g or more.

[0693]

[10] The water-absorbent resin according to any one of [4] to [9], wherein the saline flow conductivity (SFC) is 15 (×10 -7 cm 3 ·sec / g) and above and 55(×10 -7 cm 3 ·sec / g) or less.

[0694]

[11] The water-absorbent resin according to any one of [4] to

[10] , characterized in that the water-absorbent resin has a mass average particle size (D50) of 250 μm to 550 μm, the mass of particles having a particle size exceeding 710 μm accounts for no more than 2 mass % of the total mass of the water-absorbent resin, and the mass of particles having a particle size less than 150 μm accounts for no more than 3 mass % of the total mass of the water-absorbent resin.

[0695] (Industrial Applicability)

[0696] When the absorbent of the present invention is used in an absorbent article such as a thin diaper having an absorbent with a low content ratio of fiber materials such as pulp, the absorbent has a higher liquid capture capacity under pressure for urination after the second time than before, and as a result, the absorbent article such as diaper has a higher liquid capture function than before. In addition, even if the water-absorbent resin of the present invention is used in an absorbent article such as a thin diaper having an absorbent with a low content ratio of fiber materials such as pulp, the absorbent has a high absorption rate under pressure for urination after the second time, and as a result, the absorbent has a high liquid capture capacity under pressure for urination after the second time. Therefore, the absorbent and water-absorbent resin of the present invention can be preferably used in absorbent articles such as thin diapers having a low content ratio of fiber materials such as pulp. In addition, the absorbent and water-absorbent resin of the present invention can also be preferably used in various applications such as absorbent articles other than diapers (sanitary napkins, incontinence pads, etc.), soil water-retaining agents for agriculture and horticulture, and industrial water-stopping agents.

Claims

1. An absorbent body, characterized in that: The invention comprises a water-absorbent resin having a gel swelling force of 26 N or more, wherein the gel swelling force is the force at which the water-absorbent resin, which has swelled to a gel thickness of 5 mm, expands against a pressure of 4.83 kPa when the water-absorbent resin further swells, and is the maximum force during the period from the start of the measurement to the time when 1000 seconds have passed, The absorbent body uses a water-absorbent resin in which the volume of particles having a cavity volume ratio of 15 volume % or more occupies 40 volume % or more and the volume of particles having a cavity volume ratio of 1 volume % or less occupies 65 volume % or more of the total volume of the water-absorbent resin.

2. The absorbent body according to claim 1, The water-absorbent resin having a gel swelling force of 27N or more is used.

3. The absorbent body according to claim 1, The water-absorbent resin having the gel swelling force of 28N or more is used.

4. The absorbent body according to claim 1, The water-absorbent resin having a gel swelling force of 40 N or less is used.

5. The absorbent body according to claim 1, The water-absorbent resin having a gel swelling force of 35 N or less is used.

6. The absorbent body according to claim 1, The water-absorbent resin used has a gel swelling rate of 8.5 or more. The gel swelling rate is the slope of a curve represented by data from the start of measurement to the time when 100 seconds have passed, with the vertical axis representing the force required to resist a pressure of 4.83 kPa and the horizontal axis representing the measurement time when the water-absorbent resin that has swelled to a gel thickness of 5 mm further swells.

7. The absorbent body according to claim 1, The water-absorbent resin used has a gel swelling rate of 9.0 or more, wherein the gel swelling rate is the slope of a curve represented by data from the start of measurement to the time when 100 seconds have passed, with the vertical axis being the force required to resist a pressure of 4.83 kPa and the horizontal axis being the measurement time, when the water-absorbent resin swelled to a gel thickness of 5 mm further swells.

8. The absorbent body according to claim 1, The water-absorbent resin used has a gel swelling rate of 15.0 or less. The gel swelling rate is the slope of a curve represented by data from the start of measurement to the time when 100 seconds have passed, with the vertical axis being the force required to resist a pressure of 4.83 kPa and the horizontal axis being the measurement time, when the water-absorbent resin that has swelled to a gel thickness of 5 mm further swells.

9. The absorbent body according to claim 1, The water-absorbent resin used has a gel swelling rate of 14.0 or less. The gel swelling rate is the slope of a curve represented by data from the start of measurement to the time when 100 seconds have passed, with the vertical axis being the force required to resist a pressure of 4.83 kPa and the horizontal axis being the measurement time, when the water-absorbent resin that has swelled to a gel thickness of 5 mm further swells.

10. The absorbent body according to claim 1, The water-absorbent resin used is one in which the volume occupancy rate of particles having a cavity volume rate of 15% by volume or more is 42% by volume or more in the total volume of the water-absorbent resin.

11. The absorbent body according to claim 1, The water-absorbent resin used is one in which the volume occupancy rate of particles having a cavity volume rate of 15% by volume or more is 44% by volume or more in the total volume of the water-absorbent resin.

12. The absorbent body according to claim 1, The water-absorbent resin used is one in which the volume occupancy rate of particles having a void volume rate of 1 volume % or less is 67 volume % or more in the total volume of the water-absorbent resin.

13. The absorbent body according to claim 1, The water-absorbent resin used is one in which the volume occupancy rate of particles having a void volume rate of 1 volume % or less is 70 volume % or more in the total volume of the water-absorbent resin.

14. The absorbent body according to claim 1, The water-absorbent resin used is one in which the volume occupancy rate of particles having a void volume rate of 1 volume % or less is 72 volume % or more in the total volume of the water-absorbent resin.

15. The absorbent body according to claim 1, The water-absorbent resin used is one in which the volume occupancy rate of particles having a void volume rate of 1 volume % or less is 73 volume % or more in the total volume of the water-absorbent resin.

16. The absorbent body according to claim 1, The water-absorbent resin used is one in which the volume occupancy rate of particles having a cavity volume rate of 15 volume % or more and a cavity volume rate of 1 volume % or less is 20 volume % or more in the total volume of the water-absorbent resin.

17. The absorbent body according to claim 1, The water-absorbent resin used is one in which the volume occupancy rate of particles having a cavity volume rate of 15 volume % or more and a cavity volume rate of 1 volume % or less in the total volume of the water-absorbent resin is 25 volume % or more.

18. The absorbent body according to claim 1, The water-absorbent resin having a CRC of 25 g / g or more is used.

19. The absorbent body according to claim 1, The water-absorbent resin having a CRC of 27 g / g or more is used.

20. The absorbent body according to claim 1, The water-absorbent resin having a CRC of 28 g / g or more is used.

21. The absorbent body according to claim 1, A water-absorbent resin having a CRC of 40 g / g or less is used.

22. The absorbent body according to claim 1, A water-absorbent resin having a CRC of 38 g / g or less is used.

23. The absorbent body according to claim 1, The water-absorbent resin having an absorption against pressure AAP of 20 g / g or more under a pressure of 4.83 kPa is used.

24. The absorbent body according to claim 1, The water-absorbent resin having an absorption against pressure AAP of 23 g / g or more under a pressure of 4.83 kPa is used.

25. The absorbent body according to claim 1, The water-absorbent resin having an absorption against pressure AAP of 24 g / g or more under a pressure of 4.83 kPa is used.

26. The absorbent body according to claim 1, The water-absorbent resin having an absorption capacity against pressure AAP of 24.5 g / g or more under a pressure of 4.83 kPa is used.

27. The absorbent body according to claim 1, The water-absorbent resin having an absorption against pressure AAP of 25.0 g / g or more under a pressure of 4.83 kPa is used.

28. The absorbent body according to claim 1, The saline conductivity SFC used to evaluate fluid diffusion is 15×10 -7 cm 3 · Water-absorbent resin with a water absorption rate of more than sec / g.

29. The absorbent body according to claim 1, The saline conductivity SFC used to evaluate fluid diffusion is 18×10 -7 cm 3 · Water-absorbent resin with a water absorption rate of more than sec / g.

30. The absorbent body according to claim 1, The saline conductivity SFC used to evaluate fluid diffusion is 20×10 -7 cm 3 · Water-absorbent resin with a water absorption rate of more than sec / g.

31. The absorbent body according to claim 1, The saline conductivity SFC used to evaluate fluid diffusion is 55×10 -7 cm 3 · Water-absorbent resin with a water absorption capacity of less than sec / g.

32. The absorbent body according to claim 1, The saline conductivity SFC used to evaluate fluid diffusion is 53×10 -7 cm 3 · Water-absorbent resin with a water absorption capacity of less than sec / g.

33. The absorbent body according to claim 1, A water-absorbent resin having a mass average particle size D50 of 250 μm or more is used.

34. The absorbent body according to claim 1, A water-absorbent resin having a mass average particle size D50 of 300 μm or more is used.

35. The absorbent body according to claim 1, A water-absorbent resin having a mass average particle size D50 of 550 μm or less is used.

36. The absorbent body according to claim 1, A water-absorbent resin having a mass average particle size D50 of 500 μm or less is used.

37. The absorbent body according to claim 1, The water-absorbent resin used is one in which the mass of the water-absorbent resin having a particle size of less than 150 μm accounts for 3 mass % or less of the total mass of the water-absorbent resin.

38. The absorbent body according to claim 1, The water-absorbent resin used is one in which the mass of the water-absorbent resin having a particle size of less than 150 μm accounts for 2 mass % or less of the total mass of the water-absorbent resin.

39. The absorbent body according to claim 1, The water-absorbent resin used is one in which the mass of the water-absorbent resin having a particle size exceeding 710 μm accounts for 2 mass % or less of the total mass of the water-absorbent resin.

40. The absorbent body according to claim 1, The water-absorbent resin used is one in which the mass of the water-absorbent resin having a particle size exceeding 710 μm accounts for 1 mass % or less of the total mass of the water-absorbent resin.

41. The absorbent body according to claim 1, The water-absorbent resin used has a gel thickness reaching 5 mm time of 150 seconds or less.

42. The absorbent body according to claim 1, The water-absorbent resin used has a gel thickness reaching 5 mm time of 140 seconds or less.

43. The absorbent body according to claim 1, comprising: The absorption rate for urination after the second time is 14cm at a pressure of 0.3psi 3 / g or more water-absorbent resin.

44. The absorbent body according to claim 1, A water-absorbent resin having a WI value of 45 or more as an initial color tone is used.

45. The absorbent body according to claim 1, A water-absorbent resin having a WI value of 50 or more as an initial color tone is used.

46. ​​The absorbent body according to claim 1, A water-absorbent resin having a WI value of 52 or more as an initial color tone is used.

47. The absorbent body according to claim 1, wherein: The amount of liquid captured under a pressure of 0.3 psi for absorbing the second and subsequent urinations is 34.5 g or more.

48. The absorbent body according to claim 1, wherein The amount of liquid captured under a pressure of 0.3 psi for absorbing the second and subsequent urinations is 35.0 g or more.

49. The absorbent body according to claim 1, wherein The amount of liquid captured under a pressure of 0.3 psi for absorbing the second and subsequent urinations is 35.5 g or more.

50. The absorbent body according to claim 1, wherein The total liquid capture amount under a pressure of 0.3 psi for absorbing the first and second urinations was 72.0 g or more.

51. The absorbent body according to claim 1, wherein The total liquid capture amount under a pressure of 0.3 psi for absorbing the first and second urinations was 72.5 g or more.

52. The absorbent body according to claim 1, wherein: The total liquid capture amount under a pressure of 0.3 psi for absorbing the first and second urinations was 73.0 g or more.

53. The absorbent body according to claim 1, wherein: The absorbent body is formed into a sheet shape.

54. The absorbent body according to claim 1, wherein The absorbent body is formed into a cylindrical shape.

55. The absorbent body according to claim 1, which has a structure in which a layer containing a water-absorbent resin and hydrophilic fibers is sandwiched by nonwoven fabrics from above and / or below.

56. The absorbent body according to claim 55, wherein The nonwoven fabric has a unit area mass of 5 to 300 g / m 2 .

57. The absorbent body according to claim 55, wherein The nonwoven fabric has a thickness of 20 to 800 μm.

58. The absorbent body according to claim 55, wherein The liquid diffusion area of ​​the nonwoven fabric is 1 to 100 m 2 .

59. The absorbent body according to claim 55, wherein an adhesive binder is used, and a mass ratio between the water-absorbent resin and the adhesive binder is in the range of 50 / 50 to 99 / 1.

60. The absorbent body according to claim 59, wherein The mass ratio between the water-absorbing resin and the adhesive binder is in the range of 70 / 30 to 95 / 5.

61. The absorbent body according to claim 59, wherein The mass ratio between the water-absorbing resin and the adhesive binder is in the range of 80 / 20 to 95 / 5.

62. The absorbent body according to claim 1, characterized in that The mass ratio of the water-absorbent resin in the total mass of the absorbent body is 75 mass % or more and 100 mass % or less.

63. The absorbent body according to claim 1, characterized in that The mass ratio of the water-absorbent resin in the total mass of the absorbent body is 80 mass % or more and 100 mass % or less.

64. The absorbent body according to claim 1, characterized in that The mass ratio of the water-absorbent resin in the total mass of the absorbent body is 85 mass % or more and 100 mass % or less.

65. The absorbent body according to claim 1, characterized in that The mass ratio of the water-absorbent resin in the total mass of the absorbent body is 90 mass % or more and 100 mass % or less.

66. An absorbent article comprising the absorbent body according to any one of claims 1 to 65.

67. A water-absorbent resin, characterized in that The gel swelling force is 26 N or more, which is the force that the water-absorbent resin that has swelled to a gel thickness of 5 mm will expand against a pressure of 4.83 kPa when it swells further, and is the maximum force from the start of the measurement to the time when 1000 seconds have passed. The volume of the particles having a cavity volume ratio of 15% or more accounts for 40% or more of the total volume of the water-absorbent resin. The volume of particles having a void volume ratio of 1 volume % or less accounts for 65 volume % or more of the total volume of the water-absorbent resin.

68. The water-absorbent resin according to claim 67, characterized in that The gel expansion force is greater than 27N.

69. The water-absorbent resin according to claim 67, characterized in that The gel expansion force is greater than 28N.

70. The water-absorbent resin according to claim 67, characterized in that The gel expansion force is less than 40N.

71. The water-absorbent resin according to claim 67, characterized in that The gel expansion force is 35N or less.

72. The water-absorbent resin according to claim 67, characterized in that The gel swelling rate is 8.5 or more, wherein the gel swelling rate is the slope of a curve represented by data from the start of measurement to the time when 100 seconds have passed, with the vertical axis representing the force of swelling against a pressure of 4.83 kPa and the horizontal axis representing the measurement time, when the water-absorbent resin that has swelled to a gel thickness of 5 mm further swells.

73. The water-absorbent resin according to claim 67, characterized in that The gel swelling rate is 9.0 or more, wherein the gel swelling rate is the slope of a curve represented by data from the start of measurement to the time when 100 seconds have passed, with the vertical axis representing the force of swelling against a pressure of 4.83 kPa and the horizontal axis representing the measurement time, when the water-absorbent resin that has swelled to a gel thickness of 5 mm further swells.

74. The water-absorbent resin according to claim 67, characterized in that The gel swelling rate is 15.0 or less, wherein the gel swelling rate is the slope of a curve represented by data from the start of measurement to the time when 100 seconds have passed, with the vertical axis representing the force of swelling against a pressure of 4.83 kPa and the horizontal axis representing the measurement time, when the water-absorbent resin that has swelled to a gel thickness of 5 mm further swells.

75. The water-absorbent resin according to claim 67, characterized in that The gel swelling rate is 14.0 or less, wherein the gel swelling rate is the slope of a curve represented by data from the start of measurement to the time when 100 seconds have passed, with the vertical axis representing the force of swelling against a pressure of 4.83 kPa and the horizontal axis representing the measurement time, when the water-absorbent resin that has swelled to a gel thickness of 5 mm further swells.

76. The water-absorbent resin according to any one of claims 67 to 75, characterized in that The volume of the particles having a cavity volume ratio of 15% by volume or more accounts for 42% by volume or more of the total volume of the water-absorbent resin.

77. The water-absorbent resin according to any one of claims 67 to 75, characterized in that The volume of the particles having a cavity volume ratio of 15% by volume or more accounts for 44% by volume or more of the total volume of the water-absorbent resin.

78. The water-absorbent resin according to any one of claims 67 to 75, characterized in that The volume of particles having a void volume ratio of 1 volume % or less accounts for 67 volume % or more of the total volume of the water-absorbent resin.

79. The water-absorbent resin according to any one of claims 67 to 75, characterized in that The volume of particles having a void volume ratio of 1 volume % or less accounts for 70 volume % or more of the total volume of the water-absorbent resin.

80. The water-absorbent resin according to any one of claims 67 to 75, characterized in that The volume of particles having a void volume ratio of 1 volume % or less accounts for 72 volume % or more of the total volume of the water-absorbent resin.

81. The water-absorbent resin according to any one of claims 67 to 75, characterized in that The volume of particles having a void volume ratio of 1 volume % or less accounts for 73 volume % or more of the total volume of the water-absorbent resin.

82. The water-absorbent resin according to any one of claims 67 to 75, characterized in that The volume occupancy rate of the particles having a cavity volume rate of 15 volume % or more and a cavity volume rate of 1 volume % or less in the total volume of the water-absorbent resin is 20 volume % or more.

83. The water-absorbent resin according to any one of claims 67 to 75, characterized in that The volume occupancy rate of the particles having a cavity volume rate of 15 volume % or more and a cavity volume rate of 1 volume % or less in the total volume of the water-absorbent resin is 25 volume % or more.

84. The water-absorbent resin according to any one of claims 67 to 75, characterized in that The absorption capacity without pressure CRC is 25 g / g or more.

85. The water-absorbent resin according to any one of claims 67 to 75, characterized in that The absorption capacity without pressure CRC is 27 g / g or more.

86. The water-absorbent resin according to any one of claims 67 to 75, characterized in that The absorption capacity without pressure CRC is 28 g / g or more.

87. The water-absorbent resin according to any one of claims 67 to 75, characterized in that The absorption capacity without pressure CRC is 40 g / g or less.

88. The water-absorbent resin according to any one of claims 67 to 75, characterized in that The absorption capacity without pressure CRC is 38 g / g or less.

89. The water-absorbent resin according to any one of claims 67 to 75, characterized in that The absorption capacity under pressure AAP under a pressure of 4.83 kPa is 20 g / g or more.

90. The water-absorbent resin according to any one of claims 67 to 75, characterized in that The absorption capacity under pressure AAP under a pressure of 4.83 kPa is 23 g / g or more.

91. The water-absorbent resin according to any one of claims 67 to 75, characterized in that The absorption capacity under pressure AAP under a pressure of 4.83 kPa is 24 g / g or more.

92. The water-absorbent resin according to any one of claims 67 to 75, characterized in that The absorption capacity under pressure AAP under a pressure of 4.83 kPa is 24.5 g / g or more.

93. The water-absorbent resin according to any one of claims 67 to 75, characterized in that The absorption capacity under pressure AAP under a pressure of 4.83 kPa is 25 g / g or more.

94. The water-absorbent resin according to any one of claims 67 to 75, characterized in that The saline conductivity SFC is 15×10 -7 cm 3 sec / g or more and 55×10 -7 cm 3 ·Sec / g or less.

95. The water-absorbent resin according to any one of claims 67 to 75, characterized in that The saline conductivity SFC is 18×10 -7 cm 3 ·sec / g or more and 53×10 -7 cm 3 ·Sec / g or less.

96. The water-absorbent resin according to any one of claims 67 to 75, characterized in that The saline conductivity SFC is 20×10 -7 cm 3 ·sec / g or more and 53×10 -7 cm 3 ·Sec / g or less.

97. The water-absorbent resin according to any one of claims 67 to 75, characterized in that The water-absorbent resin has a mass average particle size D50 of 250 μm or more and 550 μm or less, The mass of particles having a particle size exceeding 710 μm accounts for 2 mass % or less of the total mass of the water-absorbent resin, and the mass of particles having a particle size below 150 μm accounts for 3 mass % or less of the total mass of the water-absorbent resin.

98. The water-absorbent resin according to any one of claims 67 to 75, characterized in that The water-absorbent resin has a mass average particle size D50 of 250 μm or more and 550 μm or less, The mass of particles having a particle size exceeding 710 μm accounts for 1 mass % or less of the total mass of the water-absorbent resin, and the mass of particles having a particle size less than 150 μm accounts for 2 mass % or less of the total mass of the water-absorbent resin.

99. The water-absorbent resin according to any one of claims 67 to 75, wherein The time required for the water-absorbent resin to reach a gel thickness of 5 mm is 150 seconds or less.

100. The water-absorbent resin according to any one of claims 67 to 75, wherein The time required for the water-absorbent resin to reach a gel thickness of 5 mm is 140 seconds or less.

101. The water-absorbent resin according to any one of claims 67 to 75, wherein The absorption rate for the second urination under a pressure of 0.3 psi is 14 cm 3 / g or above.

102. The water-absorbent resin according to any one of claims 67 to 75, wherein The WI value as the initial color tone of the water-absorbent resin is 45 or more.

103. The water-absorbent resin according to any one of claims 67 to 75, wherein The WI value as the initial color tone of the water-absorbent resin is 50 or more.

104. The water-absorbent resin according to any one of claims 67 to 75, wherein The WI value as the initial color tone of the water-absorbent resin is 52 or more.

105. The water-absorbent resin according to any one of claims 67 to 75, wherein The particle shape of the water-absorbent resin is a random particle shape having recesses and cavities.

Citation Information

Patent Citations

  • Superabsorbent polymer

    EP3260485A1

  • Highly absorbent resin and method for producing same

    EP3438162A1

  • Absorbale article

    JP1984105448A

  • Water absorbent

    JP1985158861A

  • Absorbable article

    JP1990041155A